15th annual conference of the DPKK - Taubert, Helge; Becker, Christoph; Borkowetz, Angelika; Seitz, Gerhard; Kristiansen, Glen; Wach, Sven; Wullich, Bernd (Urologe, 2018)
EVALuna2:35886

68Ga-PSMA-11 PET/CT-derived metabolic parameters for determination of whole-body tumor burden and treatment response in prostate cancer - Schmidkonz, Christian; Cordes, Michael; Schmidt, Daniela; Bäuerle, Tobias; Goetz, Theresa Ida; Beck, Michael; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2018)
PURPOSE: We aimed at evaluating the role of 68Ga-PSMA-11 PET/CT-derived metabolic parameters for assessment of whole-body tumor burden and its capability to determine therapeutic response in patients with prostate cancer. METHODS: A total of 142 patients with biochemical recurrence of prostate cancer underwent PET/CT with [68Ga]Ga-PSMA-HBED-CC (68Ga-PSMA-11). Quantitative assessment of all 641 68Ga-PSMA-11-positive lesions in the field of view was performed to calculate PSMA-derived parameters, including whole-body PSMA tumor volume (PSMA-TV) and whole-body total lesion PSMA (TL-PSMA), as well as the established SUVmax and SUVmean values. All PET-derived parameters were tested for correlation with serum PSA levels and for association with Gleason scores. In 23 patients who underwent 68Ga-PSMA-11 PET/CT before and after therapy with either external beam radiation, androgen deprivation, or docetaxel chemotherapy, SUVmax and TL-PSMA were compared to radiographic response assessment of CT images based on RECIST 1.1 criteria and to biochemical response determined by changes of serum PSA levels. RESULTS: PSMA-TV and TL-PSMA demonstrated a significant correlation with serum PSA levels (P < 0.0001) and TL-PSMA was significantly different for different Gleason scores. The agreement rate between TL-PSMA derived from PET and biochemical response was 87% (95% confidence interval, 0.66-0.97; Cohen's κ = 0.78; P < 0.01) and, thus, higher than for SUVmax, which was 74% (95% CI, 0.52-0.90; κ = 0.55; P < 0.01). Furthermore, agreement with PSA was higher for TL-PSMA and SUVmax than for CT-based response evaluation. Discordant findings between PET and CT were most likely due to limitations of CT and RECIST in rating small lymph nodes as metastases, as well as bone involvement, which was sometimes not detectable in CT. CONCLUSION: 68Ga-PSMA-11 PET/CT-derived metabolic tumor parameters showed promising results for evaluation of treatment response. Especially, TL-PSMA demonstrated higher agreement rates with biochemical response compared to SUVmax. Larger, ideally prospective trials are needed to help to reveal the full potential of metabolic parameters derived from PET imaging with 68Ga-PSMA-11.
EVALuna2:34269

68Ga-PSMA-11 PET/CT derived quantitative volumetric tumor parameters for classification and evaluation of therapeutic response of bone metastases in prostate cancer patients - Schmidkonz, Christian; Cordes, Michael; Goetz, Theresa Ida; Prante, Olaf; Kuwert, Torsten; Ritt, Philipp; Uder, Michael; Wullich, Bernd; Goebell, Peter; Bäuerle, Tobias (Annals of Nuclear Medicine, 2019)
Background: To evaluate the role of 68Gallium prostate-specific membrane antigen-positron emission tomography/computed tomography (68Ga-PSMA-11 PET/CT) derived quantitative volumetric tumor parameters in comparison with fully diagnostic conventional CT and serum-PSA levels for classification and evaluation of therapeutic response of bone metastases in patients with metastasized prostate cancer (PC). Methods: A total of 177 men with biochemical recurrence of prostate cancer suffering from bone metastases underwent PET/CT with [68Ga] Ga-PSMA-HBED-CC (68Ga-PSMA-11). To calculate 68Ga-PSMA-11 PET quantitative volumetric tumor parameters including whole-body total-lesion PSMA (TL-PSMA), whole-body PSMA-tumor volume (PSMA-TV), as well as the established maximum standard uptake values (SUVmax) and mean standard uptake values (SUVmean), all 443 68Ga-PSMA-11-positive bone lesions in the field of view were assessed quantitatively. Quantitative volumetric tumor parameters were correlated with CT-derived volume and bone density measurements of metastatic bone lesions, serum prostate-specific antigen (PSA) levels, and Gleason Scores. In the 20 patients suffering from bone metastases who underwent 68Ga-PSMA-11 PET/CT before and after therapy, CT-derived volume and bone density measurements of metastatic lesions were compared to biochemical response determined by serum-PSA levels. Results: In 177 patients, a total of 443 68Ga-PSMA-11 PET-positive bone lesions were detected. Of these, 50 lesions (11%) were only detectable on PET but not on conventional CT. PET-positive/CT-negative bone metastases demonstrated a significantly lower PSMA uptake compared to PET-positive/CT-positive bone lesions (p < 0.05). SUVmax, SUVmean, PSMA-TV, and TL-PSMA of bone metastases were significantly higher (p < 0.05) in patients with Gleason Scores > 7 compared to those with Gleason Scores ≤ 7. In the linear regression analysis, an association was determined between SUVmean, Gleason Scores, lesion classification, and serum-PSA levels but not for CT-derived bone density measurements. No significant correlation could be found between changes of bone density and CT-derived volume measurements of metastatic bone lesions and changes of serum-PSA levels (p > 0.05) before and after therapy, while a highly significant correlation was observed for changes of PSMA-TV, TL-PSMA, and serum-PSA levels (p < 0.001). Conclusion: Our results suggest that 68Ga-PSMA-11 PET/CT might be a valuable tool for the detection and follow-up of bone metastases in patients with metastasized prostate cancer. 68Ga-PSMA-11 PET-derived quantitative volumetric parameters demonstrated a highly significant correlation with changes of serum-PSA levels during the course of therapy. No such correlation could be determined for bone density measurements of metastatic bone lesions. Compared to the fully diagnostic CT scan, a significantly higher proportion of bone metastases was detected on 68Ga-PSMA-11 PET.
CRIS-Team Scopus Importer:2019-08-02
Keywords: 68Ga-PSMA-11 PET/CT; Bone metastases; Quantitative tumor parameters; Treatment response

99m Tc-MIP-1404-SPECT/CT for the detection of PSMA-positive lesions in 225 patients with biochemical recurrence of prostate cancer - Schmidkonz, Christian; Hollweg, Claudia; Beck, Michael; Reinfelder, Julia; Götz, Theresa; Sanders, James Chester; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; et al. (Prostate, 2018)
99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc., New York, NY) is a novel, SPECT-compatible 99m Tc-labeled PSMA inhibitor for the detection of prostate cancer. We present results of its clinical use in a cohort of 225 men with histologically confirmed prostate cancer referred for workup of biochemical relapse.From April 2013 to April 2017, 99m Tc-MIP1404-scintigraphy was performed in 225 patients for workup of PSA biochemical relapse of prostate cancer. Whole-body planar and SPECT/CT images of the lower abdomen and thorax were obtained 3-4 h p.i. of 710 ± 64 MBq 99m Tc-MIP-1404. Images were visually analyzed for presence and location of abnormal uptake. In addition, quantitative analysis of the SPECT/CT data was carried out on a subset of 125 patients. Follow-up reports of subsequent therapeutic interventions were available for 59% (139) of all patients.Tracer-positive lesions were detected in 77% (174/225) of all patients. Detections occurred at the area of local recurrence in the prostate in 25% of patients (or a total of 56), with metastases in lymph nodes in 47% (105), bone in 27% (60), lung in 5% (12), and other locations in 2% (4) of patients. Detection rates were 90% at PSA levels >=2 ng/mL and 54% below that threshold. Lesional SUVmax values were, on average, 32.2 ± 29.6 (0.8-142.2), and tumor-to-normal ratios 146.6 ± 160.5 (1.9-1482.4). The PSA level correlated significantly with total uptake of MIP-1404 in tumors (P < 0.001). Furthermore, total tumor uptake was significantly higher in patients with Gleason scores >=8 compared to those with Gleason scores <=7 (P < 0.05). In patients with androgen deprivation therapy, the detection rate was significantly higher compared to patients without androgen deprivation therapy (86% vs 71%, P < 0.001). Based on 99m Tc-MIP-1404-imaging and other information, an interdisciplinary tumor board review recommended changes to treatment plans in 74% (104/139) of those patients for whom the necessary documentation was available.SPECT/CT with 99m Tc-labeled MIP-1404 has a high probability in detecting PSMA-positive lesions in patients with elevated PSA. Statistical analysis disclosed significant relationship between quantitative 99m Tc-MIP-1404 uptake, PSA level, and Gleason score.
EVALuna2:13874

Abdominal Panniculectomy Can Simplify Kidney Transplantation in Obese Patients - Promny, Dominik; Hauck, Theresa; Cai, Aijia; Arkudas, Andreas; Heller, Katharina M.; Wullich, Bernd; Apel, Hendrik; Horch, Raymund E.; Ludolph, Ingo (Urologia Internationalis, 2021)
Background: Obesity is frequently present in patients suffering from end-stage renal disease (ESRD). However, overweight kidney transplant candidates are a challenge for the transplant surgeon. Obese patients tend to develop a large abdominal panniculus after weight loss creating an area predisposed to wound-healing disorders. Due to concerns about graft survival and postoperative complications after kidney transplantation, obese patients are often refused in this selective patient cohort. The study aimed to analyze the effect of panniculectomies on postoperative complications and transplant candidacy in an interdisciplinary setting. Methods: A retrospective database review of 10 cases of abdominal panniculectomies performed in patients with ESRD prior to kidney transplantation was conducted. Results: The median body mass index was 35.2 kg/m(2) (range 28.5-53.0 kg/m(2)) at first transplant-assessment versus 31.0 kg/m(2) (range 28.0-34.4 kg/m(2)) at panniculectomy, and 31.6 kg/m(2) (range 30.3-32.4 kg/m(2)) at kidney transplantation. We observed no major postoperative complications following panniculectomy and minor wound-healing complications in 2 patients. All aside from 1 patient became active transplant candidates 6 weeks after panniculectomy. No posttransplant wound complications occurred in the transplanted patients. Conclusion: Abdominal panniculectomy is feasible in patients suffering ESRD with no major postoperative complications, thus converting previously ineligible patients into kidney transplant candidates. An interdisciplinary approach is advisable in this selective patient cohort.
CRIS-Team WoS Importer:2021-07-02

A deep-learning workflow to predict upper tract urothelial carcinoma protein-based subtypes from H&E slides supporting the prioritization of patients for molecular testing - Angeloni, Miriam; van Doeveren, Thomas; Lindner, Sophia; Volland, Patrick; Schmelmer, Jorina; Foersch, Sebastian; Matek, Christian; Stöhr, Robert; Geppert, Carol-Immanuel; Heers, Hendrik; Wach, Sven; Taubert, Helge; et al. (Journal of Pathology: Clinical Research, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare and aggressive, yet understudied, urothelial carcinoma (UC). The more frequent UC of the bladder comprises several molecular subtypes, associated with different targeted therapies and overlapping with protein-based subtypes. However, if and how these findings extend to UTUC remains unclear. Artificial intelligence-based approaches could help elucidate UTUC's biology and extend access to targeted treatments to a wider patient audience. Here, UTUC protein-based subtypes were identified, and a deep-learning (DL) workflow was developed to predict them directly from routine histopathological H&E slides. Protein-based subtypes in a retrospective cohort of 163 invasive tumors were assigned by hierarchical clustering of the immunohistochemical expression of three luminal (FOXA1, GATA3, and CK20) and three basal (CD44, CK5, and CK14) markers. Cluster analysis identified distinctive luminal (N = 80) and basal (N = 42) subtypes. The luminal subtype mostly included pushing, papillary tumors, whereas the basal subtype diffusely infiltrating, non-papillary tumors. DL model building relied on a transfer-learning approach by fine-tuning a pre-trained ResNet50. Classification performance was measured via three-fold repeated cross-validation. A mean area under the receiver operating characteristic curve of 0.83 (95% CI: 0.67–0.99), 0.8 (95% CI: 0.62–0.99), and 0.81 (95% CI: 0.65–0.96) was reached in the three repetitions. High-confidence DL-based predicted subtypes showed significant associations (p < 0.001) with morphological features, i.e. tumor type, histological subtypes, and infiltration type. Furthermore, a significant association was found with programmed cell death ligand 1 (PD-L1) combined positive score (p < 0.001) and FGFR3 mutational status (p = 0.002), with high-confidence basal predictions containing a higher proportion of PD-L1 positive samples and high-confidence luminal predictions a higher proportion of FGFR3-mutated samples. Testing of the DL model on an independent cohort highlighted the importance to accommodate histological subtypes. Taken together, our DL workflow can predict protein-based UTUC subtypes, associated with the presence of targetable alterations, directly from H&E slides.
CRIS-Team Scopus Importer:2024-03-29
Keywords: deep-learning; digital pathology; immunohistochemistry; protein-based subtypes; targeted therapy; upper tract urothelial carcinoma; whole slide images

A Hybrid Type III Effectiveness-Implementation Trial to Optimize Medication Safety With Oral Antitumor Therapy in Real-World: The AMBORA Competence and Consultation Center. - Cuba, Lisa; Dürr, Pauline; Geßner, Katja; Häcker, Babette; Fietkau, Rainer; Siebler, Jürgen; Pavel, Marianne Ellen; Neurath, Markus; Berking, Carola; Wullich, Bernd; Brückl, Valeska; Beckmann, Matthias; et al. (JCO Oncology Practice, 2024)
PURPOSE: Implementation science endeavors to facilitate the translation of evidence-based research into clinical routine. The clinical pharmacological/pharmaceutical care program evaluated in the randomized AMBORA trial on medication safety with oral antitumor therapeutics (OAT) optimizes care delivery and provides significant benefits for patients, treatment teams, and health care systems. Thus, we aimed to investigate the implementation of this care program within the AMBORA Competence and Consultation Center (AMBORA Center). METHODS: The AMBORA Center within a University Comprehensive Cancer Center offered several services (eg, patient consultations) and was evaluated according to the RE-AIM framework. This multicenter hybrid type III trial focused on implementation outcomes (eg, patient recruitment, referring units, evaluation of services) while concurrently investigating effectiveness (eg, side effects, medication errors). Quantitative and qualitative assessments were combined. RESULTS: The AMBORA Center conducted over 800 consultations with 420 patients in seven institutions. The primary end point of counseling 70% of patients treated with OAT was not reached. Patients were referred by 15 treatment units compared with 11 units in the AMBORA trial. On the basis of heterogeneous referral rates and characteristics across the institutions, barriers and facilitators of the implementation process were derived. Several survey results (eg, stakeholder interviews, online/paper-based questionnaires) reflected a high appreciation of services by patients and health care professionals. The severity of 60.1% (178 of 296) of detected side effects improved, and 86.3% (297 of 344) of medication errors were resolved. CONCLUSION: Despite not reaching the primary implementation outcome, the AMBORA Center included more treatment units and demonstrated patient benefit of the AMBORA care program by meeting all effectiveness outcomes. We outlined quantitative and qualitative implementation characteristics to enhance outreach and foster further dissemination of centers to optimize medication safety with OAT.
EVALuna2:569426

AI allows pre-screening of FGFR3 mutational status using routine histology slides of muscle-invasive bladder cancer. - Bannier, Pierre Antoine; Saillard, Charlie; Mann, Philipp; Touzot, Maxime; Maussion, Charles; Matek, Christian; Klümper, Niklas; Breyer, Johannes; Wirtz, Ralph; Sikic, Danijel; Schmitz-Dräger, Bernd; Wullich, Bernd; et al. (Nature Communications, 2024)
Pathogenic activating mutations in the fibroblast growth factor receptor 3 (FGFR3) drive disease maintenance and progression in urothelial cancer. 10-15% of muscle-invasive and metastatic urothelial cancer (MIBC/mUC) are FGFR3-mutant. Selective targeting of FGFR3 hotspot mutations with tyrosine kinase inhibitors (e.g., erdafitinib) is approved for mUC and requires FGFR3 mutational testing. However, current testing assays (polymerase chain reaction or next-generation sequencing) necessitate high tissue quality, have long turnover time, and are expensive. To overcome these limitations, we develop a deep-learning model that detects FGFR3 mutations using routine hematoxylin-eosin slides. Encompassing 1222 cases, our study is a large-scale validation of a model prescreening FGFR3 mutations for MIBC and mUC patients. In this work, we demonstrate that our model achieves high sensitivity (>93%) on advanced and metastatic cases while reducing molecular testing by 40% on average, thereby offering a cost-effective and rapid pre-screening tool for identifying patients eligible for FGFR3 targeted therapies.
EVALuna2:578143

A multicenter comparison of PD-L1 protein and mRNA expression in urothelial bladder cancer by immunohistochemistry and RT-qPCR (Checkpoint-Typer(C)): A round robin test by the BRIDGE-Consortium Germany - Eckstein, Markus; Wirtz, R.; Pfannstil, C.; Wach, S.; Stoehr, R.; Breyer, J.; Erlmeier, F.; Guenes, C.; Nitschke, K.; Weichert, W.; Otto, W.; Keck, Bastian; et al. (2018)
EVALuna2:34065

A multicenter round robin test of PD-L1 expression assessment in urothelial bladder cancer by immunohistochemistry and RT-qPCR with emphasis on prognosis prediction after radical cystectomy - Eckstein, Markus; Wirtz, Ralph M.; Pfannstil, Carolin; Wach, Sven; Stoehr, Robert; Breyer, Johannes; Erlmeier, Franziska; Günes, Cagatay; Nitschke, Katja; Weichert, Wilko; Otto, Wolfgang; Keck, Bastian; et al. (Oncotarget, 2018)
Background: Immunohistochemical PD-L1 assessment is currently used to identify responders towards checkpoint inhibitors although it is limited by inter-observer effects. Here, we conducted a multi-center round robin test to prove the possibility of assessing the PD-L1 status by gene expression to avoid inter-observer effects. Patients and methods: Gene expression of PD-L1 was analyzed in a total of 294 samples (14 cases non-muscle invasive and muscle-invasive bladder cancer; MIBC) in seven centers by a RT-qPCR kit and compared with immunohistochemical scoring of three pathologists (DAKO, 22c3). Both assays were compared towards prognosis prediction in a cohort of 88 patients with MIBC. Results: PD-L1 gene expression revealed very high inter center correlation (centrally extracted RNA: r = 0.68-0.98, p ≤ 0.0076; locally extracted RNA: r = 0.81-0.98, p ≤ 0.0014). IHC Inter-observer concordance was moderate to substantial for immune cells (IC), fair for combined IC/ tumor cell (TC) (IC: κ = 0.50-0.61; IC + TC: κ = 0.50), and fair for TC scoring (κ = 0.26-0.35). Gene expression assessment resulted in more positive cases (9/14 cases positive vs. 6/14 cases [IHC]) which could be validated in the independent cohort. Positive mRNA status was associated with significantly better overall and disease-specific survival (5-year OS: 50% vs. 26%, p = 0.0042, HR = 0.48; 5 year DSS: 65% vs. 40%, p = 0.012, HR = 0.49). The 1% IHC IC cut-off also revealed significant better OS (5 year OS: 58% vs. 31%, p = 0.036, HR = 0.62). Conclusion: Gene expression showed very high inter-center agreement. Gene expression assessment also resulted in more positive cases and revealed better prognosis prediction. PD-L1 mRNA expression seems to be a reproducible and robust tool for PD-L1 assessment.
EVALuna2:34268

Analysis and classification of oncology activities on the way to workflow based single source documentation in clinical information systems - Wagner, Stefan; Beckmann, Matthias; Wullich, Bernd; Seggewies, Christof; Ries, Markus; Buerkle, Thomas; Prokosch, Hans-Ulrich (BMC Medical Informatics and Decision Making, 2015)
Today, cancer documentation is still a tedious task involving many different information systems even within a single institution and it is rarely supported by appropriate documentation workflows.In a comprehensive 14 step analysis we compiled diagnostic and therapeutic pathways for 13 cancer entities using a mixed approach of document analysis, workflow analysis, expert interviews, workflow modelling and feedback loops. These pathways were stepwise classified and categorized to create a final set of grouped pathways and workflows including electronic documentation forms.A total of 73 workflows for the 13 entities based on 82 paper documentation forms additionally to computer based documentation systems were compiled in a 724 page document comprising 130 figures, 94 tables and 23 tumour classifications as well as 12 follow-up tables. Stepwise classification made it possible to derive grouped diagnostic and therapeutic pathways for the three major classes - solid entities with surgical therapy - solid entities with surgical and additional therapeutic activities and - non-solid entities. For these classes it was possible to deduct common documentation workflows to support workflow-guided single-source documentation.Clinical documentation activities within a Comprehensive Cancer Center can likely be realized in a set of three documentation workflows with conditional branching in a modern workflow supporting clinical information system.
EVALuna2:145

Analysis of CXCL9, PD1 and PD-L1 mRNA in stage T1 non-muscle invasive bladder cancer and their association with prognosis - Kubon, Jennifer; Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Stöhr, Robert; Neumann, Angela; Keck, Bastian; Wullich, Bernd; Hartmann, Arndt; Wirtz, Ralph M.; Taubert, Helge; Wach, Sven (Cancers, 2020)
Non-muscle invasive bladder cancer (NMIBC), which is characterized by a recurrence rate of approximately 30% and very long treatment times, remains a major unresolved problem for patients and the health care system. The immunological interplay between tumor cells and the immune environment is important for tumor development. Therefore, we analyzed the mRNA of three immune markers, CXCL9, PD1 and PD-L1, in NMIBC by qRT-PCR. The results were subsequently correlated with clinicopathological parameters and prognostic data. Altogether, as expected, higher age was an independent prognostic factor for overall survival (OS) and disease-specific survival (DSS), but not for recurrence-free survival (RFS). Lower CXCL9 mRNA was observed in multivariate Cox’s regression analysis to be an independent prognostic parameter for reduced OS (relative risk; RR = 2.08; p = 0.049), DSS (RR = 4.49; p = 0.006) and RFS (RR = 2.69; p = 0.005). In addition, PD-L1 mRNA was an independent prognostic factor for DSS (RR = 5.02; p = 0.042) and RFS (RR = 2.07; p = 0.044). Moreover, in univariate Cox’s regression analysis, the stratification of patients revealed that low CXCL9 or low PD1 mRNA was associated with reduced RFS in the younger patient group (≤71 years), but not in the older patient group (>71 years). In addition, low CXCL9 or low PD-L1 was associated with shorter RFS in patients with higher tumor cell proliferation and in patients without instillation therapy. In conclusion, the characterization of mRNA levels of immune markers differentiates NIMBC patients with respect to prognosis.
CRIS-Team Scopus Importer:2020-10-09
Keywords: CXCL9; PD-L1; PD1; Prognosis; Stage T1 NMIBC

Analysis of the Impact of Clinical Factors on Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction - Oginski, Natalie; Apel, Hendrik; Richterstetter, Mario; Lieb, Verena; Fiebig, Christian; Goebell, Peter; Wullich, Bernd; Sikic, Danijel (Urologia Internationalis, 2022)
Introduction: Predictive factors for the treatment success of low-intensity extracorporeal shockwave therapy (Li-ESWT) for erectile dysfunction (ED) are still under debate. Methods: Li-ESWT was performed in 50 patients suffering from ED by applying 3,000 shock waves once a week over a period of 6 weeks. Treatment success was defined as an increase in the International Index of Erectile Function 5 (IIEF-5) score by >= 5 points or an Erectile Hardness Score (EHS) of >= 3 points. IIEF-5 and EHS were measured at baseline and at 3 and 6 months of follow-up. Results: Treatment success according to either the IIEF-5 score or EHS at any time of follow-up was achieved in 28 patients (56%). Twenty-five patients (50%) experienced an improvement during the first 3 months, which lasted for 6 months in 8 cases (16%). Three patients reported improved erectile function only after 6 months. When stratifying the cohort with regard to potential influencing factors, a significantly improved IIEF-5 score could be achieved in men with cardiovascular risk factors (p = 0.026) and in men with antihypertensive medication (p = 0.009). Men without cardiovascular risk factors showed no therapeutic benefit from Li-ESWT. Discussion/Conclusion: Li-ESWT is a valid but often short-lived treatment option for ED, especially in men with cardiovascular risk factors or controlled hypertension. Future studies should assess the feasibility and safety of repeated applications of Li-ESWT.
CRIS-Team WoS Importer:2022-03-04

Analytical and inter-observer comparability of 4 clinically developed programmed death-ligand 1 (PD-L1) immunohistochemistry assays in advanced clear cell renal cell carcinoma (CCRCC) - Sommer, Ulrich; Eckstein, Markus; Ammann, Johannes; Braunschweig, Till; Macher-Goeppinger, Stephan; Schwamborn, Kristina; Hieke-Schulz, Stefanie; Wullich, Bernd; Wirth, Manfred; Roth, Wilfried; Knuechel, Ruth; Weichert, Wilko; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

An easily expandable multi-drug LC-MS assay for the simultaneous quantification of 57 oral antitumor drugs in human plasma - Kehl, Niklas; Schlichtig, Katja; Dürr, Pauline; Bellut, Laura; Dörje, Frank; Fietkau, Rainer; Pavel, Marianne Ellen; Mackensen, Andreas; Wullich, Bernd; Maas, Renke; Fromm, Martin; Geßner, Arne; et al. (Cancers, 2021)
Oral anticancer drugs have led to significant improvements in the treatment of multiple tumor entities. However, in patients undergoing oral antitumor therapy, plasma concentrations are highly variable, resulting in risks of reduced therapeutic effects or an increase in side effects. One important tool to reduce this variability is therapeutic drug monitoring. In this work we describe a method to simultaneously quantify the plasma concentrations of 57 oral antitumor agents. Quantification of these drugs was achieved using liquid chromatography coupled to an Orbitrap mass spectrometer. The method was fully validated according to the FDA guidelines and constitutes a simple and robust way for exposure monitoring of a wide variety of oral anticancer drugs. Applicability to clinical routine was demonstrated by the analysis of 71 plasma samples taken from 39 patients. In summary, this new multi-drug method allows simultaneous quantification of 57 oral antitumor drugs, which can be applied to exposure monitoring in clinical studies, taking into account the broad variety of oral antitumor drugs prescribed in clinical routine.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Exposure measurement; Kinase inhibitors; Liquid chromatography mass spectrometry; Oral antitumor drug; Orbitrap mass spectrometer

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

Annual meeting of the German Prostate Cancer Consortium: Updates to circulating tumor cells, "liquid biopsy" and the role of the androgen receptor - Taubert, Helge; Becker, Christoph; Fuessel, Susanne; Seitz, Gerhard; Thelen, Paul; Wullich, Bernd (Urologe, 2016)
EVALuna2:16346

Assessment of a fully-automated diagnostic AI software in prostate MRI: Clinical evaluation and histopathological correlation - Bayerl, Nadine; Adams, Lisa C.; Cavallaro, Alexander Josef; Bäuerle, Tobias; Schlicht, Michael; Wullich, Bernd; Hartmann, Arndt; Uder, Michael; Ellmann, Stephan (European Journal of Radiology, 2024)
Objective: This study aims to evaluate the diagnostic performance of a commercial, fully-automated, artificial intelligence (AI) driven software tool in identifying and grading prostate lesions in prostate MRI, using histopathological findings as the reference standard, while contextualizing its performance within the framework of PI-RADS v2.1 criteria. Material and methods: This retrospective study analyzed 123 patients who underwent multiparametric prostate MRI followed by systematic and targeted biopsies. MRI protocols adhered to international guidelines and included T2-weighted, diffusion-weighted, T1-weighted, and dynamic contrast-enhanced imaging. The AI software tool mdprostate was integrated into the Picture Archiving and Communication System to automatically segment the prostate, calculate prostate volume, and classify lesions according to PI-RADS scores using biparametric T2-weighted and diffusion-weighted imaging. Histopathological analysis of biopsy cores served as the reference standard. Diagnostic performance metrics including sensitivity, specificity, positive and negative predictive value (PPV, NPV), and area under the ROC curve (AUC) were calculated. Results: mdprostate demonstrated 100 % sensitivity at a PI-RADS ≥ 2 cutoff, effectively ruling out both clinically significant and non-significant prostate cancers for lesions remaining below this threshold. For detecting clinically significant prostate cancer (csPCa) using a PI-RADS ≥ 4 cutoff, mdprostate achieved a sensitivity of 85.5 % and a specificity of 63.2 %. The AUC for detecting cancers of any grade was 0.803. The performance metrics of mdprostate were comparable to those reported in two meta-analyses of PI-RADS v2.1, with no significant differences in sensitivity and specificity (p > 0.05). Conclusion: The evaluated AI tool demonstrated high diagnostic performance in identifying and grading prostate lesions, with results comparable to those reported in meta-analyses of expert readers using PI-RADS v2.1. Its ability to standardize evaluations and potentially reduce variability underscores its potential as a valuable adjunct in the prostate cancer diagnostic pathway. The high accuracy of mdprostate, particularly in ruling out prostate cancers, highlights its clinical utility by reducing workload and enhancing patient outcomes.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Artificial intelligence; Clinical evaluation; Diagnostic performance; PI-RADS; Prostate cancer; Prostate MRI

Assessment of Treatment Response by 99mTc-MIP-1404 SPECT/CT: A Pilot Study in Patients With Metastatic Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (Clinical Nuclear Medicine, 2018)
BACKGROUND: We investigated the role of Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) SPECT/CT of PSMA expression in the assessment of treatment response in patients with metastatic prostate cancer. METHODS: We retrospectively analyzed Tc-MIP-1404 SPECT/CT scans from 28 patients with metastatic prostate cancer examined before initiation and after completion of therapy. Eight of these patients had been treated with androgen deprivation therapy, 10 with docetaxel, and another 10 with external beam radiotherapy. On the CT images from SPECT/CT, treatment response was assessed according to RECIST 1.1 criteria; independently from that analysis, maximal standardized uptake values (SUVmax) were quantified in representative tumor lesions and treatment response assumed at differences in SUVmax greater than 30%. Radiographic response assessment was correlated to biochemical response (BR) based on prostate-specific antigen serum levels. RESULTS: The concordance rate between SPECT and BR was 75% (95% confidence interval [CI], 0.55-0.89) (Cohen κ = 0.57; 95% CI, 0.29-0.85; P ≤ 0.01), higher than for that between SPECT and CT with 57% (95% CI, 0.37-0.76) (κ = 0.40; 95% CI, 0.14-0.65; P ≤ 0.01), as well as that between CT and BR with 50% (95% CI, 0.31-0.69) (κ = 0.31; 95% CI, 0.06-0.57, P ≤ 0.05). Discordant findings between SPECT and CT were most likely due to limitations of CT in assessing metastases in lymph nodes, as well as bone involvement, which was sometimes not detectable on CT scans. CONCLUSIONS: The high agreement between treatment response, as assessed by Tc-MIP-1404 SPECT/CT and BR, suggests a possible role of that imaging tool for monitoring treatment in metastatic prostate cancer. Larger, ideally prospective trials are needed to help to reveal the full potential of SPECT imaging of PSMA expression in that regard.
EVALuna2:34693

Association of tissue mRNA and serum antigen levels of members of the urokinase-type plasminogen activator system with clinical and prognostic parameters in prostate cancer - Al-Janabi, Omar; Taubert, Helge; Lohse-Fischer, Andrea; Froehner, Michael; Wach, Sven; Stoehr, Robert; Keck, Bastian; Burger, Max; Wieland, Wolf; Erdmann, Kati; Wirth, Manfred P.; Wullich, Bernd; et al. (BioMed Research International, 2014)
The objective was to determine the mRNA expression and protein levels of uPA system components in tissue specimens and serum samples, respectively, from prostate cancer (PCa) patients and to assess their association with clinicopathological parameters and overall survival (OS). The mRNA expression levels of uPA, its receptor (uPAR), and its inhibitor type 1 (PAI-1) were analyzed in corresponding malignant and adjacent nonmalignant tissue specimens from 132 PCa patients by quantitative PCR. Preoperative serum samples from 81 PCa patients were analyzed for antigen levels of uPA system members by ELISA. RNA levels of uPA system components displayed significant correlations with each other in the tumor tissues. A significantly decreased uPA mRNA expression in PCa compared to the corresponding nonmalignant tissue was detected. High uPA mRNA level was significantly associated with a high Gleason score. Elevated concentration of soluble uPAR (suPAR) in serum was significantly associated with a poor OS of PCa patients (P = 0.022). PCa patients with high suPAR levels have a significantly higher risk of death (multivariate Cox's regression analysis; HR = 7.12, P = 0.027). The association of high suPAR levels with poor survival of PCa patients suggests a prognostic impact of suPAR levels in serum of cancer patients.
EVALuna2:6625

Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

Biobanks, translational research and medical informatics - Schüttler, Christina; Jahns, R.; Prokosch, Hans-Ulrich; Wach, Sven; Wullich, Bernd (Die Urologie, 2022)
When we think of medical research, one intuitively associates it with the analysis of study data collected for a specific research question or with the secondary use of patient data from routine care. However, these are not the only sources for answering scientific questions. Especially for translational research, tissue and liquid samples such as blood, DNA or other body fluids provide essential insights into disease pathogenesis, development of new therapies and treatment decisions. Access to these biomedical materials is provided by so-called biobanks. By collecting, characterizing, documenting and, if necessary, processing human biospecimens in accordance with high quality standards, they can support research of the causes of diseases, early diagnosis and the targeted treatment of diseases, or make a significant contribution to the investigation of common diseases.
CRIS-Team WoS Importer:2022-09-16

Bladder tumor subtype commitment occurs in carcinoma in-situ driven by key signaling pathways including ECM remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, J.; Burger, M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09

Blunt renal trauma-induced hypertension in pediatric patients: a single-center experience - Marcou, Marios; Galiano, Matthias; Jüngert, Jörg M.; Rompel, Oliver; Kuwert, Torsten; Wullich, Bernd; Hirsch-Koch, Karin (Journal of Pediatric Urology, 2021)
Purpose: Children have a greater chance of sustaining a renal injury than adults and higher odds of having a high-grade renal injury. Hypertension is a rare complication of blunt renal trauma, with risk being higher in cases of major renal trauma. We reviewed the cases of pediatric blunt renal trauma-induced hypertension in our tertiary referral center in an attempt to better understand this rare condition. Study design: A retrospective evaluation of children under the age of 18 who were admitted to our department during the last 20 years and were diagnosed with blunt renal trauma. Results: Twenty-three children presented with blunt renal trauma, one of whom was treated with emergency nephrectomy. Four children (18%) developed post-traumatic hypertension. All four cases were associated with a reduction in blood flow to the kidney, either through injury to the renal artery (in three cases) or through extrinsic compression of the kidney by a large perirenal hematoma (Page kidney; in one case). The Page kidney case developed hypertension during the initial hospitalization, and it resolved spontaneously after five months through the gradual resorption of the perirenal hematoma. Among the three cases of renal artery injury, hypertension during the initial hospitalization was only observed in one case, with hypertension in the other two cases manifesting after two months and four years, respectively. All three cases of renal artery injury resulted in a complete loss of function of the injured kidney, and two cases were treated with nephrectomy. Following nephrectomy, the blood pressure level returned to normal within a few days. Discussion: Development of hypertension following a blunt renal trauma can be heterogenous, with the time of manifestation stretching between days after the accident and years thereafter. Children have a higher risk of renal trauma and, according to published data out of the National Trauma Data Bank, a 20-times higher risk of renal artery injury in comparison to the adult population. Large multicenter studies are required to answer the question of whether children are therefore more prone to blunt renal trauma-induced hypertension than adults. Conclusions: Our study highlights the importance of blood pressure monitoring in children following blunt renal trauma, as post-traumatic hypertension can develop even years after the accident. In cases of a poorly functioning kidney, nephrectomy may be regarded as a curative therapy.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Accidents; Blood pressure; Child; Renal artery; Renovascular hypertension

CCL2 expression in tumor cells and tumor-infiltrating immune cells shows divergent prognostic potential for bladder cancer patients depending on lymph node stage - Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; et al. (Cancers, 2020)
Bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, markers for tumor cells and immune cells that are associated with prognosis are still needed. The chemokine CC motif ligand 2 (CCL2) could be such a marker. We analyzed the expression of CCL2 by immunohistochemistry (IHC) in 168 muscle invasive BCa samples using a tissue microarray. Application of a single cut-off for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; ≤6% of ICs vs. >6% of ICs) revealed 57 cases (33.9%) and 70 cases (41.7%) with CCL2-positive TCs or ICs, respectively. IHC results were correlated with clinicopathological and survival data. Positive CCL2 staining in TCs was associated with shorter overall survival (OS), disease-specific survival (DSS), and relapse-free survival (RFS) (p = 0.004, p = 0.036, and p = 0.047; log rank test) and appeared to be an independent prognostic factor for OS (RR = 1.70; p = 0.007; multivariate Cox’s regression analysis). In contrast, positive CCL2 staining in the ICs was associated with longer OS, DSS, and RFS (p = 0.032, p = 0.001, and p = 0.001; log rank test) and appeared to be an independent prognostic factor for DSS (RR = 1.77; p = 0.031; multivariate Cox’s regression analysis). Most interestingly, after separating the patients according to their lymph node status (N0 vs. N1+2), CCL2 staining in the ICs was differentially associated with prognosis. In the N0 group, CCL2 positivity in the ICs was a positive independent prognostic factor for OS (RR = 1.99; p = 0.014), DSS (RR = 3.17; p = 0.002), and RFS (RR = 3.10; p = 0.002), whereas in the N1+2 group, CCL2 positivity was a negative independent factor for OS (RR = 3.44; p = 0.019)) and RFS (RR = 4.47; p = 0.010; all multivariate Cox’s regression analyses). In summary, CCL2 positivity in TCs is a negative prognostic factor for OS, and CCL2 can mark ICs that are differentially associated with prognosis depending on the nodal stage of BCa patients. Therefore, CCL2 staining of TCs and ICs is suggested as a prognostic biomarker for BCa patients.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bladder cancer; CCL2; Immune cells; Lymph node stage; Prognosis; Tumor cells

Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Characterization of PD-1 and PD-L1 Expression in Papillary Renal Cell Carcinoma: Results of a Large Multicenter Study - Erlmeier, Franziska; Steffens, Sandra; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Clinical Genitourinary Cancer, 2020)
Background: Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) play a decisive role as prognostic markers in clear-cell renal cell carcinoma (RCC). To date, the role of PD-1/PD-L1 as a prognostic marker in papillary RCC (pRCC) remains scarce. Patients and Methods: Patients’ sample collection was a joint collaboration of the nationwide PANZAR consortium – a multicenter study. Medical history and tumor specimens were collected from 245 and 129 patients with pRCC types 1 and 2, respectively. Expression of PD-1 and PD-L1 was determined by immunohistochemistry in pRCC and tumor-infiltrating mononuclear cells. Results: Of 374 pRCC specimens, 204 type 1 and 97 type 2 were evaluable for PD-1 and PD-L1 expression analysis. In total, PD-1 and PD-L1 expression were found in 8 (4.9%) of 162 and 12 (7.2%) of 166 evaluable pRCC type 1 specimens. Comparably, PD-1 and PD-L1 expression were found in 2 (2.4%) of 83 and 5 (6.2%) of 81 evaluable pRCC type 2 specimens. Hardly any clinically relevant associations between PD-1 and PD-L1 positivity and clinicopathologic or clinical courses were observed, neither in pRCC type 1 nor type 2. Conclusion: The analysis of a large pRCC cohort from a multicenter consortium revealed no impact of PD-1/PD-L1 expression on prognosis in patients with pRCC with predominantly limited disease status, neither for type 1 nor type 2. However, the impact of PD-1 and PD-L1 in more advanced pRCC disease needs further elucidation. Understanding the impact of programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) expression becomes increasingly important in renal cell carcinoma (RCC) owing to increasing therapeutic implications. However, little is known in non–clear-cell RCC about the relevance of those immune checkpoint surrogates. Here, we suggest that PD-1/PD-L1 expression in papillary RCC does not have prognostic impact, neither for type 1 nor type 2. However, in advanced disease, further evaluation according to PD-1/PD-L1 is warranted.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Non-clear-cell-renal carcinoma; Papillary renal cell; PD-1; PD-L1; Renal cell carcinoma

Characterization of the expression and immunological impact of the transcriptional activator CREB in renal cell carcinoma - Friedrich, Michael; Stoehr, Christine; Jasinski-Bergner, Simon; Hartmann, Arndt; Wach, Sven; Wullich, Bernd; Steven, André; Seliger, Barbara (Journal of Translational Medicine, 2020)
Background: The non-classical human leukocyte antigen (HLA)-G is a strong immunomodulatory molecule. Under physiological conditions, HLA-G induces immunological tolerance in immune privileged tissues, while under pathophysiological situations it contributes to immune escape mechanisms. Therefore, HLA-G could act as a potential immune checkpoint for future anti-cancer immunotherapies. Recent data suggest an aberrant expression of the cAMP response element binding protein (CREB) in clear cell renal cell carcinoma (ccRCC), which is correlated with tumor grade and stage. Furthermore, preliminary reports demonstrated a connection of CREB as a control variable of HLA-G transcription due to CREB binding sites in the HLA-G promoter region. This study investigates the interaction between CREB and HLA-G in different renal cell carcinoma (RCC) subtypes and its correlation to clinical parameters. Methods: The direct interaction of CREB with the HLA-G promoter was investigated by chromatin immunoprecipitation in RCC cell systems. Furthermore, the expression of CREB and HLA-G was determined by immunohistochemistry using a tissue microarray (TMA) consisting of 453 RCC samples of distinct subtypes. Staining results were assessed for correlations to clinical parameters as well as to the composition of the immune cell infiltrate. Results: There exists a distinct expression pattern of HLA-G and CREB in the three main RCC subtypes. HLA-G and CREB expression were the lowest in chromophobe RCC lesions. However, the clinical relevance of CREB and HLA-G expression differed. Unlike HLA-G, high levels of CREB expression were positively associated to the overall survival of RCC patients. A slightly, but significantly elevated number of tumor infiltrating regulatory T cells was observed in tumors of high CREB expression. Whether this small increase is of clinical relevance has to be further investigated. Conclusions: An interaction of CREB with the HLA-G promoter could be validated in RCC cell lines. Thus, for the first time the expression of CREB and its interaction with the HLA-G in human RCCs has been shown, which might be of clinical relevance.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CREB; HLA-G; Immune cell infiltration; Renal cell carcinoma

Clean Intermittent Catheterization in Children under 12 Years Does Not Have a Negative Impact on Long-Term Graft Survival following Pediatric Kidney Transplantation - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2024)
Background: Congenital anomalies of the kidneys and urinary tract (CAKUTs) are one of the most prevalent primary causes of end-stage renal disease (ESRD) in young children, and approximately one-third of these children present with lower urinary tract dysfunction (LUTD). Many children with LUTD require therapy with clean intermittent catheterization (CIC). CIC commonly leads to bacteriuria, and considerations have arisen regarding whether CIC in immunosuppressed children is safe or whether repeated febrile urinary tract infections (UTIs) may lead to the deterioration of kidney graft function. Material and Methods: We retrospectively reviewed all cases of primary kidney transplantation performed in our center between 2001 and 2020 in recipients aged less than twelve years. The number of episodes of febrile UTIs as well as the long-term kidney graft survival of children undergoing CIC were compared to those of children with urological causes of ESRD not undergoing CIC, as well as to those of children with nonurological causes of ESRD. Results: Following successful kidney transplantation in 41 children, CIC was needed in 8 of these patients. These 8 children undergoing CIC had significantly more episodes of febrile UTIs than did the 18 children with a nonurological cause of ESRD (p = 0.04) but not the 15 children with a urological cause of ESRD who did not need to undergo CIC (p = 0.19). Despite being associated with a higher rate of febrile UTIs, CIC was not identified as a risk factor for long-term kidney graft survival, and long-term graft survival did not significantly differ between the three groups at a median follow-up of 124 months. Conclusions: Our study demonstrates that, under regular medical care, CIC following pediatric transplantation is safe and is not associated with a higher rate of long-term graft loss.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CAKUT; catheterization; child; kidney transplantation; LUTD

Clinical and laboratory visit programme for residents in urology - Schneidewind, L.; Borowitz, R.; Wullich, Bernd; Borgmann, H. (Urologe, 2014)
EVALuna2:16324

Clinical outcome of patients with lymph node-positive prostate cancer following radical prostatectomy and extended sentinel lymph node dissection - Muck, Alexander; Langesberg, Christian; Mugler, Michael; Rahnenfuehrer, Joerg; Wullich, Bernd; Schafhauser, Wolfgang (Urologia Internationalis, 2015)
This study sought to evaluate the clinical outcome after extended sentinel lymph node dissection (eSLND) and radical retropubic prostatectomy (RRP) in patients with clinically localized prostate cancer (PCa).From August 2002 until February 2011, a total of 819 patients with clinically localized PCa, confirmed by biopsy, were treated with RRP plus eSLND. Biochemical recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS) were assessed with Kaplan-Meier curves. Various histopathological parameters were analyzed by univariate and multivariate analysis.The mean follow-up was 5.3 years. Lymph node (LN) metastases occurred in 140 patients. We removed an average of 10.9 LNs via eSLND from patients with pN1 PCa. Postoperatively, 121 pN1 patients temporarily received adjuvant androgen deprivation therapy. The mean survival periods for RFS, RFS after secondary treatment, CSS, and OS were 4.7, 7.0, 8.8, and 8.1 years, respectively. The cancer-specific death rate of the 140 pN1 patients was 13.6%. RFS, CSS, and OS were significantly correlated with pathological margin status, LN density, the total diameter of evident metastases, and membership in the subgroup 'micrometastases only'.Despite the presence of LN metastases, patients with a low nodal tumor burden demonstrate a remarkable clinical outcome after undergoing eSLND and RRP, thus suggesting a potential curative therapeutic approach.
EVALuna2:16322

Clinical relevance of miR-mediated HLA-G regulation and the associated immune cell infiltration in renal cell carcinoma - Jasinski-Bergner, Simon; Stoehr, Christine; Bukur, Juergen; Massa, Chiara; Braun, Juliane; Huettelmaier, Stefan; Spath, Verena; Wartenberg, Roland; Legal, Wolfgang; Taubert, Helge; Wach, Sven; Wullich, Bernd; et al. (OncoImmunology, 2015)
In human tumors of distinct origin including renal cell carcinoma (RCC), the non-classical human leukocyte antigen G (HLA-G) is frequently expressed, thereby inhibiting the cytotoxic activity of T and natural killer (NK) cells. Recent studies demonstrated a strong post-transcriptional gene regulation of the HLA-G by miR-152, -148A, -148B and -133A. Standard methods were applied to characterize the expression and function of HLA-G, HLA-G-regulatory microRNAs (miRs) and the immune cell infiltration in 453 RCC lesions using a tissue microarray and five RCC cell lines linking these results to clinical parameters. Direct interactions with HLA-G regulatory miRs and the HLA-G 3' untranslated region (UTR) were detected and the affinities of these different miRs to the HLA-G 3'-UTR compared. qPCR analyses and immunohistochemical staining revealed an inverse expression of miR-148A and -133A with the HLA-G protein in situ and in vitro. Stable miR overexpression caused a downregulation of HLA-G protein enhancing the NK and LAK cell-mediated cytotoxicity in in vitro CD107a activation assays revealing a HLA-G-dependent cytotoxic activity of immune effector cells. A significant higher frequency of CD3(+)/CD8(+) T cell lymphocytes, but no differences in the activation markers CD69, CD25 or in the presence of CD56(+), FoxP3(+) and CD4(+) immune cells were detected in HLA-G(+) compared to HLA-G(-) RCC lesions. This could be associated with higher WHO grade, but not with a disease-specific survival. These data suggest a miR-mediated control of HLA-G expression in RCC, which is associated with a distinct pattern of immune cell infiltration.
EVALuna2:6743

cMET: a prognostic marker in papillary renal cell carcinoma? - Erlmeier, Franziska; Bruecher, Benedict; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Human Pathology, 2022)
The tyrosine-protein kinase c-Met plays a decisive role in numerous cellular processes, as a proto-oncogene that supports aggressive tumor behavior. It is still unknown whether c-Met could be relevant for prognosis of papillary RCC (pRCC). Specimen collection was a collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from 197 and 110 patients with type 1 and 2 pRCC, respectively. Expression of cMET was determined by immunohistochemistry. In total, cMET staining was evaluable in of 97 of 197 type 1 and 63 of 110 type 2 pRCC cases. Five-year overall survival revealed no significant difference in dependence of cMET positivity (cMET− vs. cMET+: pRCC type 1: 84.8% vs. 80.3%, respectively [p = 0.303, log-rank]; type 2: 71.4% vs. 64.4%, respectively [p = 0.239, log-rank]). Interestingly, the subgroup analyses showed a significant difference for cMET expression in T stage and metastases of the pRCC type 2 (p = 0.014, p = 0.022, chi-square). The cMET-positive type 2 collective developed more metastases than the cMET-negative cohort (pRCC type 2 M+: cMET−: 2 [4.3%] vs. cMET+: 12 [19%]). cMET expression did not qualify as a prognostic marker in pRCC for overall survival.
CRIS-Team Scopus Importer:2022-02-04
Keywords: cMET; Outcome; Papillary renal cell carcinoma; Prognosis; Survival

Combination of Autoantibody Signature with PSA Level Enables a Highly Accurate Blood-Based Differentiation of Prostate Cancer Patients from Patients with Benign Prostatic Hyperplasia - Leidinger, Petra; Keller, Andreas; Milchram, Lisa; Harz, Christian; Hart, Martin; Werth, Angelika; Lenhof, Hans-Peter; Weinhaeusel, Andreas; Keck, Bastian; Wullich, Bernd; Ludwig, Nicole; Meese, Eckart (PLoS ONE, 2015)
Although an increased level of the prostate-specific antigen can be an indication for prostate cancer, other reasons often lead to a high rate of false positive results. Therefore, an additional serological screening of autoantibodies in patients' sera could improve the detection of prostate cancer. We performed protein macroarray screening with sera from 49 prostate cancer patients, 70 patients with benign prostatic hyperplasia and 28 healthy controls and compared the autoimmune response in those groups. We were able to distinguish prostate cancer patients from normal controls with an accuracy of 83.2%, patients with benign prostatic hyperplasia from normal controls with an accuracy of 86.0% and prostate cancer patients from patients with benign prostatic hyperplasia with an accuracy of 70.3%. Combining seroreactivity pattern with a PSA level of higher than 4.0 ng/ml this classification could be improved to an accuracy of 84.1%. For selected proteins we were able to confirm the differential expression by using luminex on 84 samples. We provide a minimally invasive serological method to reduce false positive results in detection of prostate cancer and according to PSA screening to distinguish men with prostate cancer from men with benign prostatic hyperplasia.
EVALuna2:16331

Combination of GP88 Expression in Tumor Cells and Tumor-Infiltrating Immune Cells Is an Independent Prognostic Factor for Bladder Cancer Patients - Eckstein, Markus; Lieb, Verena; Jung, Rudolf; Sikic, Danijel; Weigelt, Katrin; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Serrero, Ginette; Yue, Binbin; Hartmann, Arndt; et al. (Cells, 2021)
Urothelial bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide and accounts for approximately 3% of global cancer diagnoses. We are interested in prognostic markers that may characterize tumor cells (TCs) and immune cells (ICs) and their relationship in BCa. A potential candidate marker that meets these criteria is progranulin (GP88), which is expressed separately in TCs and ICs. We analyzed GP88 expression by immunohistochemistry (IHC) in 196 muscle-invasive BCa samples using a tissue microarray. The immunoreactive score for GP88 staining in TCs and the percentage of GP88-positive ICs was determined. An easy cutoff for the staining status of TCs (positive vs. negative) and ICs (0% vs. >0%) and, more generally, negative vs. positive GP88 staining could be applied. We detected 93 patients (47.4%) and 92 patients (46.9%) with GP88-positive TCs or ICs, respectively. The IHC results were correlated with clinicopathological and survival data. Positive GP88 staining in TCs appeared to be an independent poor prognostic factor for disease-specific survival (DSS) (RR (relative risk) = 1.74; p = 0.009) and recurrence-free survival (RFS) (RR = 1.92; p = 0.002). In contrast, negative GP88 staining in ICs was an independent negative predictor for overall survival (OS) (RR = 2.18; p < 0.001), DSS (RR = 2.84; p < 0.001) and RFS (RR = 2.91; p < 0.001) in multivariate Cox's regression analysis. When combining GP88 staining in TCs and ICs, a specific combination of GP88-positive TCs and GP88-negative ICs was associated with a 2.54-fold increased risk of death, a 4.21-fold increased risk of disease-specific death and a 4.81-fold increased risk of recurrence compared to GP88-negative TCs and GP88-positive ICs. In summary, GP88 positivity in TCs is a negative prognostic factor for DSS and RFS. In addition, GP88 positivity can mark ICs that are associated with a good prognosis (OS, DSS and RFS). The combination of GP88 staining in TCs and ICs appears to be a significant independent prognostic biomarker in muscle-invasive BCa.
CRIS-Team WoS Importer:2021-08-06

Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Comparative genomic hybridization shows complex genomic changes of plasmacytoid urothelial carcinoma - Keck, Bastian; Elhnann, Christina; Stoehr, Robert; Weigelt, Katrin; Goebell, Peter; Kunath, Frank; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Wach, Sven (Urologic Oncology-Seminars and Original Investigations, 2014)
To describe genomic imbalances in plasmacytoid urothelial carcinoma (PUC), which is a rare and aggressive variant of urothelial carcinoma (UC).In total, 25 formalin-fixed paraffin-embedded PUCs were analyzed by metaphase comparative genomic hybridization. Genomic imbalances were considered to be characteristic if they were detected in >= 20% of the cases. Chromosome regions deviating by >= 3 standard deviations from the average chromosome profile were scored as chromosomal gains or losses. Copy-number variations (CNVs) of CDH1 (16q 22.1), SNAI1 (20q 13.1), CCND1 (11q13.3), ERBB2 (17q12), and FOXO3 (6q21) were validated using quantitative polymerase chain reaction.Chromosomal aberrations were detected in every PUC analyzed, and the average number of aberrations was 10.24 (ranging from 1-15). Characteristic aberrations were gains on 1q (48%), 3p (20%), 6p (32%), 11q (72%), 15q (36%), 16q (44%), 17p (76%), 17q (88%), and 20q (88%) and losses on 2q (24%) 4p (36%), 4q (84%), 5q (44%), 6q (68%), 13q (20%), and Xq (52%). polymerase chain reaction-based analysis of CNV for CCND1 (11q13) showed a deletion in 73% of the cases. CDH1 (16q22) was deleted in 72% and amplified in 5%. ERBB2 (17q12) displayed remarkably few copy-number alterations, with only 14% showing an amplification. SNAI1 (20q13) showed reduced gene copy numbers in 59.1% of the cases, whereas no copy-number gains were detected. FOXO3 (6q21) exhibited the lowest number of copy-number alterations, with 9% of all cases showing an amplification.In PUCs, the frequency of aneuploidy and the complexity of genomic changes per tumor are greater than those described in conventional UC. The aberrations described in PUC involve the same regions that are associated with aggressive biological behavior in conventional UC. Gains on 11q, 17q, 17p, and 20q and losses on 4q and 6q affect most PUCs and seem to harbor important chromosomal regions for PUC carcinogenesis. Large-scale deletions on chromosome 9 were not detected. CNV analysis indicates heterozygous deletion of CDH1 as one underlying mechanism of loss of membranous E-cadherin in PUC. Loss of CCND1 and SNAI1 is a common molecular feature and could contribute to the aggressive biological behavior of PUC.
EVALuna2:6676

Comparative microRNA Profiling of Prostate Carcinomas with Increasing Tumor Stage by Deep Sequencing - Hart, Martin; Nolte, Elke; Wach, Sven; Szczyrba, Jaroslaw; Taubert, Helge; Rau, Tilman; Hartmann, Arndt; Graesser, Friedrich A.; Wullich, Bernd (Molecular Cancer Research, 2014)
MicroRNAs (miRNA) posttranscriptionally regulate gene expression and are important in tumorigenesis. Previous deep sequencing identified the miRNA profile of prostate carcinoma versus nonmalignant prostate tissue. Here, we generated miRNA expression profiles of prostate carcinoma by deep sequencing, with increasing tumor stage relative to corresponding nonmalignant and healthy prostate tissue, and detected clearly changed miRNA expression patterns. The miRNA profiles of the healthy and nonmalignant tissues were consistent with our previous findings, indicating a high fidelity of the method employed. In the tumors, quantitative real-time PCR (qRT-PCR) analysis of 40 paired samples of prostate carcinoma versus normal tissue revealed significant upregulation of miR-20a, miR-148a, miR-200b, and miR-375 and downregulation of miR-143 and miR-145. Hereby, miR-375 increased from normal to organ-confined tumors (pT2 pN0), slightly decreased in tumors with extracapsular growth (pT3 pN0), but was then expressed again at higher levels in lymph node metastasizing (pN1) tumors. The sequencing data for miR-375 were confirmed by Northern blotting and qRT-PCR. The regulation for other selected miRNAs could, however, not be confirmed by qRT-PCR in individual tumor stages. MiR-200b, in addition to miR-200c and miR-375 reduced the expression of SEC23A. Interestingly, miR-375, found by sequencing in pT2 upregulated by us and others in tumor versus normal tissue, and miR-15a, found by sequencing in pT2 and pT3 and in the metastasizing tumors, target the phosphatases PHLPP1 and PHLPP2, respectively. PHLPP1 and PHLPP2 dephosphorylate members of the AKT family of signal transducers, thereby inhibiting cell growth. Coexpression of miR-15a and miR-375 resulted in downregulation of PHLPP1/2 and strongly increased prostate carcinoma cell growth. Implications: These genomic data reveal relevant miRNAs in prostate cancer that may have biomarker and therapeutic potential. Mol Cancer Res; 12(2); 250-63. ©2013 AACR.
EVALuna2:6552

Computer-aided diagnosis in multiparametric mri of the prostate: An open-access online tool for lesion classification with high accuracy - Ellmann, Stephan; Schlicht, Michael; Dietzel, Matthias; Janka, Rolf Matthias; Hammon, Matthias; Saake, Marc; Ganslandt, Thomas; Hartmann, Arndt; Kunath, Frank; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (Cancers, 2020)
Computer-aided diagnosis (CADx) approaches could help to objectify reporting on prostate mpMRI, but their use in many cases is hampered due to common-built algorithms that are not publicly available. The aim of this study was to develop an open-access CADx algorithm with high accuracy for classification of suspicious lesions in mpMRI of the prostate. This retrospective study was approved by the local ethics commission, with waiver of informed consent. A total of 124 patients with 195 reported lesions were included. All patients received mpMRI of the prostate between 2014 and 2017, and transrectal ultrasound (TRUS)-guided and targeted biopsy within a time period of 30 days. Histopathology of the biopsy cores served as a standard of reference. Acquired imaging parameters included the size of the lesion, signal intensity (T2w images), diffusion restriction, prostate volume, and several dynamic parameters along with the clinical parameters patient age and serum PSA level. Inter-reader agreement of the imaging parameters was assessed by calculating intraclass correlation coefficients. The dataset was stratified into a train set and test set (156 and 39 lesions in 100 and 24 patients, respectively). Using the above parameters, a CADx based on an Extreme Gradient Boosting algorithm was developed on the train set, and tested on the test set. Performance optimization was focused on maximizing the area under the Receiver Operating Characteristic curve (ROCAUC). The algorithm was made publicly available on the internet. The CADx reached an ROCAUC of 0.908 during training, and 0.913 during testing (p = 0.93). Additionally, established rule-in and rule-out criteria allowed classifying 35.8% of the malignant and 49.4% of the benign lesions with error rates of <2%. All imaging parameters featured excellent inter-reader agreement. This study presents an open-access CADx for classification of suspicious lesions in mpMRI of the prostate with high accuracy. Applying the provided rule-in and rule-out criteria might facilitate to further stratify the management of patients at risk.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Artificial intelligence; Computer-aided diagnosis; Machine learning; Prostate cancer; Prostate mpMRI

Consensus on definition and severity grading of lymphatic complications after kidney transplantation - Mehrabi, A.; Kulu, Y.; Sabagh, M.; Khajeh, E.; Mohammadi, S.; Ghamarnejad, O.; Golriz, M.; Morath, C.; Bechstein, W. O.; Berlakovich, G. A.; Demartines, N.; Duran, M.; et al. (British Journal of Surgery, 2020)
Background: The incidence of lymphatic complications after kidney transplantation varies considerably in the literature. This is partly because a universally accepted definition has not been established. This study aimed to propose an acceptable definition and severity grading system for lymphatic complications based on their management strategy. Methods: Relevant literature published in MEDLINE and Web of Science was searched systematically. A consensus for definition and a severity grading was then sought between 20 high-volume transplant centres. Results: Lymphorrhoea/lymphocele was defined in 32 of 87 included studies. Sixty-three articles explained how lymphatic complications were managed, but none graded their severity. The proposed definition of lymphorrhoea was leakage of more than 50 ml fluid (not urine, blood or pus) per day from the drain, or the drain site after removal of the drain, for more than 1 week after kidney transplantation. The proposed definition of lymphocele was a fluid collection of any size near to the transplanted kidney, after urinoma, haematoma and abscess have been excluded. Grade A lymphatic complications have a minor and/or non-invasive impact on the clinical management of the patient; grade B complications require non-surgical intervention; and grade C complications require invasive surgical intervention. Conclusion: A clear definition and severity grading for lymphatic complications after kidney transplantation was agreed. The proposed definitions should allow better comparisons between studies.
CRIS-Team Scopus Importer:2020-04-07

Correction to: The natural course of pT2 prostate cancer with positive surgical margin: predicting biochemical recurrence (World Journal of Urology, (2015), 33, 7, (973-979), 10.1007/s00345-015-1510-y) - Karl, A.; Buchner, A.; Tympner, C.; Kirchner, T.; Ganswindt, U.; Belka, C.; Ganzer, R.; Burger, M.; Eder, F.; Hofstädter, F.; Schilling, D.; Sievert, K.; et al. (World Journal of Urology, 2020)
In multivariate analysis, GS of the regular prostatectomy specimen was the only statistically significant parameter for pT2R1 prostate cancer.
CRIS-Team Scopus Importer:2020-02-28

Corrigendum to "Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes" [European Urology Oncology (2023)]. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2023)
EVALuna2:542094

Co-staining of microRNAs and their target proteins by miRNA in situ hybridization and immunohistofluorescence on prostate cancer tissue microarrays - Eckstein, Markus; Sailer, Verena; Nielsen, Boye Schnack; Wittenberg, Thomas; Wiesmann, Veit; Lieb, Verena; Nolte, Elke; Hartmann, Arndt; Kristiansen, Glen; Wernert, Nicolas; Wullich, Bernd; Taubert, Helge; et al. (Laboratory Investigation, 2019)
The co-expression of miRNAs and their target proteins was studied on tissue microarrays from different prostate cancer (PCa) patients. PCa of primary Gleason pattern 4 (GP4), lymph node metastases of GP4, distant metastases, and normal tissue from the transitional and peripheral zones were co-stained by fluorescent miRNA in situ hybridization (miRisH) and protein immunohistofluorescence (IHF). The miRNAs and corresponding target proteins include the pairs miR-145/ERG, miR-143/uPAR, and miR-375/SEC23A. The fluorescence-stained and scanned tissue microarrays (TMAs) were evaluated by experienced uropathologists. The pair miR-145/ERG showed an exclusive staining for miR-145 in the nuclei of stromal cells, both in tumor and normal tissue, and for ERG in the cytoplasm with/without co-expression in the nucleus of tumor cells. The pair miR-143/uPAR revealed a clear distinction between miR-143 in the nuclei of stromal cells and uPAR staining in the cytoplasm of tumor cells. Metastases (lymph node and distant) however, showed tumor cells with cytoplasmic staining for miR-143/uPAR. In normal tissues, beside the nuclei of the stroma cells, gland cells could also express miR-143 and uPAR in the cytoplasm. miR-375 showed particular staining in the nucleoli of GP4 and metastatic samples, suggesting that nucleoli play a special role in sequestering proteins and miRNAs. Combined miRisH/IHF allows for the study of miRNA expression patterns and their target proteins at the single-cell level.
CRIS-Team Scopus Importer:2019-06-28

C-reactive protein flare predicts response to anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Büttner, Thomas; Goldschmidt, Franziska; Jarczyk, Jonas; Becker, Philippe; Zeuschner, Philip; Weinke, Maximilian; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; et al. (European Journal of Cancer, 2022)
Purpose: Robust biomarkers to predict response to immune checkpoint blockade (ICB) in metastatic urothelial carcinoma (mUC) are still in demand. Recently, early C-reactive protein (CRP) kinetics and especially the novel CRP flare-response phenomenon has been associated with immunotherapy response. Methods: We conducted a multicentre observational study comprising 154 patients with mUC treated with ICB to evaluate the predictive value of a previously described on-treatment CRP kinetics: CRP flare responders (at least doubling of baseline CRP within the first month after initiation of ICB followed by a decline below baseline within three months), CRP responders (decline in baseline CRP by ≥ 30% within three months without a prior flare) and the remaining patients as CRP non-responders. CRP kinetics groups were correlated with baseline parameters, PD-L1 status, progression-free survival (PFS) and overall survival (OS). Results: Objective response was observed in 57.1% of CRP responders, 45.8% of CRP flare responders and 17.9% of CRP non-responders (P < 0.001). CRP flare response was associated with prolonged PFS and OS (P < 0.001). In multivariable Cox regression analysis, CRP flare responders showed a risk reduction of ∼70% for tumour progression and death compared to CRP non-responders. Subgroup analysis of CRP flare responders revealed that patients with a long-flare response (completed flare-response kinetics ≥6 weeks on-treatment) showed even more favourable outcomes following ICB (HR = 0.18, 95%-CI: 0.07–0.48, P < 0.001). Conclusion: CRP (flare)response robustly predicts immunotherapy response and outcomes in mUC independent of PD-L1 status. Thus, early on-treatment CRP kinetics is a promising low-cost and easy-to-implement biomarker to optimise therapy monitoring in patients with mUC treated with ICB.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biomarker; Bladder cancer; C-reactive protein; CRP flare; CRP flare-Response; Immune checkpoint blockade; Immunotherapy; Long-flare; Metastatic urothelial carcinoma

Current Role of Multiparametric MRI and MRI Targeted Biopsies for Prostate Cancer Diagnosis in Germany: A Nationwide Survey - Saar, Matthias; Linxweiler, Johannes; Borkowetz, Angelika; Fussek, Sebastian; Urbanova, Katerina; Kristiansen, Glen; Wullich, Bernd; Bellut, Laura (Urologia Internationalis, 2020)
Introduction: Multiparametric MRI (mpMRI) and MRI targeted biopsies (MRtb) are a new standard in prostate cancer (PCa) screening and diagnosis. Guidelines already include this approach for patients at risk. We aimed to gather information from German urologists about their knowledge, routine use, and attitude toward mpMRI and consecutive biopsy methods. Materials and Methods: An anonymous online questionnaire was sent via Survey Monkey to the members of the German Society of Urology (DGU). Statistical analyses were performed using SPSS version 25.0. Results: 496 members with a median age of 48.6 years (±11.7) participated in the survey. The majority rated mpMRI of the prostate as a very useful diagnostic tool (72.7%). MRtb of the prostate was considered as very advantageous (71.5%). MpMRI was used by 95.9%, and 83.2% also recommended MRtb predominantly in clinical institutions. For targeted biopsy, MRI-ultrasound fusion biopsy was clearly favored (75.8%). MpMRI was mostly used in patients with previously negative biopsy (90.9%) and in patients under active surveillance (60.9%). Arguments against the use of prostate mpMRI are costs (84.9%) and/or lack of sufficient radiological infrastructure (17.4%). Conclusion: Our data illustrate the meanwhile high acceptance and clinical use of the prostate mpMRI and MRtb in Germany.
CRIS-Team Scopus Importer:2020-07-24

Cytotoxic T-cell-related gene expression signature predicts improved survival in muscle-invasive urothelial bladder cancer patients after radical cystectomy and adjuvant chemotherapy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Assessment of the immune status of muscle-invasive bladder cancer (MIBC) has previously shown to be prognostically relevant after treatment with curative intent. We conducted this study to develop a clinically applicable immune gene expression assay to predict prognosis and adjuvant chemotherapy benefit. Patients and methods Gene expression of CD3Z, CD8A and CXCL9, immune cell (IC) populations including stromal tumor infiltrating lymphocytes (sTILs), T-cells, natural killer cells (NK-cells), macrophages, Programmed cell death protein 1 positive (PD-1) IC and tumor subtypes (MD Anderson Cancer Center/MDACC-approach) were assessed in 187 MIBC patients (Comprehensive Cancer Center Erlangen-EMN/CCC-EMN-cohort). A gene expression signature was derived by hierarchical-clustering and validated in The Cancer Genome Atlas (TCGA)-cohort. IC populations in the TCGA cohort were assessed via CIBERSORT. Benefit of platinum-containing adjuvant chemotherapy was assessed in a pooled cohort of 125 patients. Outcome measurements were disease specific survival, disease-free survival and overall survival. Results The gene expression signature of CXCL9, CD3Z and CD8A correlates with quantitative amounts of specific IC populations and sTILs (CCC-EMN: ρ-range: 0.44-0.74; TCGA: ρ-range: 0.56-0.82) and allows stratification of three different inflammation levels (inflamed high, inflamed low, uninflamed). Highly inflamed tumors are preferentially basal subtype and show favorable 5-year survival rates of 67.3% (HR=0.27; CCC-EMN) and 55% (HR=0.41; TCGA). Uninflamed tumors are predominantly luminal subtypes and show low 5-year survival rates of 28% (CCC-EMN) and 36% (TCGA). Inflamed tumors exhibit higher levels of PD-1 and Programmed cell death 1 ligand 1 (PD-L1). Patients undergoing adjuvant platinum-based chemotherapy with 'inflamed high' tumors showed a favorable 5-year survival rate of 64% (HR=0.27; merged CCC-EMN and TCGA cohort). Conclusion The gene expression signature of CD3Z, CD8A and CXCL9 can assess the immune status of MIBC and stratify the survival of MIBC patients undergoing surgery and adjuvant platinum-based chemotherapy. Furthermore, the assay can identify patients with immunological hot tumors with particular high expression of PD-L1 potentially suitable for immunotherapy.
CRIS-Team Scopus Importer:2020-06-05
Keywords: immunology; pathology; urology

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Development and Usability Analysis of a Multimedia eConsent Solution - Schneiderheinze, Hauke; Prokosch, Hans-Ulrich; Apel, Hendrik; Bellut, Laura; Wullich, Bernd; Trollmann, Regina; Schüttler, Christina (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
BACKGROUND: More and more medical data is being stored digitally in routine care. The secondary use of patient data is only possible to a limited extent for data protection reasons. In order to enable a long-term and far-reaching use of secondary data, a possible approach is to obtain "broad consent" from patients, e.g. on research projects whose purpose is still unknown at the time of consent. OBJECTIVE: To develop and evaluate an interactive eConsent prototype that presents the extensive contents of the "broad consent" in multimedia form for the purpose of a successful and resource-efficient information and consent process. METHODS: The eConsent prototype was designed on basis of a literature review and in accordance with the goals of the German medical informatics initiative. User tests and subsequent questionnaire surveys using the System Usability Scale (SUS) were carried out with patients from a university hospital to assess the prototype's usability. The study was conducted in a quasi-experimental, one-group posttest-only design. RESULTS: The created interactive prototype can present the contents acoustically and visually and offers the possibility to retrieve additional information. With a SUS score of 84,1/100 the results indicate a very good usability of the prototype. CONCLUSION: The next steps will include further refinements of the prototype based on the feedback received and a subsequent study with a broader user group aimed at introducing an eConsent tool as part of a patient portal.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Informed consent; multimedia; patient participation; patient portals

Diagnosis and Therapeutic Management in Kidney, Ureter and Bladder Trauma - Hirsch, Karin; Heinz, Marco; Wullich, Bernd (Aktuelle Urologie, 2017)
Trauma refers to the destruction of tissues or organs by external forces and it is the most common cause of mortality and morbidity in children (1, 2). Injuries of the genitourinary tract may be the result of blunt (falls, sport injuries, motor vehicle accidents and sexual abuse) or penetrating (stab wounds, gun shots, falling onto sharp objects) injuries. The genitourinary tract is significantly injured in 2.9 % of paediatric trauma patients [4]. In the paediatric population, the kidney is the most affected organ in the genitourinary tract (> 60 % of all genitourinary tract injuries) [4]. Blunt renal trauma is the most common type of injury representing 80-90 % [4]. The paediatric kidney is more susceptible due to less abdominal and retroperitoneal fat, weaker trunk and abdominal muscles and a lower position in the abdomen. Preexisting renal abnormalities such as UPJ obstruction, hydronephrosis, horseshoe kidney or ectopic kidney make the kidney more vulnerable. Spiral computed tomography is the gold standard method for radiological assessment. Surgical intervention is needed only in the minority of children. Isolated ureteral injury due to trauma is very rare in children. Penetrating ureteral trauma is more common than blunt trauma in the paediatric population. Among all urological trauma cases, the incidence of ureteral injury is lower than 1 % [4]. Ureteral injuries include contusion, laceration and avulsion. Because of their hyperextensible vertebral column, children are more likely to sustain deceleration injuries. Delayed films of IVP and CT are the main diagnostic tools whereas the gold standard is retrograde ureteropyelography. Ureteral injury treatment options depend on the location of injury. The bladder in children is a more abdominal organ than in adults. Lying in an exposed position above the pelvis, the bladder is more vulnerable in this age group as it is less well protected due to the less developed abdominal fat and rectus muscles. Here, too, the most common type of trauma is blunt injury. High percentages of bladder injuries are associated with pelvic fractures (70-90 %) [4]. The average rate of bladder injury in patients with pelvic fractures is 4 % in the paediatric age group [4]. Conventional or CT cystography is the gold standard method of imaging.
EVALuna2:35926

Diagnostic potential of major and trace elements in the serum of bladder cancer patients - Wach, Sven; Weigelt, Katrin; Michalke, Bernhard; Lieb, Verena; Stoehr, Robert; Keck, Bastian; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Chaudhri, Anwar (Journal of Trace Elements in Medicine and Biology, 2018)
Major and trace elements may play a role in the diagnosis of diseases. In this study, we investigated the concentration of 26 major and trace elements in the serum by inductively coupled plasma (ICP) - optical emission spectrometry (OES) and ICP-sector field-mass spectrometry (sf-MS). We analyzed the serum from a discovery cohort of 6 bladder cancer (BCa) patients and 12 healthy controls as well as from a validation cohort of 21 BCa patients, 29 non-tumor bladder patients (with acute and chronic inflammation) and 18 healthy controls. Patients were recruited after written consent was obtained at one medical center. Serum was prepared from peripheral blood prior to surgical treatment. Differences in the levels of major and trace elements were determined by a nonparametric Mann-Whitney test and Kruskal-Wallis statistics. In the discovery cohort, we measured significantly increased levels of calcium, mercury, potassium, lithium, nickel, phosphorus and strontium and a significantly decreased level of sodium in BCa patients compared with healthy controls. These findings were reassessed in our validation cohort. We measured significantly increased levels of boron, calcium, cadmium, copper, chromium, lead, lithium, potassium, magnesium, nickel, sulfur, strontium, titan, vanadium and zinc and significantly decreased levels of iron and molybdenum. When we studied the concordance for the discovery and validation cohorts, concentrations of five elements were detected as significantly increased in BCa patients compared with healthy controls: calcium, lithium, potassium, nickel, and strontium. Interestingly, the levels of three elements (calcium, potassium and strontium) were also significantly increased in non-tumor bladder patients compared with healthy controls. But no element was significantly altered between non-tumor bladder patients and BCa patients. In summary, we suggest that determination of the elements calcium, lithium, nickel and strontium in the serum could be a new and promising tool for the early diagnosis of BCa.
EVALuna2:32785

Differences in the frequencies of HLA-class I and II alleles between German patients with renal cell carcinoma and healthy controls - Goebel, Steffen; Kehlen, Astrid; Bluemke, Karen; Altermann, Wolfgang; Schlaf, Gerald; Fischer, Kersten; Fornara, Paolo; Wullich, Bernd; Wach, Sven; Taubert, Helge (Cancer Immunology, Immunotherapy, 2017)
The human leukocyte antigen (HLA) system is a major part of the human immune system and has an impact on tumor initiation, tumor progression, and immunosurveillance. Renal cell carcinoma tumors are considered to be immunogenic. Therefore, we studied the allele frequencies of four gene loci (HLA-A, -B, -C, and HLA-DR) in a cohort of German renal cell carcinoma (RCC) patients and in healthy controls. HLA-A-C were determined using serological methods, whereas HLA-C12, C14, C16, C18, and HLA-DR were characterized through the use of standard molecular biological methods. The occurrence of the HLA-C*12 allele was significantly increased in German RCC patients compared with healthy controls (P < 0.005; Fisher's exact test), whereas the occurrence of the HLA-DRB1*04 allele was significantly reduced in RCC patients compared with healthy controls (P < 0.05; Fisher's exact test). However, the presence of allele HLA-C*12 was not significantly associated with 10 year overall survival. We suggest that the frequency of HLA alleles can affect development of RCC and could add knowledge as predictive marker for future immunotherapies.
EVALuna:33572

Differential blood-based diagnosis between benign prostatic hyperplasia and prostate cancer: miRNA as source for biomarkers independent of PSA level, Gleason score, or TNM status - Leidinger, Petra; Hart, Martin; Backes, Christina; Rheinheimer, Stefanie; Keck, Bastian; Wullich, Bernd; Keller, Andreas; Meese, Eckart (Tumor Biology, 2016)
Since the benefit of prostate-specific antigen (PSA) screening remains controversial, new non-invasive biomarkers for prostate carcinoma (PCa) are still required. There is evidence that microRNAs (miRNAs) in whole peripheral blood can separate patients with localized prostate cancer from healthy individuals. However, the potential of blood-based miRNAs for the differential diagnosis of PCa and benign prostatic hyperplasia (BPH) has not been tested. We compared the miRNome from blood of PCa and BPH patients and further investigated the influence of the tumor volume, tumor-node-metastasis (TNM) classification, Gleason score, pretreatment risk status, and the pretreatment PSA value on the miRNA pattern. By microarray approach, we identified seven miRNAs that were significantly deregulated in PCa patients compared to BPH patients. Using quantitative real time PCR (qRT-PCR), we confirmed downregulation of hsa-miR-221* (now hsa-miR-221-5p) and hsa-miR-708* (now hsa-miR-708-3p) in PCa compared to BPH. Clinical parameters like PSA level, Gleason score, or TNM status seem to have only limited impact on the overall abundance of miRNAs in patients' blood, suggesting a no influence of these factors on the expression of deregulated miRNAs.
EVALuna2:16327

Differential prognostic value of MYC immunohistochemistry in subtypes of papillary renal cell carcinoma - Bellut, Julia; Bertz, Simone; Nolte, Elke; Stoehr, Christine; Polifka, Iris; Lieb, Verena; Herrmann, Edwin; Jung, Rudolf; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Wach, Sven (Scientific Reports, 2017)
The histomorphological subtyping of papillary renal cell carcinomas (pRCCs) has improved the predictions of patients' long-term survival. Based on our previous results, we hypothesized that the MYC proto-oncogene would show differential expression in pRCC subtypes. Using a multi-institutional cohort of 204 pRCC patients we assessed the additional value of the immunohistochemical markers MYC, MINA53, and Ki67 in predicting patient's long-term survival. The clinical endpoints were overall survival (OS) and cancer-specific survival (CSS). Nomograms were constructed to predict each patient's risk of death (OS). The incorporation of the MYC staining patterns allowed the stratification of pRCC type 1 patients into better and worse prognostic groups. None of the patients with pRCC type 1 tumors and favorable MYC staining patterns died from tumor-related causes. This prognostic value was independent of the patient's age at surgery, the pathological tumor stage and presence of lymph node invasion. we could show that the immunohistochemical assessment of MYC and the histomorphological subtyping of pRCC stratifies pRCC type 1 tumors with regard to OS and CSS. The determination of the histomorphologic pRCC subtype in combination with the MYC immunohistochemical staining patterns allows a more accurate prediction of patients' individual risk of death.
EVALuna2:33570

Digital volumetric assessment of CIS and tumor mass compliments conventional histopathological assessment in muscle-invasive urothelial bladder cancer - Lange, Fabienne; Geppert, Carol-Immanuel; Bahlinger, Veronika; Bertz, Simone; Stöhr, Robert; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Virchows Archiv, 2024)
Carcinoma in situ (CIS) of the bladder is a known parameter regarding the prognosis and recurrence tendency of urothelial carcinomas. Nevertheless, there is little evidence whether the amount of CIS or other precursor lesions, as well as the quantified tumor mass of muscle-invasive urothelial carcinoma, has an influence on the survival or recurrence rate of affected patients. From 80 patients with muscle invasive urothelial bladder cancer and radical cystectomy, 23 samples each were obtained as part of a whole organ mapping in a single institution study, in which the precursor lesions and tumor area were digitally measured and further correlated to pathological standard parameters, patient survival, molecular luminal and basal subtypes, and immune infiltration. Significant correlations were found between tumor mass and surface lining CIS amount for pT-stage, lymphovascular invasion, and perineural infiltration. Furthermore, an increased tumor mass as well as an increased amount of CIS combined with an increased tumor mass showed a significantly reduced survival rate in multivariable analysis (HR = 2.75; P = 0.019 vs. HR = 3.54; P = 0.002) as well as a significantly increased recurrence. No correlations could be found with molecular subtypes and immune infiltration. The exact measurement of the tumor mass with and without the CIS surface area, whether manually or, more specifically, digitally, could be incorporated into routine diagnostics and implemented as an independent predictor for patient post-surgical outcomes. It can therefore serve as an additional predictor for risk stratification and, if necessary, intensified follow-up care or therapy.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Muscle invasive bladder cancer; Prognosis; Radical cystectomy; Survival; Urothelial carcinoma; Urothelial carcinoma in situ

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, Rebecca; Moskalev, Evgeny; Haller, Florian; Stöhr, Robert; Eckstein, Markus; Zinnall, Ulrike; Gaisa, Nadine T.; Comperat, Eva; Perren, Aurel; Keck, Bastian; Allory, Yves; et al. (Histopathology, 2019)
Aims Nested variant of urothelial carcinoma (NVUC) is rare, and only a few small series exist. Molecular characteristics and the classifying marker profile as well as therapeutic targets of this specific variant are mostly unknown. The aim of this study was to characterise NVUC at the molecular level in one of the largest cohorts to date. In addition, we applied an immunohistochemical marker panel in order to define the molecular subtype. Methods and results Sixty NVUC cases were collected from different departments. TERT promoter mutation analysis was carried out in all samples using SNaPshot analysis. Targeted sequencing of 48 cancer-related genes by next-generation sequencing (NGS) analysis was performed in a subset of 26 cases. Immunohistochemical markers CD44, CK5, CK14, EGFR, p63, FOXA1, GATA3, CD24 and CK20 were used to elucidate the molecular subtype. A total of 62.5% of NVUC cases harboured a mutation of the TERT promoter. Additionally, TP53, JAK3 and CTNNB1 were among the most frequently mutated genes identified by NGS analysis. Subtyping revealed that all NVUC express luminal markers such as CD24, FOXA1, GATA3 and CK20. Conclusions In summary, NVUC belong to the luminal molecular subtype. Moreover, a subset of NVUC seems to be characterised by mutations of the Wnt and inflammatory pathways, including JAK3 mutations, indicating a different biological background compared to conventional urothelial bladder cancer.
CRIS-Team WoS Importer:2019-11-01

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, R.; Moskalev, Evgeny; Haller, Florian; Stoehr, R.; Eckstein, Markus; Zinnall, U.; Gaisa, N. T.; Comperat, E.; Perren, A.; Keck, Bastian; Allory, Y.; et al. (Virchows Archiv, 2019)
CRIS-Team WoS Importer:2019-09-27

Donor acute kidney injury and short-term graft outcome in renal transplantation - Jacobi, Johannes; Rebhan, Dirk; Heller, Katharina; Velden, Joachim; Hilgers, Karl Friedrich; Wullich, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Clinical Transplantation, 2014)
With increased waiting times for kidney transplantation, marginal organs from expanded criteria donors (ECD) are increasingly offered for allocation. In addition to ECD status, donors may have suffered from acute kidney injury (AKI) prior to organ procurement.In this retrospective cohort study, we studied short-term allograft function in 517 kidney transplants performed between the years 2008-2014. Recipients of allografts from deceased organ donors were categorized as standard criteria donors (SCD) or ECD with or without AKI defined by RIFLE criteria.Of 382 deceased donations, 174 (45.5%) were classified as ECD and 63 (16.5%) fulfilled AKI criteria. Donor creatinine on hospital admission was similar, whereas creatinine before organ procurement differed (p < 0.001). Despite these differences, serum creatinine and eGFR at discharge and after one yr showed only minor differences between kidneys with or without AKI. In multivariate linear regression analyses, donor AKI was not a predictor of one-yr allograft function.Given the poor prognosis of dialysis patients and the increase in waiting time, kidneys from SCD and ECD donors with AKI should be allocated for transplantation. In case of ECD donors with AKI, recipients should be informed about the possibility of permanent non-function or early graft loss.
EVALuna2:3714

Drug Therapy Safety with new oral Antitumor Agents for the Therapy of Prostate and Renal Cell Carcinoma: Findings from the AMBORA Study - Cuba, Lisa; Schlichtig, Katja; Dürr, Pauline; Bellut, Laura; Meidenbauer, Norbert; Kunath, Frank; Goebell, Peter; Mackensen, Andreas; Dörje, Frank; Fromm, Martin; Wullich, Bernd (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Early CRP kinetics predict long-term treatment success and favorable outcomes of anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Buettner, Thomas; Jarczyk, Jonas; Zeuschner, Philip; Weinke, Maximilan; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; Nuhn, Philipp; Tully, Karl; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Effect of Hospital and Surgeon Case Volume on Perioperative Quality of Care and Short-term Outcomes After Radical Cystectomy for Muscle-invasive Bladder Cancer: Results From a European Tertiary Care Center Cohort - Vetterlein, Malte W.; Meyer, Christian P.; Leyh-Bannurah, Sami-Ramzi; Mayr, Roman; Gierth, Michael; Fritsche, Hans-Martin; Burger, Maximilian; Keck, Bastian; Wullich, Bernd; Martini, Thomas; Bolenz, Christian; Pycha, Armin; et al. (Clinical Genitourinary Cancer, 2017)
This prospective multicenter study analyzed the effect of hospital and surgeon case volume on perioperative quality of care and short-term complications and mortality in 479 patients undergoing radical cystectomy for bladder cancer. We found that hospital volume might represent an at least equally important factor regarding postoperative complications as the surgeon case volume itself at European tertiary care centers. Background Case volume has been suggested to affect surgical outcomes in different arrays of procedures. We aimed to delineate the relationship between case volume and surgical outcomes and quality of care criteria of radical cystectomy (RC) in a prospectively collected multicenter cohort. Patients and Methods This was a retrospective analysis of a prospectively collected European cohort of patients with bladder cancer treated with RC in 2011. We relied on 479 and 459 eligible patients with available information on hospital case volume and surgeon case volume, respectively. Hospital case volume was divided into tertiles, and surgeon volume was dichotomized according to the median annual number of surgeries performed. Binomial generalized estimating equations controlling for potential known confounders and inter-hospital clustering assessed the independent association of case volume with short-term complications and mortality, as well as the fulfillment of quality of care criteria. Results The high-volume threshold for hospitals was 45 RCs and, for high-volume surgeons, was > 15 cases annually. In adjusted analyses, high hospital volume remained an independent predictor of fewer 30-day (odds ratio, 0.34; P = .002) and 60- to 90-day (odds ratio, 0.41; P = .03) major complications but not of fulfilling quality of care criteria or mortality. No difference between surgeon volume groups was noted for complications, quality of care criteria, or mortality after adjustments. Conclusion The coordination of care at high-volume hospitals might confer a similar important factor in postoperative outcomes as surgeon case volume in RC. This points to organizational elements in high-volume hospitals that enable them to react more appropriately to adverse events after surgery. (C) 2017 Elsevier Inc. All rights reserved.
EVALuna2:35912

Effects of whole-body electromyostimulation combined with individualized nutritional support on body composition in patients with advanced cancer: a controlled pilot trial - Schink, Kristin; Herrmann, Hans J.; Schwappacher, Raphaela; Meyer, Julia; Orlemann, Till; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (BMC Cancer, 2018)
BACKGROUND: Physical exercise and nutritional treatment are promising measures to prevent muscle wasting that is frequently observed in advanced-stage cancer patients. However, conventional exercise is not always suitable for these patients due to physical weakness and therapeutic side effects. In this pilot study, we examined the effect of a combined approach of the novel training method whole-body electromyostimulation (WB-EMS) and individualized nutritional support on body composition with primary focus on skeletal muscle mass in advanced cancer patients under oncological treatment. METHODS: In a non-randomized controlled trial design patients (56.5% male; 59.9 ± 12.7 years) with advanced solid tumors (UICC III/IV, N = 131) undergoing anti-cancer therapy were allocated to a usual care control group (n = 35) receiving individualized nutritional support or to an intervention group (n = 96) that additionally performed a supervised physical exercise program in form of 20 min WB-EMS sessions (bipolar, 85 Hz) 2×/week for 12 weeks. The primary outcome of skeletal muscle mass and secondary outcomes of body composition, body weight and hand grip strength were measured at baseline, in weeks 4, 8 and 12 by bioelectrical impedance analysis and hand dynamometer. Effects of WB-EMS were estimated by linear mixed models. Secondary outcomes of physical function, hematological and blood chemistry parameters, quality of life and fatigue were assessed at baseline and week 12. Changes were analyzed by t-tests, Wilcoxon signed-rank or Mann-Whitney-U-tests. RESULTS: Twenty-four patients of the control and 58 of the WB-EMS group completed the 12-week trial. Patients of the WB-EMS group had a significantly higher skeletal muscle mass (0.53 kg [0.08, 0.98]; p = 0.022) and body weight (1.02 kg [0.05, 1.98]; p = 0.039) compared to controls at the end of intervention. WB-EMS also significantly improved physical function and performance status (p < 0.05). No significant differences of changes in quality of life, fatigue and blood parameters were detected between the study groups after 12 weeks. CONCLUSIONS: Supervised WB-EMS training is a safe strength training method and combined with nutritional support it shows promising effects against muscle wasting and on physical function in advanced-stage cancer patients undergoing treatment. TRIAL REGISTRATION: ClinicalTrials.gov NCT02293239 (Date: November 18, 2014).
EVALuna2:35141

Efficacy of anti-PD(L)1 treatment in patients with metastatic urothelial cancer based on mRNA- and protein- based PD-L1 determination: Results from the multicentric, retrospective FOsMIC trial - Jarczyk, J.; Wirtz, R.; Roghmann, F.; Juette, H.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Elevated Microsatellite Alterations at Selected Tetranucleotide Repeats (EMAST) in Penile Squamous Cell Carcinoma-No Evidence for a Role in Carcinogenesis. - Fiegl, August; Wendler, Olaf; Giedl, Josef; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Simmer, Femke; Nagtegaal, Iris; Wullich, Bernd; Bertz, Simone; Hartmann, Arndt; et al. (Current Oncology, 2024)
Penile squamous cell carcinoma (pSCC) is a rare malignancy with a global incidence ranging from 0.1 to 0.7 per 100,000 males. Prognosis is generally favorable for localized tumors, but metastatic pSCC remains challenging, with low survival rates. The role of novel biomarkers, such as tumor mutational burden (TMB) and microsatellite instability (MSI), in predicting the response to immune checkpoint inhibitors (ICIs) has been investigated in various cancers. However, MSI has not been observed in pSCC, limiting immunotherapy options for this patient subgroup. Elevated microsatellite alterations at selected tetranucleotide repeats (EMAST) are a distinct form of genomic instability associated with deficient MSH3 expression, which has been proposed as a potential biomarker in several cancers. This study investigates EMAST and MSH3 expression in a cohort of 78 pSCC cases using PCR, fragment analysis and immunohistochemistry. For the detection of EMAST, the stability of five microsatellite markers (D9S242, D20S82, MYCL1, D8S321 and D20S85) was analyzed. None of the cases showed an instability. As for MSH3 immunohistochemistry, all analyzable cases showed retained MSH3 expression. These results strongly suggest that neither EMAST nor MSH3 deficiency is involved in the carcinogenesis of pSCC and do not represent reliable predictive biomarkers in this entity. Furthermore, these findings are in full agreement with our previous study showing a very low frequency of MSI and further support the thesis that EMAST and MSI are strongly interconnected forms of genomic instability. Further research is needed to explore novel therapeutic targets and predictive biomarkers for immunotherapy in this patient population.
EVALuna2:578801

Endogenous Retroviral-K Envelope Is a Novel Tumor Antigen and Prognostic Indicator of Renal Cell Carcinoma - Weyerer, Veronika; Strissel, Pamela; Stohr, Christine; Eckstein, Markus; Wach, Sven; Taubert, Helge; Brandl, Lisa; Geppert, Carol-Immanuel; Wullich, Bernd; Cynis, Holger; Beckmann, Matthias; Seliger, Barbara; et al. (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is one of the ten most common cancers for men and women with an approximate 75% overall 5-year survival. Sixteen histological tumor subtypes exist and the most common are papillary, chromophobe and clear cell renal cell carcinoma (ccRCC) representing 85% of all RCC. Although epigenetically silenced, endogenous retroviral (ERV) genes become activated in tumors and function to ignite immune responses. Research has intensified to understand ERV protein function and their role as tumor antigens and targets for cancer (immune) therapy. ERV-K env is overexpressed and implicated as a therapeutic target for breast cancer, however studies in RCC are limited. In this investigation a human RCC tissue microarray (TMA) (n=374) predominantly consisting of the most common histological tumor subtypes was hybridized with an ERV-K env antibody and correlated with patient clinical data. TMA results showed the highest amount of ERV-K env protein expression and the strongest significant membrane expression in ccRCC versus other RCC subtypes. High ERV-K env total protein expression of all tumor subtypes significantly correlated with low tumor grading and a longer disease specific survival using multivariable analyses. Cell proliferation and invasion were assayed using the kidney cell lines HEK293 with wild-type p53 and a ccRCC cell line MZ1257RC mutated for p53. Transfecting these cell lines with a codon optimized ERV-K113 env overexpressing CMV vector was performed with or without 5'-Aza-2'-deoxycytidine (Aza) treatment to sustain promoter de-methylation. MZ1257RC showed induction of ERV-K113 expression and significantly increased both proliferation and invasion in the presence or absence of Aza. HEK293 cells demonstrated a restriction of ERV-K113 env expression and invasion with no changes in proliferation in the absence of Aza. However, in the presence of Aza despite increased ERV-K113 env expression, an inhibition of HEK293 proliferation and a further restriction of invasion was found. This study supports ERV-K env as a single prognostic indicator for better survival of RCC, which we propose represents a new tumor antigen. In addition, ERV-K env significantly regulates proliferation and invasion depending on p53 status and Aza treatment.
CRIS-Team WoS Importer:2021-05-14
Keywords: tumor antigen; renal cell carcinoma; patient prognosis; p53; ERV-K; invasion; azacytidine; endogenous retrovirus

ERBB2 Expression as Potential Risk-Stratification for Early Cystectomy in Patients with pT1 Bladder Cancer and Concomitant Carcinoma in situ - Breyer, Johannes; Otto, Wolfgang; Wirtz, Ralph M.; Wullich, Bernd; Keck, Bastian; Erben, Philipp; Kriegmair, Maximilian C.; Stoehr, Robert; Eckstein, Markus; Laible, Mark; Schlombs, Kornelia; Eidt, Sebastian; et al. (Urologia Internationalis, 2017)
Background/Aims/Objectives: It is difficult to identify patients with a non-muscle-invasive bladder cancer (NMIBC) at stage pT1 with concomitant carcinoma in situ (Cis) who will benefit from an early cystectomy.We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues of patients with NMIBC. Messenger ribonucleic acid (mRNA) expression of progesterone receptor (PGR), estrogen receptor (ESR1), ERBB2, and marker of proliferation Ki-67 (MKI67) was measured by single-step reverse transcription quantitative real-time polymerase chain reaction using RNA-specific TaqMan assays. Relative gene expression was determined by the normalization of 2 reference genes (CALM2, B2M) using the 40 ??CT method and relative gene expression was correlated to the histopathological stage and oncological outcome.Of 302 patients with pT1 NMIBC in the initial transurethral resection of the bladder, 65 had a concomitant Cis. Elevated ERBB2 expression (>40.1) significantly correlated with progress in patients with and without concomitant Cis (p = 0.020 and p = 0.049, respectively). For the subgroup of pT1 with concomitant Cis, elevated ERBB2 expression significantly discriminated between a high-risk group of 55% progression-free survival (PFS) and a low-risk group of 90% PFS after a 5-year follow-up (p = 0.020). Cox-regression analysis revealed ERBB2 expression as the only independent prognostic factor for PFS (p = 0.0037).High mRNA expression of ERBB2 can identify patients with pT1 NMIBC with concomitant Cis, who have a high risk of progression and might benefit from an early cystectomy.
EVALuna2:6879

Evaluation of Gas 6 as a Prognostic Marker in Papillary Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Urologia Internationalis, 2023)
Introduction: Growth arrest-specific protein 6 (Gas 6) is a ligand that plays a role in proliferation and migration of cells. For several tumor entities, high levels of Gas 6 are associated with poorer survival. We examined the prognostic role of Gas 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), which is still unclear. Methods: The patients' sample collection is a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Gas 6 was determined by immunohistochemistry. Results: In total, Gas 6 staining was evaluable in 180 of 240 type 1 and 110 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed no significant difference in 5-year overall survival for all pRCC nor either subtype. Also, Gas+ and Gas- groups did not significantly differ in any tumor or patient characteristics. Conclusion: Gas 6 was not found to be an independent prognostic marker in pRCC. Future studies are warranted to determine if Gas 6 plays a role as prognostic marker or therapeutic target in pRCC.
CRIS-Team Scopus Importer:2023-08-11

Evaluation of Potential Targeted Therapy and Molecular Subtype in Large Nested Variant of Urothelial Carcinoma (LNUC) - Weyerer, Veronika; Eckstein, Markus; Comperat, Eva; Juette, Hendrik; Gaisa, Nadine; Allory, Yves; Stoehr, Robert; Wullich, Bernd; Roupret, Morgan; Hartmann, Arndt; Bertz, Simone (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Exploring the MIR143-UPAR Axis for the Inhibition of Human Prostate Cancer Cells In Vitro and In Vivo - Wach, Sven; Brandl, Madeleine; Borchardt, Hannes; Weigelt, Katrin; Lukat, Sabine; Nolte, Elke; Al-Janabi, Omar; Hart, Martin; Grässer, Friedrich; Giedl, Josef; Jung, Rudolf; Stöhr, Robert; et al. (Molecular Therapy - Nucleic Acids, 2019)
MIR143 is pathologically downregulated and may function as a tumor suppressor in prostate cancer. Likewise, the urokinase plasminogen activator receptor (UPAR) is overexpressed in prostate carcinoma, representing a negative prognostic marker and putative therapeutic target gene. In this paper, we establish UPAR as a new direct target of MIR143. Luciferase reporter gene constructs identify one of the two in silico-predicted binding sites as functionally relevant for direct MIR143 binding to the 3′ UTR, and, concomitantly, transfection of MIR143 reduces UPAR protein levels in prostate carcinoma cells in vitro. Inhibitory effects on cell proliferation and colony formation, spheroid growth and integrity, and cell viability are extensively analyzed, and they are compared to direct small interfering RNA (siRNA)-mediated uPAR knockdown or combined microRNA (miRNA)-siRNA treatment. Switching to a therapeutically more relevant in vivo model, we demonstrate tumor-inhibitory effects of MIR143 replacement therapy by systemic treatment of mice bearing subcutaneous PC-3 tumor xenografts with MIR143 formulated in polymeric nanoparticles. This efficient, nanoparticle-mediated delivery of intact MIR143 mediates the marked downregulation of uPAR protein, but not mRNA levels, thus indicating translational inhibition rather than mRNA degradation. In summary, we identify UPAR as a direct target gene of MIR143, and we establish the therapeutic anti-tumor potential of nanoparticle-based MIR143 replacement in prostate cancer.
CRIS-Team Scopus Importer:2019-05-07
Keywords: MIR143; miRNA replacement; PEI nanoparticles; prostate cancer; urokinase plasminogen activator receptor; xenograft

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Expression of GP88 (progranulin) in serum of prostate cancer patients is associated with Gleason scores and overall survival - Greither, Thomas; Fischer, Kersten; Theil, Gerit; Marcou, Marios; Holzhausen, Hans-Juergen; Weigelt, Katrin; Serrero, Ginette; Hicks, David; Yue, Binbin; Fornara, Paolo; Wullich, Bernd; Taubert, Helge; et al. (Cancer Management and Research, 2018)
Background: GP88/Progranulin is a well-recognized cell growth promoter in different cancers, and elevated serum GP88 levels have been described as negative prognostic factor in breast cancer. However, serum levels in prostate cancer (PCa) patients have not yet been studied. Material and Methods: We analyzed serum GP88 levels by enzyme immunosorbent assay and correlated them with clinicopathological parameters in PCa patients. PCa patients were separated into two groups based on the serum GP88 median level (low <= 44.56 ng/mL or high >44.56 ng/mL) and according to their median age (younger <= 66 years or elder patients >66 years). Results: Low serum GP88 levels were more often detected in younger patients and high levels in elder patients (P=0.018; Fisher's exact test). PCa patients were separated into three groups, Gleason score (GS) <= 6; GS=7; and GS >= 8. In receiver operating characteristic analyses, we could distinguish GS <= 6 from GS=7 [area under the curve (AUC): 0.646; P=0.018] and GS <= 6 from GS >= 8 (AUC: 0.629; P=0.048) but not GS=7 from GS >= 8. For survival analysis, GP88 levels were separated into two groups by an optimized cutoff value of 36.92 ng/mL. Using this GP88 stratification, all PCa patients and younger patients with a low serum GP88 level had a significantly better overall survival compared with patients with higher serum GP88 levels (log-rank test P=0.010 and P=0.024). Conclusion: Serum GP88 levels are significantly different depending on age and GS, and they are associated with the prognosis of PCa patients.
EVALuna2:35896

Expression of GP88 (Progranulin) Protein Is an Independent Prognostic Factor in Prostate Cancer Patients - Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; et al. (Cancers, 2019)
Prostate cancer, the second most common cancer, is still a major cause of morbidity and mortality among men worldwide. The expression of the survival and proliferation factor progranulin (GP88) has not yet been comprehensively studied in PCa tumors. The aim of this study was to characterize GP88 protein expression in PCa by immunohistochemistry and to correlate the findings to the clinico-pathological data and prognosis. Immunohistochemical staining for GP88 was performed by TMA with samples from 442 PCa patients using an immunoreactive score (IRS). Altogether, 233 cases (52.7%) with negative GP88 staining (IRS < 2) and 209 cases (47.3%) with positive GP88 staining (IRS >= 2) were analyzed. A significant positive correlation was found for the GP88 IRS with the PSA value at prostatectomy and the cytoplasmic cytokeratin 20 IRS, whereas it was negatively associated with follow-up times. The association of GP88 staining with prognosis was further studied by survival analyses (Kaplan-Meier, univariate and multivariate Cox's regression analysis). Increased GP88 protein expression appeared as an independent prognostic factor for overall, disease-specific and relapse-free survival in all PCa patients. Interestingly, in the subgroup of younger PCa patients (<= 65 years), GP88 positivity was associated with a 3.8-fold (p = 0.004), a 6.0-fold (p = 0.008) and a 3.7-fold (p = 0.003) increased risk for death, disease-specific death and occurrence of a relapse, respectively. In the PCa subgroup with negative CK20 staining, GP88 positivity was associated with a 1.8-fold (p = 0.018) and a 2.8-fold increased risk for death and disease-specific death (p = 0.028). Altogether, GP88 protein positivity appears to be an independent prognostic factor for PCa patients.
CRIS-Team WoS Importer:2020-01-28

Expression of nectin-4 in papillary renal cell carcinoma - Zschabitz, Stefanie; Mikuteit, Marie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Discover Oncology, 2022)
Background: Nectin-4 contributes to tumor proliferation, lymphangiogenesis and angiogenesis in malignant tumors and is an emerging target in tumor therapy. In renal cell carcinoma (RCC) VEGF-directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. Enfortumab vedotin-ejf (EV) is an antibody drug conjugate that targets Nectin-4. The aim of our study was to investigate the expression of Nectin-4 in a large cohort of papillary RCC specimens. Patients and methods: Specimens were derived from the PANZAR consortium (Erlangen, Heidelberg, Herne, Homburg, Mainz, Mannheim, Marburg, Muenster, LMU Munich, TU Munich, and Regensburg). Clinical data and tissue samples from n = 190 and n = 107 patients with type 1 and 2 pRCC, respectively, were available. Expression of Nectin-4 was determined by immunohistochemistry (IHC). Results: In total, Nectin-4 staining was moderately or strongly positive in of 92 (48.4%) of type 1 and 39 (36.4%) type 2 of pRCC cases. No associations between Nectin-4 expression and age at diagnosis, gender, grading, and TNM stage was found. 5 year overall survival rate was not statistically different in patients with Nectin-4 negative versus Nectin-4 positive tumors for the overall cohort and the pRCC type 2 subgroup, but higher in patient with Nectin-4 positive pRCC type 1 tumors compared to Nectin-4 negative tumors (81.3% vs. 67.8%, p = 0.042). Conclusion: Nectin-4 could not be confirmed as a prognostic marker in pRCC in general. Due to its high abundance on pRCC specimens Nectin-4 is an interesting target for therapeutical approaches e.g. with EV. Clinical trials are warranted to elucidate its role in the pRCC treatment landscape.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Nectin 4; Papillary renal cell carcinoma

Expression of PD-1 and CTLA-4 Are Negative Prognostic Markers in Renal Cell Carcinoma - Kahlmeyer, Andreas; Stoehr, Christine; Hartmann, Arndt; Goebell, Peter; Wullich, Bernd; Wach, Sven; Taubert, Helge; Erlmeier, Franziska (Journal of Clinical Medicine, 2019)
Immuno-oncological therapy with checkpoint inhibition (CI) has become a new standard treatment in metastatic renal cell carcinoma (RCC), but the prognostic value of the expression of CI therapy target molecules is still controversial. 342 unselected consecutive RCC tumor samples were analyzed regarding their PD-1, PD-L1, and CTLA-4 expression by immunohistochemistry (IHC). The prognostic values for cancer-specific survival (CSS) and overall survival (OS) were analyzed for those not exposed to CI therapy. The expression of PD-1 in tumor-infiltrating mononuclear cells (TIMC) and PD-L1 in tumor cells was detected in 9.4% and 12.3%, respectively (Immune reactive score (IRS) > 0). Furthermore, PD-L1 expression in TIMC (IRS > 0) and CTLA-4 expression in TIMC (>1% positive cells) was detected in 4.8% and 6.3%. PD-1 expression and CTLA-4 expression were significantly associated with a worse OS and CSS in log rank survival analysis and univariate Cox regression analysis. CTLA-4 expression is a prognostic marker that is independently associated with a worse outcome in multivariate Cox regression analysis in the whole cohort (OS: p = 0.013; CSS: p = 0.048) as well as in a non-metastatic subgroup analysis (OS: p = 0.028; CSS: p = 0.022). Patients with combined CTLA-4 expression and PD-1-expression are at highest risk in OS and CSS. In RCC patients, PD-1 expression in TIMC and CTLA-4 expression in TIMC are associated with a worse OS and CSS. The combination of PD-1 expression in TIMC and CTLA-4 expression in TIMC might identify high risk patients. This is, to our knowledge, the first description of CTLA-4 expression to be a prognostic marker in RCC.
CRIS-Team WoS Importer:2019-06-25

Expression of Prostate-specific Membrane Antigen (PSMA) in Papillary Renal Cell Carcinoma - Overview and Report on a Large Multicenter Cohort - Zschaebitz, Stefanie; Erlmeier, Franziska; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Journal of Cancer, 2022)
Prostate specific membrane antigen (PSMA) is an emerging diagnostic and therapeutic target in prostate cancer. 68 Ga-PSMA-labeled hybrid imaging is used for the detection of prostate primary tumors and metastases. Therapeutic applications such as Lutetium-177 PSMA radionuclide therapy or bispecific antibodies that target PSMA are currently under investigation within clinical trials. The expression of PSMA, however, is not specific to prostate-tissue. It has been described in the neovascular endothelium of different types of cancer such as breast cancer, and clear cell renal cell carcinoma (ccRCC). The aim of this study was to analyze PSMA expression in papillary RCC (pRCC) type 1 and type 2, the most common non-ccRCC subtypes, and to evaluate the potential of PSMA-targeted imaging and treatment in pRCC. Formalin-fixed, paraffin-embedded tissue samples of primary tumors were analyzed for PSMA expression by immunohistochemistry. Out of n=374 pRCC specimens from the multicenter PANZAR consortium, n=197 pRCC type 1 and n=110 type 2 specimens were eligible for analysis and correlated with clinical data. In pRCC type 1 PSMA staining was positive in 4 of 197 (2.0%) samples whereas none (0/110) of the pRCC type 2 samples were positive for PSMA in this large cohort of pRCC patients. No significant PSMA expression was detected in pRCC. Reflecting current clinical evaluation of PMSA expression in RCC do not encourage further analysis in papillary subtypes.
CRIS-Team WoS Importer:2022-04-15
Keywords: prostate specific membrane antigen; papillary renal cell carcinoma; kidney cancer

Female Gender Is an Age-dependent Negative Prognostic Factor for Patients with Upper Tract Urothelial Carcinoma - Sikic, Danijel; Wach, Sven; Taubert, Helge; Richterstetter, Mario; Kunath, Frank; Goebell, Peter; Schick, Stefan; Olbert, Peter; Huber, Johannes; Wullich, Bernd; Keck, Bastian (Anticancer Research, 2015)
To analyze female gender as a possible age-dependent prognostic factor for overall (OS) and cancer-specific survival (CSS) in patients with upper urinary tract urothelial carcinoma (UUTUC) after radical nephroureterectomy (RNU).A total of 167 men and 101 women with UUTUC treated with RNU with bladder cuff resection at our clinic were retrospectively analyzed. Female patients were divided into pre- and post-menopausal groups and compared against male patients of the same age. We used a cut-off age of 59 years or more as a surrogate for the post-menopausal hormonal status of women. Kaplan-Meier analyses and multivariate Cox proportional hazards regression analyses were performed to analyze gender as a possible prognostic factor of OS and CSS.Women aged 59 years or more had a significantly worse CSS with an average of 231 months after RNU compared to 303 months for their male counterparts (p=0.011). Univariate Cox regression analysis showed a 2.44-fold higher risk of death (p=0.013), while multivariate analyses, adjusted for tumor stage and tumor grade, showed a 2.92-fold higher risk (p=0.011) of cancer-specific death for women aged 59 years or more.Female gender is an age-dependent prognostic factor for CSS for patients with UUTUC treated with RNU.
EVALuna2:16326

FGFR3 Mutation Status and FGFR3 Expression in a Large Bladder Cancer Cohort Treated by Radical Cystectomy: Implications for Anti-FGFR3 Treatment? - van Rhijn, Bas W.G.; Mertens, Laura S.; Mayr, Roman; Bostrom, Peter J.; Real, Francisco X.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (European Urology, 2020)
Oncogenic fibroblast growth factor receptor 3 (FGFR3) mutations were associated with favorable bladder cancer in a series of 1000 radical cystectomy cases. Moreover, patients with FGFR3 mutant tumors would be more likely to benefit from anti-FGFR3 therapy than patients with overexpression only.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Bladder; Cancer; Cystectomy; Expression; FGFR3; Mutation; Urothelial carcinoma

First Experience With SPECT/CT Using a 99mTc-Labeled Inhibitor for Prostate-Specific Membrane Antigen in Patients With Biochemical Recurrence of Prostate Cancer - Reinfelder, Julia; Kuwert, Torsten; Beck, Michael; Sanders, James C.; Ritt, Philipp; Schmidkonz, Christian; Hennig, Peter; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter (Clinical Nuclear Medicine, 2017)
Prostate-specific membrane antigen (PSMA) is overexpressed in most prostate cancers (PCs). Here, we report our first experience using the Tc-labeled PSMA inhibitor MIP-1404 (Progenics Pharmaceuticals, Inc, Tarrytown, NY) in 60 patients with biochemically recurrent PC.Whole-body planar scintigraphy and SPECT/CT of the lower abdominal pelvic region of 60 patients with biochemical relapse of PC were analyzed retrospectively. In these subjects, an average dose of 733.1 ± 49.5 MBq (19.8 ± 1.3 mCi) Tc-labeled MIP-1404 was injected 4 to 5 hours prior to imaging. In addition to visual evaluation, SUVmax were determined in the tumor lesions using a previously developed protocol for quantitative SPECT/CT.In 42 of 60 patients, Tc-MIP-1404-positive lesions could be detected (70%; 95% confidence interval [CI], 0.58-0.82). Twenty patients had Tc-MIP-1404-positive lymph nodes suggestive of metastasis, 14 patients had pathological uptake in the prostate region indicative of local recurrence, and for another 19 patients, there was tracer accumulation in the skeleton (n = 18) or lungs (n = 1). Detection rate was 91.4% (95% CI, 0.82-1) at prostate-specific antigen levels greater than 2 ng/mL and 40.0% (95% CI, 0.21-0.59) at lower prostate-specific antigen values (P < 0.01). Of the 60 patients, in total, 82 positive lesions were analyzed quantitatively. Average SUVmax of the lesions was 16.3 ± 21.6 with a range of 1.7 to 142.9.Tc-labeled PSMA inhibitor MIP-1404 is a promising SPECT tracer for detection of locally recurrent or metastatic prostate cancer.
EVALuna2:13859

FOXA1 Gene Expression for Defining Molecular Subtypes of Muscle-Invasive Bladder Cancer after Radical Cystectomy - Sikic, Danijel; Eckstein, Markus; Wirtz, Ralph M.; Jarczyk, Jonas; Worst, Thomas S.; Porubsky, Stefan; Keck, Bastian; Kunath, Frank; Weyerer, Veronika; Breyer, Johannes; Otto, Wolfgang; Rinaldetti, Sebastien; et al. (Journal of Clinical Medicine, 2020)
It remains unclear how to implement the recently revealed basal and luminal subtypes of muscle-invasive bladder cancer (MIBC) into daily clinical routine and whether molecular marker panels can be reduced. The mRNA expression of basal (KRT5) and luminal (FOXA1, GATA3, KRT20) markers was measured by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) and correlated to clinicopathological features, recurrence-free survival (RFS), disease-free survival (DFS), and overall survival (OS) in 80 patients with MIBC who underwent radical cystectomy. Additionally, the correlation of single markers with the basal and non-basal subtypes defined by a 36-gene panel was examined and then validated in the TCGA (The Cancer Genome Atlas) cohort. High expression of FOXA1 (p = 0.0048) and KRT20 (p = 0.0317) was associated with reduced RFS. In the multivariable analysis, only FOXA1 remained an independent prognostic marker for DFS (p = 0.0333) and RFS (p = 0.0310). FOXA1 expression (AUC = 0.79; p = 0.0007) was closest to the combined marker expression (AUC = 0.79; p = 0.0015) in resembling the non-basal subtype defined by the 36-gene panel. FOXA1 in combination with KRT5 may be used to distinguish the basal and non-basal subtypes of MIBC.
CRIS-Team WoS Importer:2020-05-26

Frequency of microsatellite instability (MSI) in upper tract urothelial carcinoma: comparison of the Bethesda panel and the Idylla MSI assay in a consecutively collected, multi-institutional cohort - Kullmann, Friederike; Strissel, Pamela; Strick, Reiner; Stöhr, Robert; Eckstein, Markus; Bertz, Simone; Wullich, Bernd; Sikic, Danijel; Wach, Sven; Taubert, Helge; Olbert, Peter; Heers, Hendrik; et al. (Journal of Clinical Pathology, 2021)
Aims Upper tract urothelial carcinoma (UTUC) is a rare malignancy with a poor prognosis which occurs sporadically or in few cases results from a genetic disorder called Lynch syndrome. Recently, examination of microsatellite instability (MSI) has gained importance as a biomarker: MSI tumours are associated with a better response to immunomodulative therapies. Limited data are known about the prevalence of MSI in UTUC. New detection methods using the fully automated Idylla MSI Assay facilitate analysis of increased patient numbers. Methods We investigated the frequency of MSI in a multi-institutional cohort of 243 consecutively collected UTUC samples using standard methodology (Bethesda panel), along with immunohistochemistry of mismatch repair (MMR) proteins. The same tumour cohort was retested using the Idylla MSI Assay by Biocartis. Results Using standard methodology, 230/243 tumours were detected as microsatellite stable (MSS), 4/243 tumours as MSI and 9/243 samples as invalid. In comparison, the Idylla MSI Assay identified four additional tumours as MSS, equalling 234/243 tumours; 4/243 were classified as MSI and only 5/243 cases as invalid. At the immunohistochemical level, MSI results were supported in all available cases with a loss in MMR proteins. The overall concordance between the standard and the Idylla MSI Assay was 98.35%. Time to result differed between 3 hours for Idylla MSI Assay and 2 days with the standard methodology. Conclusion Our data indicate a low incidence rate of MSI tumours in patients with UTUC. Furthermore, our findings highlight that Idylla MSI Assay can be applied as an alternative method of MSI analysis for UTUC.
CRIS-Team WoS Importer:2021-12-10

Frequency of TERT Promoter Mutations in Prostate Cancer - Stoehr, Robert; Taubert, Helge; Zinnall, Ulrike; Giedl, Josef; Gaisa, Nadine T.; Burger, Maximilian; Ruemmele, Petra; Hurst, Carolyn D.; Knowles, Margaret A.; Wullich, Bernd; Hartmann, Arndt (Pathobiology, 2015)
Recently, recurrent mutations within the core promoter of the human telomerase reverse transcriptase (TERT) gene generating consensus binding sites for ETS transcription factor family members were described in melanomas and other malignancies (e.g. bladder cancer, hepatocellular carcinoma). These mutations were discussed as early drivers for malignant transformation. In prostate cancer (PrCa) TERT expression has been associated with a poor prognosis and higher risk for disease recurrence. The underlying mechanisms for high TERT expression in PrCa have still not been clarified. To date, data on TERT promoter mutation analysis in PrCa are sparse. Therefore, we performed sequence analysis of the core promoter region of the TERT gene in an unselected cohort of prostate tumors.Sections from 167 formalin-fixed, paraffin-embedded and cryopreserved prostate tumors were microdissected and used for DNA isolation. The mutation hotspot region within the TERT core promoter (-260 to +60) was analyzed by direct Sanger sequencing or SNaPshot analysis.All cases were analyzed successfully. Mutations within the core promoter of the TERT gene were not detected in any of the cases with all tumors exhibiting a wild-type sequence.TERT core promoter mutations reported from several other malignancies were not detected in our unselected cohort of PrCa. These data indicate that alterations within the core promoter of the TERT gene do not play an important role in prostate carcinogenesis. © 2015 S. Karger AG, Basel.
EVALuna2:6706

Functional analyses and prognostic significance of SFRP1 expression in bladder cancer - Rogler, Anja; Kendziorra, Emil; Giedl, Josef; Stoehr, Christine; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; Stoehr, Robert (Journal of Cancer Research and Clinical Oncology, 2015)
We previously showed that the Wnt-signaling antagonist SFRP1 (secreted frizzled-related protein 1) is a promising marker in bladder cancer. The aim of this study was to validate the prognostic role and analyze the functional significance of SFRP1.Four bladder cancer cell lines (RT112, RT4, J82 and BFTC905) and one urothelial cell line (UROtsa) were used for functional characterization of SFRP1 expression. Effects on viability, proliferation and wound healing were investigated, and canonical Wnt-pathway activity as well as Wnt-signaling target gene expression was analyzed. Additionally, tissue micro-arrays from two different bladder tumor cohorts were evaluated for SFRP1 expression, and associations with survival and histopathological parameters were analyzed.The cell lines RT112, RT4, J82 and UROtsa showed SFRP1 expression. In BFTC905, SFRP1 expression was inhibited by promoter hypermethylation. Wnt-pathway activity was absent in all cell lines and independent from SFRP1 expression. RT112 and BFTC905 were used for further functional characterization. SFRP1 overexpression resulted in decreased viability and migration in BFTC905 cells. Knockdown of SFRP1 expression in RT112 cells resulted only in marginal effects. In bladder tumors, SFRP1 expression was associated with lower tumor grade, but not with progression in patients with papillary bladder cancer. SFRP1 expressing papillary bladder cancer tumors also demonstrated a tendency to longer overall survival.SFRP1 is reducing malignant potential of BFTC905 cells, but not by regulation of canonical Wnt-signaling pathway. Other pathways, like non-canonical Wnt or the MAPK pathway, could be activated via SFRP1-expression loss. In bladder tumors, SFRP1 has the potential to predict outcome for a subset of papillary bladder tumors.
EVALuna2:6533

Geriatric Assessments Can Predict Functional Outcome and Mortality after Urological Tumor Surgery - Kahlmeyer, Andreas; Fiebig, Christian; Müller, Marco; Kraulich, Matthias; Brendel-Suchanek, Jonas; Kunath, Frank; Wach, Sven; Goebell, Peter; Ritt, Martin; Gaßmann, Karl-Günter; Wullich, Bernd (Urologia Internationalis, 2021)
Introduction: Older patients undergoing major urological tumor surgery are at severe risk of functional deterioration, complications, and mortality. We prospectively evaluated geriatric assessment tools and developed a novel easy-to-use assessment tool for clinical use. Methods: In 159 patients, geriatric assessment tools were used prior to cystectomy, prostatectomy, and renal tumor surgery, and their peri- and postoperative courses were recorded. Using all the tests, a short and easy-to-use assessment tool was developed, and nomograms were generated to predict functional outcomes and mortality. Results: Of all the patients, 13.8% underwent radical cystectomy, 37.7% underwent radical prostatectomy, and 48.4% underwent tumor surgery of the kidney at the age of 70 years or older. The average age was 75.6 years. Incomplete functional recovery at day 30 and day 180 was observed in 37.7% and 36.1% of the patients, respectively, and incomplete functional recovery was associated with impaired mobility, previous care dependency, frailty, comorbidities, and a high ASA score. The only predictor for high-grade complications was comorbidities, whereas mortality was associated with the geriatric screening tool scores, impaired mobility, preoperative care dependency, and comorbidities. The Erlangen Index (EI), a combination of the selected assessment tools, showed a good prediction of early (p = 0.002) and medium-term (p = 0.002) functional outcomes and mortality (p = 0.001). Conclusion: Our prospective evaluation confirms the high risk of incomplete functional recovery, high-grade complications, and mortality in older patients undergoing major urological tumor surgery. The EI is an easy-to-use preoperative assessment tool and therefore should be used in preoperative patient counseling.
CRIS-Team WoS Importer:2021-10-01

Geriatric Urology - Kahlmeyer, A.; Wullich, Bernd; Wiedemann, A. (Urologe, 2018)
EVALuna2:35889

Geriatric urology (Geriatrische Urologie) - Wullich, Bernd; Wiedemann, Andreas (Urologe, 2019)
CRIS-Team Scopus Importer:2019-05-02

Geriatrisches Assessment – Was sollte vor Therapiebeginn des mHSPC und des mCRPC gemacht und bedacht werden? - Heers, Hendrik; Butea-Bocu, Marius Cristian; Groeben, Christer; Huber, Johannes; Wullich, Bernd; Goebell, Peter; Fiebig, Christian (Aktuelle Urologie, 2023)
The systemic treatment of prostate cancer nowadays is predominantly carried out with combination therapies. A range of aspects should be respected in older and comorbid patients, in order to avoid toxicities and to achieve a successful therapy alongside good quality of life. The definition of geriatric patients is not primarily based on chronological age but rather on the overall health condition and life expectancy. Comorbid patients > 70 years should undergo a three-step geriatric screening before treatment initiation. If the G8 screening and/or mini-COG shows abnormalities (taking into account nutrition, comorbidity/medication, mobility, and cognition), a simplified geriatric assessment is recommended. Patients can then be stratified into three groups (fit, vulnerable, frail). Only a few cases warrant a complete geriatric assessment. Treatable deficits in the above mentioned domains should be improved if possible. When choosing a systemic therapy, fit patients can be treated the same as non-geriatric patients. Vulnerable and frail patients are under a higher risk for toxicities, so special care should be taken. While the diverse substances of hormonal therapy are usually well tolerated (even though some substance-specific toxicities can occur), haematotoxic substances such as taxanes or olaparib can only be recommended in select cases. As falls - especially under hormonal therapy - are a common problem, osteoprotective therapy should especially be considered. Upon progression of the tumour disease, there should not be a reflex to simply switch to the next line of treatment, but an individual concept should be established together with the patient and his relatives, taking into account aspects of palliative care and patient needs and focussing on quality of life and also setting therapy limitations.
CRIS-Team Scopus Importer:2023-10-13
Keywords: chemotherapy; geriatrics; hormonal therapy; personalised medicine; prostate cancer

Gonadotropin-releasing hormone antagonists versus standard androgen suppression therapy for advanced prostate cancer A systematic review with meta-analysis - Kunath, Frank; Borgmann, Hendrik; Bluemle, Anette; Keck, Bastian; Wullich, Bernd; Schmucker, Christine; Sikic, Danijel; Roelle, Catharina; Schmidt, Stefanie; Wahba, Amr; Meerpohl, Joerg J. (BMJ Open, 2015)
To evaluate efficacy and safety of gonadotropin-releasing hormone (GnRH) antagonists compared to standard androgen suppression therapy for advanced prostate cancer.The international review team included methodologists of the German Cochrane Centre and clinical experts.We searched CENTRAL, MEDLINE, Web of Science, EMBASE, trial registries and conference books for randomised controlled trials (RCT) for effectiveness data analysis, and randomised or non-randomised controlled studies (non-RCT) for safety data analysis (March 2015). Two authors independently screened identified articles, extracted data, evaluated risk of bias and rated quality of evidence according to GRADE.13 studies (10 RCTs, 3 non-RCTs) were included. No study reported cancer-specific survival or clinical progression. There were no differences in overall mortality (RR 1.35, 95% CI 0.63 to 2.93), treatment failure (RR 0.91, 95% CI 0.70 to 1.17) or prostate-specific antigen progression (RR 0.83, 95% CI 0.64 to 1.06). While there was no difference in quality of life related to urinary symptoms, improved quality of life regarding prostate symptoms, measured with the International Prostate Symptom Score (IPSS), with the use of GnRH antagonists compared with the use of standard androgen suppression therapy (mean score difference -0.40, 95% CI -0.94 to 0.14, and -1.84, 95% CI -3.00 to -0.69, respectively) was found. Quality of evidence for all assessed outcomes was rated low according to GRADE. The risk for injection-site events was increased, but cardiovascular events may occur less often by using GnRH antagonist. Available evidence is hampered by risk of bias, selective reporting and limited follow-up.There is currently insufficient evidence to make firm conclusive statements on the efficacy of GnRH antagonist compared to standard androgen suppression therapy for advanced prostate cancer. There is need for further high-quality research on GnRH antagonists with long-term follow-up.CRD42012002751.
EVALuna2:16325

Hepatocyte differentiation markers in adenocarcinoma of the prostate: hepatocyte paraffin 1 but not arginase-1 is specifically expressed in a subset of prostatic adenocarcinoma - Giedl, Josef; Buettner-Herold, Maike; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Human Pathology, 2016)
Prostate adenocarcinoma and hepatocellular carcinoma (HCC) are common cancer types. Both may present with bone metastases, and both are known to be CK7/CK20 negative. Thus, diagnosis of less well-differentiated tumors at metastatic sites essentially relies on immunohistochemical confirmation. However, insufficient data exist on the expression status of the main 2 hepatocyte markers hepatocyte paraffin 1 (HepPar-1) and arginase-1 (Arg-1) in prostatic adenocarcinoma. We screened 557 prostate carcinoma cases for expression of these 2 markers using tissue microarrays. Sixty-four of 557 (11.5%) cases showed highly variable expression of HepPar-1 in 1% to 75% of tumor cells with a characteristically strong granular "mitochondrial" pattern. Only 13 cases (2.3%) expressed HepPar-1 in greater than 10% of the tumor cells. No correlation was seen with Gleason grade. On the other hand, 19 (3.4%) of 557 cases showed variable nonspecific cytoplasmic expression of Arg-1 distinct from the specific combined nucleocytoplasmic staining seen in normal liver and in HCC. Specifically, this Arg-1 pattern was seen only using one antibody lot and not another suggesting cross-reactivity. Only a single case showed specific nucleocytoplasmic expression of Arg-1 in the tumor cells. In conclusion, specific granular cytoplasmic staining for HepPar-1 is frequent in prostatic adenocarcinomas (11.5%) but usually focal and limited to less than 5% of tumor cells. This should not be misinterpreted as evidence of HCC, particularly in solid-pattern neoplasms. On the other hand, specific Arg-1 expression is very rare (0.18%), highlighting the value of Arg-1 in distinguishing HepPar-1-positive prostatic carcinoma from HCC at metastatic sites or in cases of liver metastasis from prostate carcinoma.
EVALuna2:6774

Heterogeneity-analysis of molecular subtypes of muscle-invasive bladder cancer and their precursor lesions in multiregion mapped whole-organ bladders - Weyerer, Veronika; Lange, Fabienne; Wullweber, Adrian; Stöhr, Robert; Bertz, Simone; Wach, S.; Taubert, Helge; Wullich, Bernd; Sikic, Danijel; Strissel, Pamela; Strick, Reiner; Hartmann, Arndt; et al. (UROLOGIC ONCOLOGY-SEMINARS AND ORIGINAL INVESTIGATIONS, 2020)
CRIS-Team WoS Importer:2021-01-15

High androgen receptor mrna expression is associated with improved outcome in patients with high-risk non-muscle-invasive bladder cancer - Sikic, Danijel; Taubert, Helge; Wirtz, Ralph M.; Breyer, Johannes; Eckstein, Markus; Weyerer, Veronika; Kubon, Jennifer; Erben, Philipp; Bolenz, Christian; Burger, Maximilian; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2021)
The role of the androgen receptor (AR) in non-muscle-invasive bladder cancer (NMIBC) remains controversial. We retrospectively analyzed the mRNA expression of AR using RT-qPCR in 95 patients with high-risk NMIBC treated with a bladder-sparing approach and correlated AR with clinical data and recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS). The mRNA expression of AR and KRT5, i.e., the basal-like subtype, was strongly correlated (rs = 0.456; p < 0.001). AR (p = 0.053) and KRT5 (p = 0.029) mRNA expression was negatively correlated with tumor grade. Kaplan–Meier analyses indicated significantly prolonged CSS (p = 0.020) and OS (p = 0.015) and a trend towards longer RFS (p = 0.051) in patients with high AR expression. High KRT5 expression was associated with significantly longer RFS (p = 0.033), CSS (p = 0.029) and OS (p = 0.030), while high KRT20 expression was associated with reduced RFS (p = 0.042). In multivariable analysis, none of the molecular markers was an independent prognostic factor. When performing a substratification with regard to molecular markers and clinicopathological parameters, high AR expression showed improved OS in patients with high KRT20 mRNA expression (p = 0.041). Women showed significantly longer OS in cases with high AR expression (p = 0.011). High AR was associated with significantly improved CSS in males (p = 0.044) and patients with instillation therapy (p = 0.040), while OS was improved regardless of instillation therapy. Younger patients with high AR expression had significantly improved RFS (p = 0.021), CSS (p = 0.014) and OS (p = 0.007). RFS was also improved in patients with high AR and low expression of either KRT5 (p = 0.003) or KRT20 (p = 0.014), but not in patients with high expression of KRT5 or KRT20. In conclusion, high AR mRNA expression is correlated with KRT5 mRNA expression and is associated with an improved outcome in high-risk NMIBC.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Androgen receptor; Bladder cancer; KRT20; KRT5; MRNA; NMIBC; PCR

High Androgen Receptor mRNA Expression Is Independently Associated with Prolonged Cancer-Specific and Recurrence-Free Survival in Stage T1 Bladder Cancer - Sikic, Danijel; Breyer, Johannes; Hartmann, Arndt; Burger, Maximilian; Erben, Philipp; Denzinger, Stefan; Eckstein, Markus; Stohr, Robert; Wach, Sven; Wullich, Bernd; Keck, Bastian; Wirtz, Ralph M.; et al. (Translational Oncology, 2017)
High-risk non-muscle-invasive bladder cancer (NMIBC) remains challenging given the high probability of progression. Given that the androgen receptor (AR) has been discussed as a possible factor in the development and progression of bladder cancer, we investigated the predictive value of AR in stage pT1 NMIBC.We retrospectively analyzed the clinical data and AR mRNA expression in 296 patients with stage pT1 NMIBC who underwent a transurethral resection of the bladder. The mRNA expression of the AR transcript variants 1 (AR1) and 2 (AR2) was measured by reverse transcription quantitative real-time polymerase chain reaction. AR expression was also correlated to KRT5 and KRT20 mRNA expression.Kaplan-Meier analysis indicated that high AR1 mRNA expression >=35.47 is associated with statistically significant better recurrence-free survival (RFS) (P=.0007), progression-free survival (PFS) (P=.0420), and cancer-specific survival (CSS) (P=.0050). Multivariate Cox regression analysis revealed that high AR1 mRNA expression is an independent prognostic marker for RFS (P=.0029) and CSS (P=.0119). Spearman rank correlation revealed a significant positive association between mRNA expression of AR1 and KRT5 (rs: 0.3171, P<.0001) as well as a negative association with multifocal tumors (rs: 0.1478, P<.0109). No association was noted between AR1 expression and tumor grade, concomitant CIS, gender, tumor size, and KRT20 in patients with stage T1 NMIBC.AR mRNA expression can predict RFS and CSS in patients with stage T1 NMIBC. Further studies are necessary to refine the relevance of AR mRNA expression compared with immunohistochemically detectable AR expression.
EVALuna2:6884

High coexpression of CCL2 and CX3CL1 is gender-specifically associated with good prognosis in soft tissue sarcoma patients - Kehlen, Astrid; Greither, Thomas; Wach, Sven; Nolte, Elke; Kappler, Matthias; Bache, Matthias; Holzhausen, Hans-Juergen; Lautenschlaeger, Christine; Goebel, Steffen; Wuerl, Peter; Immel, Uta-Dorothee; Agaimy, Abbas; et al. (International Journal of Cancer, 2014)
Chemokines are involved in both the negative and positive regulation of inflammatory processes, angiogenesis and cancer/cancer stem cell proliferation as well as the chemoattraction of tumor cells to metastatic sites. The aim of this study was to measure the mRNA expression levels of three chemokines, CCL2, CCL7 and CX3CL1, in soft tissue sarcomas (STSs) and to assess the correlations between these levels as well as their correlations with clinicopathological data and the disease-specific survival of STS patients. The mRNA levels of CCL2, CCL7 and CX3CL1 were analyzed in tumor tissues from 126 STS patients using qPCR. Low mRNA expression of CCL2 and CX3CL1 was significantly correlated with a worse prognosis (RR = 1.98; p = 0.019 and RR = 2.10; p = 0.014; multivariate Cox's regression analysis). A combined low expression of CCL2 and CX3CL1 was associated with a significantly increased risk of tumor-related death as compared to patients with high expression levels of both chemokines (RR = 3.08; p = 0.003). A gender-specific multivariate analysis revealed that female STS patients with low CX3CL1 mRNA expression had a 3.46-fold increased risk of death (p = 0.004). Low expression of both CCL2 and CX3CL1 mRNAs resulted in an additive 5.37-fold increased risk of tumor-related death (p = 0.003) as compared to those with high expression of both parameters in female patients. In conclusion, this is the first study to show a significant correlation between combined low expression of CCL2 and CX3CL1 and a poor prognosis for STS patients, particularly in female patients.
EVALuna2:6682

High expression of ERBB2 is an independent risk factor for reduced recurrence-free survival in patients with stage T1 non-muscle-invasive bladder cancer - Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Kubon, Jennifer; Breyer, Johannes; Roghmann, Florian; Kunath, Frank; Keck, Bastian; Erben, Philipp; Hartmann, Arndt; Wirtz, Ralph M.; Wullich, Bernd; et al. (Urologic Oncology-Seminars and Original Investigations, 2021)
Introduction: Molecular markers associated with breast cancer are assumed to be associated with outcome in non-muscle-invasive bladder cancer (NMIBC). Materials and methods: We retrospectively investigated the association of the mRNA expression of estrogen receptor 1 (ESR1) and 2 (ESR2), progesterone receptor (PGR), MKI67, and HER2 (ERBB2) with recurrence-free (RFS), cancer-specific (CSS), and overall survival (OS) in 80 patients with stage T1 NMIBC. Results: High expression of ESR2 (P = 0.003), ERBB2 (P < 0.001), and MKI67 (P = 0.029) was associated with shorter RFS. Only high ERBB2 was an independent prognostic factor for reduced RFS (HR = 2.98; P = 0.009). When sub stratifying the cohort, high ESR2 was associated with reduced RFS (P < 0.001), CSS (P = 0.037) and OS (P = 0.006) in patients without instillation therapy. High ESR2 was associated with reduced CSS (P = 0.018) and OS (P = 0.029) in females and with shorter RFS in both sexes (males: P = 0.035; females: P = 0.010). Patients with high ERBB2 showed reduced CSS (P = 0.011) and OS (P = 0.042) in females and reduced CSS (P = 0.012) in those without instillation, while RFS was significantly reduced irrespective of sex or instillation. Conclusion: High mRNA expression of ERBB2 is an independent predictor of reduced RFS in patients with stage T1 NMIBC. High ERBB2 and ESR2 are associated with reduced outcomes, especially in females and patients without instillation therapy.
CRIS-Team Scopus Importer:2021-08-06
Keywords: ERBB2; Estrogen receptor; HER2; Non-muscle-invasive bladder cancer; Urothelial carcinoma

High interobserver variability of PTEN immunohistochemistry defining PTEN status in low- to intermediate-risk prostate cancer: results of the first German ring trial - Hommerding, Oliver; Bernhardt, Marit; Kreft, Tobias; Scherping, Anna; Abbas, Mahmoud; Baretton, Gustavo; Bräsen, Jan Hinrich; Breyer, Johannes; Darr, Christopher; Dressler, Franz Friedrich; Ellinger, Jörg; Erber, Ramona; et al. (Virchows Archiv, 2024)
The prognostication of individual disease trajectory and selection of optimal therapy in patients with localized, low-grade prostate cancer often presents significant difficulty. The phosphatase and tensin homolog on chromosome 10 (PTEN) has emerged as a potential novel biomarker in this clinical context, based on its demonstrated prognostic significance in multiple retrospective studies. Incorporation into standard clinical practice necessitates exceptional diagnostic accuracy, and PTEN’s binary readout—retention or loss—suggests its suitability as a biomarker. This multi-institutional ring trial aimed to validate the diagnostic precision of PTEN immunohistochemistry in localized, low- to intermediate-risk prostate cancer, across ten university pathology institutes in Germany. The trial incorporated 90 cases of patients diagnosed with acinar adenocarcinoma of the prostate of grade groups 1 (n = 8, 8.9%) and 2 (n = 82, 91.1%) post-radical prostatectomy. Remarkably, the interpretation of PTEN immunohistochemistry displayed substantial variation (12.5–51.2% PTEN loss rates) within an identical cohort of prostate cancer. Fluorescence in situ hybridization analysis demonstrated PTEN hemizygous deletions in 5.5% (5/90) of cases. All cases with hemizygous deletions presented a distinct loss of PTEN expression by immunohistochemistry and were unanimously identified as PTEN loss by all participants (sensitivity 100%). However, negative (loss) immunohistochemistry was relatively non-specific for an underlying genomic deletion. Improved inter-observer agreement was observed in a subsequent ring trial. Finally, we identify S473-pAKT immunohistochemistry as a useful marker in equivocal cases. In summary, this multi-institutional ring trial illustrates surprisingly heterogeneous outcomes in defining PTEN status by immunohistochemistry.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Active surveillance; AKT; Prognostic biomarker; Prostate cancer; PTEN

High proliferation rate and TNM stage but not histomorphological subtype are independent prognostic markers for overall survival in papillary renal cell carcinoma - Polifka, Iris; Agaimy, Abbas; Herrmann, Edwin; Spath, Verena; Trojan, Lutz; Stoeckle, Michael; Becker, Frank; Stroebel, Philipp; Muelfing, Christian; Schrader, Andres J.; Barth, Peter; Staehler, Michael; et al. (Human Pathology, 2019)
Papillary renal cell carcinoma (PRCC) is currently divided in 2 subtypes. We reviewed a large cohort of PRCC and correlated subtype, morphological features and diagnostic marker expression with overall survival (OS) to uncover differences between the 2 subtypes. Three hundred seventy-six renal tumors initially diagnosed as PRCC with clinical and survival data were collected from the participating centers. Two hundred forty-six tumors were classified as PRCC1 (65.4%) and 130 as PRCC2 (34.6%) and graded according to the 2016 World Health Organization/Intemational Society of Urological Pathology grading system. Morphological features (abundant cytoplasm, necrosis, fibrous stroma, foamy macrophages and psammoma bodies) were noted. Immunohistochemical stains (MIB1, p53, Racemase, EMA, CK7, CK20, E-Cadherin) were performed using tissue microarrays. chi(2)-Tests, log-rank tests and uni- and multivariate Cox regression analysis were performed. Both subtypes displayed different morphological features and immunohistochemical profiles: abundant cytoplasm was more frequent in PRCC2, while foamy macrophages were more common in PRCC1. Abundant cytoplasm and presence of psammoma bodies were associated with poorer OS. PRCC1 showed more frequent CK7 expression, PRCC2 more frequent E-Cadherin, p53 and higher MIB1 expression (>15%). Expression of Racemase and CK7 was associated with better OS, while high MIB1 (>15%) was associated with poorer OS. In multivariate analysis, the only independent predictors of OS were proliferation (MIB1), tumor stage, metastasis and age at surgery. Subtype was not an independent prognostic factor. Therefore, PRCC subtype on its own is not suitable for estimating survival. More data focusing on PRCC tumor biology is needed to define prognostic subgroups, especially in PRCC2. (C) 2018 Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2019-03-06

HLA-E expression and its clinical relevance in human renal cell carcinoma - Seliger, Barbara; Jasinski-Bergner, Simon; Quandt, Dagmar; Stoehr, Christine; Bukur, Juergen; Wach, Sven; Legal, Wolfgang; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt (Oncotarget, 2016)
The non-classical human leukocyte antigen E (HLA-E) expression is frequently overexpressed in tumor diseases, transplants and virus-infected cells and represents an immunomodulatory molecule by binding to the receptors CD94/NKG2A, -B and -C on NK and T cells. Due to its immune suppressive features HLA-E expression might represent an important mechanism of tumors to escape immune surveillance. While an aberrant expression of the non-classical HLA-G antigen in human renal cell carcinoma (RCC) has been demonstrated to be associated with a worse outcome of patients and reduced sensitivity to immune effector cell-mediated cytotoxicity, the expression and function of HLA-E has not yet been analyzed in this tumor entity. Higher levels of HLA-E transcripts were detected in all RCC cell lines and tumor lesions, which were tested in comparison to normal kidney epithelium. Immunohistochemical staining of a tissue microarray (TMA) using the HLA-E-specific monoclonal antibody TFL-033 recognizing the cytoplasmic HLA-E ?-chain as monomer revealed a heterogeneous HLA-E expression in RCC lesions with the highest frequency in chromophobe RCC when compared to other RCC subtypes. HLA-E expression did not correlate with the frequency of CD3+, CD4+, CD8+ and FoxP3+ immune cell infiltrations, but showed an inverse correlation with infiltrating CD56+ cells. In contrast to HLA-G, HLA-E expression in RCCs was not statistically significant associated with a decreased disease specific survival. These data suggest that HLA-E overexpression frequently occurs in RCC and correlates with reduced immunogenicity.
EVALuna2:6816

HLA-G expression associates with immune evasion muscle-invasive urothelial cancer and drives prognostic relevance - Branz, Annalena; Matek, Christian; Lange, Fabienne; Bahlinger, Veronika; Klümper, Niklas; Hölzel, Michael; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Wach, Sven; Taubert, Helge; Wullich, Bernd; et al. (Frontiers in Immunology, 2024)
Introduction: Urothelial bladder cancer is frequent and exhibits diverse prognoses influenced by molecular subtypes, urothelial subtype histology, and immune microenvironments. HLA-G, known for immune regulation, displays significant membranous expression in tumor tissues. Methods: We studied the protein expression of Human Leucocyte Antigen G (HLA-G) in 241 Muscle-Invasive Bladder Cancer (MIBC) patients, elucidating its potential clinical and biological significance. Protein expression levels were evaluated and correlated with molecular subtypes, histological characteristics, immune microenvironment markers, and survival outcomes. Results: High HLA-G expression associates with poor overall survival (OS) and diseasespecific survival (DSS), independent of clinicopathological parameters. HLA-G expression varies among molecular subtypes and Urothelial Subtype Histology, e.g., elevated expression levels in basal/squamous MIBC and those with sarcomatoid differentiation. Notably, HLA-G is increased in MIBC with an immune evasive microenvironment (high PD-L1 tumor cell expression, NK cell depletion, granzyme B (GZMB)/CD8 ratio reduction, MHC class I (MHCI) expression reduction) that are characterized by immunosuppressive features and poor prognosis. Furthermore, HLA-G correlates with elevated levels of other immune checkpoint proteins (TIGIT, LAG3, CTLA-4), indicating its role in immune evasion. Discussion: Our findings underscore HLA-G’s role as a potential prognostic marker and interesting immunotherapeutic target in MIBC. Its impact on immune evasion mechanisms and broad expression, coupled with associations withpoor survival and distinct tumor phenotypes, positions HLA-G as a promising protein for further exploration in developing targeted immunotherapies for MIBC patients.
CRIS-Team Scopus Importer:2024-11-15
Keywords: HLA-G; immune checkpoints; immune evasion; immune microenvironment; urothelial cancer

Homozygous G/G variant of SNP309 in the human MDM2 gene is associated with earlier tumor onset in Caucasian female renal cell carcinoma patients - Stoehr, Christine; Stoehr, R.; Wenners, A.; Hartmann, Arndt; Bertz, Simone; Spath, V.; Walter, B.; Junker, K.; Moch, H.; Hinze, R.; Denzinger, S.; Bond, E. E.; et al. (Oncogenesis, 2016)
Human mouse double minute 2 (Mdm2) plays an essential role in the regulation of the tumor suppressor p53. The G/G variant of SNP309 was shown to increase Mdm2 mRNA/protein expression and to be associated with an increased risk and earlier onset of different cancers in Asian populations. However, the frequency and impact of these G/G variants have not been studied in Caucasian renal cell carcinoma (RCC) patients. Therefore, we analyzed an unselected German cohort of 197 consecutive RCC patients and detected the G/G variant in 18 (9.1%) patients, the G/T variant in 116 (58.9%) patients and the T/T variant in 63 (32.0%) patients. Studying the association between age at tumor onset and SNP309 genotypes, no correlation was detected in the entire RCC cohort or among the male RCC patients. However, the female G/G patients (median age 59.5 years) were diagnosed 13.5 years earlier than the T/T females (median age 73 years). When separating all females into two groups at their median age (68 years), 7 and 1 patients with the G/G variant and 9 and 13 patients with the T/T variant were noted in these age groups (P=0.024). To study the age dependency of tumor onset further, a second, age-selected cohort of 205 RCC patients was investigated, which comprised especially young and old patients. Interestingly, the G/G type occurred more often at lower tumor stages and tumor grades compared with higher stages (P=0.039 and 0.004, respectively). In females, the percentage of the G/G variant was only slightly higher in the younger age group, whereas in males, the percentage of the G/G variant was remarkably higher in the younger age group (19.4% vs 8.0%). In summary, female Caucasian RCC patients with the MDM2 SNP309 G/G genotype showed significantly earlier tumor onset than patients with the wild-type T/T genotype.
EVALuna2:6760

How Octogenarians with Bladder Cancer Are Treated in a Maximum-Care Hospital: The Real-Life Experience - Sikic, Danijel; Wach, Sven; Taubert, Helge; Richterstetter, Mario; Kunath, Frank; Lieb, Verena; Krause, F. Steffen; Merten, Ricarda; Ott, Oliver; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (Urologia Internationalis, 2016)
With increasing life expectancy, curative treatment of octogenarians with urothelial carcinoma of the bladder (UCB) becomes more important.The treatment modalities of 276 octogenarians with UCB who were treated at the University Hospital of Erlangen between 1982 and 2011 were assessed retrospectively.One hundred forty-six patients had non-muscle invasive bladder cancer (NMIBC) while 71 had muscle invasive bladder cancer (MIBC). No data was available for 59 patients. Eighty-five (58.2%) of the 146 patients with NMIBC received transurethral resection of the bladder tumor (TURBT) only, another 38 patients (26%) underwent additional intravesical therapy; and 8.9% were treated with radiochemotherapy (RCT), 4.1% with radiotherapy (RT), 1.4% with systemic chemotherapy and 1.4% with radical cystectomy (RC). Of the 71 patients suffering from MIBC, 39 (54.9%) received TURBT alone. A potentially curative therapy was performed on 31 of the 71 patients with MIBC (43.7%). Of these, 16 patients (51.6%) received RCT, 9 patients (29.0%) RT and 6 patients (19.4%) RC. In Kaplan-Meier analysis, patients with MIBC had better median overall survival with curative treatment compared to TURBT alone (28 vs. 9 months; p < 0.001, log-rank test).By offering a wide range of treatment options, over 43% of octogenarians with MIBC received a curative therapy at a maximum care hospital.
EVALuna2:16292

Hypoxia drives glucose transporter 3 expression through hypoxia-inducible transcription factor (HIF)-mediated induction of the long noncoding RNA NICI - Lauer, Victoria; Grampp, Steffen; Platt, James; Lafleur, Veronique; Lombardi, Olivia; Choudhry, Hani; Kranz, Franziska; Hartmann, Arndt; Wullich, Bernd; Yamamoto, Atsushi; Coleman, Mathew L.; Ratcliffe, Peter John; et al. (Journal of Biological Chemistry, 2020)
Hypoxia-inducible transcription factors (HIFs) directly dictate the expression of multiple RNA species including novel and as yet uncharacterized long noncoding transcripts with unknown function. We used pan-genomic HIF-binding and transcriptomic data to identify a novel long noncoding RNA Noncoding Intergenic Co-Induced transcript (NICI) on chromosome 12p13.31 which is regulated by hypoxia via HIF-1 promoter-binding in multiple cell types. CRISPR/Cas9-mediated deletion of the hypoxia-response element revealed co-regulation of NICI and the neighboring protein-coding gene, solute carrier family 2 member 3 (SLC2A3) which encodes the high-affinity glucose transporter 3 (GLUT3). Knockdown or knockout of NICI attenuated hypoxic induction of SLC2A3, indicating a direct regulatory role of NICI in SLC2A3 expression, which was further evidenced by CRISPR/Cas9-VPR-mediated activation of NICI expression. We also demonstrate that regulation of SLC2A3 is mediated through transcriptional activation rather than posttranscriptional mechanisms because knockout of NICI leads to reduced recruitment of RNA polymerase 2 to the SLC2A3 promoter. Consistent with this we observe NICI-dependent regulation of glucose consumption and cell proliferation. Furthermore, NICI expression is regulated by the von Hippel-Lindau (VHL) tumor suppressor and is highly expressed in clear cell renal cell carcinoma (ccRCC), where SLC2A3 expression is associated with patient prognosis, implying an important role for the HIF/NICI/SLC2A3 axis in this malignancy.
CRIS-Team Scopus Importer:2020-04-07
Keywords: ChIP; ChIP-sequencing (ChIP-Seq); glucose transport; GLUT3; hypoxia; hypoxia-inducible factor (HIF); long noncoding RNA (long ncRNA; lncRNA)

Identification of novel microRNAs regulating HLA-G expression and investigating their clinical relevance in renal cell carcinoma - Jasinski-Bergner, Simon; Reches, Adi; Stoehr, Christine; Massa, Chiara; Gonschorek, Evamaria; Huettelmaier, Stefan; Braun, Juliane; Wach, Sven; Wullich, Bernd; Spath, Verena; Wang, Ena; Marincola, Francesco M.; et al. (Oncotarget, 2016)
The non-classical human leukocyte antigen G (HLA-G) is expressed at a high frequency in renal cell carcinoma (RCC) and is associated with a higher tumor grade and a poor clinical outcome. This might be caused by the HLA-G-mediated inhibition of the cytotoxicity of T and NK cells. Therefore a selective targeting of HLA-G might represent a powerful strategy to enhance the immunogenicity of RCC lesions. Recent studies identified a number of HLA-G-regulating microRNAs (miRs) and demonstrated an inverse expression of some of these miRs with HLA-G in RCC in vitro and in vivo. However, it was postulated that further miRs might exist contributing to the tightly controlled selective HLA-G expression.By application of a miR enrichment assay (miTRAP) in combination with in silico profiling two novel HLA-G-regulatory miRs, miR-548q and miR-628-5p, were identified. Direct interactions of both miRs with the 3' untranslated region of HLA-G were confirmed with luciferase reporter gene assays. In addition, qPCR analyses and immunohistochemical staining revealed an inverse, expression of miR-628-5p, but not of miR-548q to the HLA-G protein in primary RCC lesions and cell lines. Stable overexpression of miR-548q and miR-628-5p caused a downregulation of HLA-G mRNA and protein. This leads in case of miR-548q to an enhanced NK cell-mediated HLA-G-dependent cytotoxicity, which could be reverted by ILT2 blockade suggesting a control of the immune effector cell activity at least by this miR. The identification of two novel HLA-G-regulatory miRs extends the number of HLA-G-relevant miRs tuning the HLA-G expression and might serve as future therapeutic targets.
EVALuna2:6802

Immune Cell-Associated Protein Expression Helps to Predict Survival in Muscle-Invasive Urothelial Bladder Cancer Patients after Radical Cystectomy and Optional Adjuvant Chemotherapy - Taubert, Helge; Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; et al. (Cells, 2021)
Bladder cancer (BCa) is the tenth most commonly diagnosed malignant cancer worldwide. Although adjuvant chemotherapy following radical cystectomy is a common therapy for muscle invasive bladder cancer patients, no applicable biomarkers exist to predict which patients will benefit from chemotherapy. In this study, we examined three immune cell markers, the chemokine CC motif ligand 2 (CCL2), the pan macrophage marker cluster of differentiation 68 (CD68) and the M2 macrophage marker cluster of differentiation 163 (CD163), using immunohistochemistry to determine their predictive value for the chemotherapy response in different nodal stage (pN0 vs. pN1 + 2) and tumor stage subgroups (pT2 vs. pT3 + 4). The prognosis was studied in terms of the overall survival (OS), disease-specific survival (DSS), and recurrence-free-survival (RFS) in 168 muscle invasive BCa patients. Chemotherapy was associated with a poorer prognosis in patients with a higher expression of the immune markers CCL2 (RFS), CD68 (DSS and RFS), and CD163 (DSS and RFS) in the N0 group and with poorer survival in patients with a higher expression of the immune markers CCL2 (OS, DSS, and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS, DSS, and RFS) in the pT2 group when compared with treatments without chemotherapy. In contrast, chemotherapy was associated with a better prognosis in patients with a low expression of the immune markers CCL2 (DSS and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS) in the N1 + 2 group. In addition, chemotherapy was associated with improved survival in patients with a low expression of the immune marker CD68 (OS and DSS) and there was a trend for a better prognosis in patients with a low expression of CD163 (OS) in the pT3 + 4 group compared to patients not treated with chemotherapy. Interestingly, CD68 appeared to be the most applicable immune marker to stratify patients by the outcome of chemotherapy in the nodal stage and tumor stage groups. Overall, we suggest that, in addition to the clinical factors of tumor stage and nodal stage, it is also meaningful to consider the abundance of immune cells, such as macrophages, to better predict the response to chemotherapy for BCa patients after radical treatment.
CRIS-Team Scopus Importer:2021-02-12
Keywords: bladder cancer; CCL2; CD163; CD68; chemotherapy; immune cells; nodal stage; tumor stage

Immune Cell Gene Expression Signature is Associated with Improved Outcome in Muscle-Invasive Urothelial Bladder Cancer Patients Treated with Radical Cystectomy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph M.; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium. - Seitz, Julia; Hoegel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
OBJECTIVE: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. METHODS: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffin-embedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. RESULTS: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. CONCLUSION: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
EVALuna2:512116

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium - Seitz, Julia; Hogel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
Objective: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. Methods: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffinembedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. Results: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. Conclusion: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
CRIS-Team WoS Importer:2022-09-30

Immunohistochemiocal subtyping using CK20 and CK5 can identify urothelial carcinomas of the upper urinary tract with a poor prognosis - Sikic, Danijel; Keck, Bastian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Goebell, Peter; Kahlmeyer, Andreas; Olbert, Peter; Isfort, Philipp; Nimphius, Wilhelm; Hartmann, Arndt; Giedl, Josef (PLoS ONE, 2017)
Genome-wide analyses revealed basal and luminal subtypes of urothelial carcinomas of the bladder. It is unknown if this subtyping can also be applied to upper tract urothelial carcinomas.Tumor samples from 222 patients with upper tract urothelial carcinomas who were treated with radical nephroureterectomy were analyzed for the expression of seven basal/luminal immunohistochemical markers (CK5, EGFR, CD44, CK20, p63, GATA3, FOXA1).Hierarchical clustering revealed a basal-like subtype (enrichment of CK5, EGFR and CD44) in 23.9% and a luminal-like subtype (enrichment of CK20, GATA3, p63 and FOXA1) in 13.1% of the patients. In 60.8%, little to no markers were expressed, whereas markers of both subtypes were expressed in 2.2%. By using CK5 and CK20 as surrogate markers for the basal and luminal subtypes, we defined four subtypes of upper tract urothelial carcinomas: (i) exclusively CK20 positive and CK5 negative (CK20+/CK5-), (ii) exclusively CK5 positive and CK20 negative (CK20-/ CK5+), (iii) both markers positive (CK20+/CK5+) and (iv) both markers negative (CK20-/CK5-). A receiver-operator analysis provided the optimal cut-off values for this discrimination. An immunoreactive score >1 for CK5 and >6 for CK20 were defined as positive. In multivariate Cox's regression analysis, the CK20+/CK5- subtype was an independent negative prognostic marker with a 3.83-fold increased risk of cancer-specific death (p = 0.02) compared to the other three subtypes.Immunohistochemical subgrouping of upper tract urothelial carcinomas by analyzing CK5 and CK20 expression can be performed in a routine setting and can identify tumors with a significantly worse cancer-specific survival prognosis.
EVALuna2:6876

Improving the Quality of Care for Cancer Patients through Oncological Second Opinions in a Comprehensive Cancer Center: Feasibility of Patient-Initiated Second Opinions through a Health-Insurance Service Point - Schulmeyer, Carla; Beckmann, Matthias; Fasching, Peter; Häberle, Lothar; Golcher, Henriette; Kunath, Frank; Wullich, Bernd; Emons, Julius (Diagnostics, 2023)
Background: To improve the quality and cost-effectiveness of care, cancer patients can obtain a second medical opinion on their treatment. Validation of the diagnostic procedure (e.g., imaging), diagnosis, and treatment recommendation allows oncological therapy to be applied in a more targeted way, optimizing interdisciplinary care. This study describes patients who received second opinions at the Comprehensive Cancer Center for Erlangen–Nuremberg metropolitan area in Germany over a 6-year period, as well as the amount of time spent on second-opinion counseling. Methods: This prospective, descriptive, single-center observational study included 584 male and female cancer patients undergoing gynecological, urologic, or general surgery who sought a second medical opinion. The extent to which the first opinion complied with standard guidelines was assessed solely descriptively. Results: The first opinion was in accordance with the guidelines and complete in 54.5% of the patients, and guideline compliant but incomplete in 13.2%. The median time taken to form a second opinion was 225 min, and the cancer information service was contacted by patients an average of eight times. Conclusions: The initial opinion was guideline compliant and complete in every second case. Without a second opinion, the remaining patients would have been denied a guideline-compliant treatment recommendation. Obtaining a second opinion gives patients an opportunity to receive a guideline-compliant treatment recommendation and enables them to benefit from newer, individualized therapeutic approaches in clinical trials. Establishing patient-initiated second opinions via central contact points appears to be a feasible option for improving guideline compliance.
CRIS-Team Scopus Importer:2023-11-24
Keywords: gastrointestinal cancer; gynecologic cancer; sarcoma; second medical opinion; urologic cancer

Individualisierte Präzisionsmedizin - Wullich, Bernd; Taubert, Helge; Goebell, Peter; Kuwert, Torsten; Beck, Michael; Schott, Christian; Baur, Andreas; Eckstein, Markus; Wach, Sven (Die Urologie, 2023)
Spectacular advances have been made in personalized medicine , which has rapidly revolutionized our traditional understanding of disease diagnosis and treatment. Molecular testing of tissue and liquid samples using next generation sequencing has developed into a key technology in this scenario. It can be used for both the determination of biomarkers for diagnostic, prognostic and predictive purposes, as well as the possible improvement of treatment outcome through the use of targeted therapies and the avoidance of therapies in the event of special resistance situations. In addition to drugs that have already been approved, which among other things intervene in cellular DNA repair, many new drugs have been developed and are in clinical testing. Furthermore, new possibilities in molecular imaging have dramatically expanded our understanding of tumor spread and created new approaches for targeted therapies.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Biomarkers; Cancer; Liquid biopsy; Next generation sequencing; PSMA

Infectious complications following transperineal prostate biopsy with or without periprocedural antibiotic prophylaxis—a systematic review including meta-analysis of all comparative studies - Wolff, Ingmar; Büchner, Markus; Hauner, Katharina; Wagenlehner, Florian; Burchardt, Martin; Abele-Horn, Marianne; Wullich, Bernd; Gilfrich, Christian; Pilatz, Adrian; May, Matthias (Prostate Cancer and Prostatic Diseases, 2025)
Background: Despite the relatively low infection rate following transperineal prostate biopsy (TPB), it remains unresolved whether periprocedural antibiotic prophylaxis (PAP) can be omitted. Our aim was to compare infectious complications (genitourinary infections/GUI, fever, sepsis, readmission rate, 30-day-mortality) following TPB, considering all studies of varying levels of evidence that enable a direct comparison between patients with and without PAP. Methods: We performed a comprehensive search in PubMed/Medline, Embase, Web of Science, and Cochrane databases, as well as grey literature sources, to identify reports published until January 2024. All studies comparing the incidence of infectious endpoints following TPB with vs. without PAP were included in the analyses. The GRADE approach was employed to assess the certainty of evidence for each comparison. Results: Twenty-three studies met the inclusion criteria involving 6520 and 5804 patients who underwent TPB with vs. without PAP, respectively. Two of the 23 studies were randomized-controlled trials, not all studies investigated all endpoints. Pooled incidences between patients with vs. without PAP for the endpoints GUI (0.50% vs. 0.37%), fever (0.44% vs. 0.26%), sepsis (0.16% vs. 0.13%), and readmission rate (0.35% vs. 0.29%) showed no significant differences (all p > 0.250). The corresponding odds ratios (including 95% confidence interval) also revealed no statistically significant differences: 1.37 (0.74–2.54) [GUI], 0.87 (0.28–2.66) [fever], 1.30 (0.46–3.67) [sepsis], and 1.45 (0.70–3.03) [readmission rate]. No study reported events regarding 30-day-mortality. In subgroup analyses and sensitivity analyses, TPB without PAP showed no significantly higher complication rates regarding all analyzed endpoints. Conclusions: Infectious complications after TPB occur very rarely and cannot be further reduced by PAP. Considering the results of this systematic review and adhering to the principles of effective antibiotic stewardship, omitting PAP in the context of TPB is advisable.
CRIS-Team Scopus Importer:2025-01-31

Integration of spatial pd-l1 expression with the tumor immune microenvironment outperforms standard pd-l1 scoring in outcome prediction of urothelial cancer patients - Weyerer, Veronika; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Breyer, Johannes; Bolenz, Christian; Erben, Philipp; et al. (Cancers, 2021)
Background: Immune therapy has gained significant importance in managing urothelial cancer. The value of PD-L1 remains a matter of controversy, thus requiring an in-depth analysis of its biological and clinical relevance. Methods: A total of 193 tumors of muscle-invasive bladder cancer patients (MIBC) were assessed with four PD-L1 assays. PD-L1 scoring results were correlated with data from a comprehensive digital-spatial immune-profiling panel using descriptive statistics, hierarchical clustering and uni-/multivariable survival analyses. Results: PD-L1 scoring algorithms are heterogeneous (agreements from 63.1% to 87.7%), and stems from different constellations of immune and tumor cells (IC/TC). While Ventana IC5% algorithm identifies tumors with high inflammation and favorable baseline prognosis, CPS10 and the TCarea25%/ICarea25% algorithm identify tumors with TC and IC expression. Spatially organized immune phenotypes, which correlate either with high PD-L1 IC expression and favorable prognosis or constitutive PD-L1 TC expression and poor baseline prognosis, cannot be resolved properly by PD-L1 algorithms. PD-L1 negative tumors with relevant immune infiltration can be detected by sTILs scoring on HE slides and digital CD8+ scoring. Conclusions: Contemporary PD-L1 scoring algorithms are not sufficient to resolve spatially distributed MIBC immune phenotypes and their clinical implications. A more comprehensive view of immune phenotypes along with the integration of spatial PD-L1 expression on IC and TC is necessary in order to stratify patients for ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Bladder cancer; Immune phenotypes; PD-1; PD-L1; TILs; Urothelial cancer

Is there evidence for a close connection between side of intravesical tumor location and ipsilateral lymphatic spread in lymph node-positive bladder cancer patients at radical cystectomy? Results of the PROMETRICS 2011 database - May, M.; Protzel, C.; Vetterlein, M. W.; Gierth, M.; Noldus, J.; Karl, A.; Grimm, T.; Wullich, Bernd; Grimm, M. O.; Nuhn, P.; Bastian, P. J.; Roigas, J.; et al. (International Urology and Nephrology, 2017)
To evaluate the possible association between bladder tumor location and the laterality of positive lymph nodes (LN) in a prospectively collected multi-institutional radical cystectomy (RC) series. The study population included 148 node-positive bladder cancer (BC) patients undergoing RC and pelvic lymph node dissection in 2011 without neoadjuvant chemotherapy and without distant metastasis. Tumor location was classified as right, left or bilateral and compared to the laterality of positive pelvic LN. A logistic regression model was used to identify predictors of ipsilaterality of lymphatic spread. Using multivariate Cox regression analyses (median follow-up: 25 months), the effect of the laterality of positive LN on cancer-specific mortality (CSM) was estimated. Overall, median 18.5 LN [interquartile range (IQR), 11-27] were removed and 3 LN (IQR 1-5) were positive. There was concordance of tumor location and laterality of positive LN in 82% [95% confidence interval (CI), 76-89]. Patients with unilateral tumors (n = 78) harbored exclusively ipsilateral positive LN in 67% (95% CI 56-77). No criteria were found to predict ipsilateral positive LN in patients with unilateral tumors. CSM after 3 years in patients with ipsilateral, contralateral, and bilateral LN metastasis was 41, 67, and 100%, respectively (p = 0.042). However, no significant effect of the laterality of positive pelvic LN on CSM could be confirmed in multivariate analyses. Our prospective cohort showed a concordance of tumor location and laterality of LN metastasis in BC at RC without any predictive criteria and without any influence on CSM. It is debatable, whether these findings may contribute to a more individualized patient management.
EVALuna2:35927

IT infrastructure components to support clinical care and translational research projects in a comprehensive cancer center - Prokosch, Hans-Ulrich; Ries, Markus; Beyer, Alexander; Schwenk, Martin; Seggewies, Christof; Köpcke, Felix; Mate, Sebastian; Martin, Marcus; Bärthlein, Barbara; Beckmann, Matthias; Stürzl, Michael; Croner, Roland; et al. (User Centred Networked Health Care, 2011)
This paper presents the concept of an integrated IT infrastructure framework established at the comprehensive cancer center at the University Hospital Erlangen. The framework is based on the single source concept where data from the electronic medical record are reused for clinical and translational research projects. The applicability of the approach is illustrated by two case studies from colon cancer and prostate cancer research projects. © 2011 European Federation for Medical Informatics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.infome.itinfr
Keywords: Cancer documentation; Center; Comprehensive cancer; IT infrastructure framework; Single source concept; Translational research

Kidney transplantation in prostate cancer patients after local therapy with curative intent: a systematic review - Rumpff, C.; Lieb, Verena; Wullich, Bernd; Schiffer, Mario; Kunath, Frank; Apel, Hendrik (World Journal of Urology, 2024)
Purpose: It is still unclear whether kidney transplantation can be safely performed in patients with prostate cancer after local therapy with curative intent. Methods: The protocol was registered in PROSPERO. We systematically searched Google, MEDLINE, the Cochrane Library, and the ICTRP for studies, official standards, clinical practice guidelines and organ transplant laws. Two review authors independently examined the full-text reports and identified relevant studies and one review author extracted the data. We assessed the overall certainty of the evidence for each outcome according to the GRADE approach. Results: We identified 1346 references through electronic database searching and finally included 6 references for official standards, clinical practice guidelines, and organ transplant laws, and 6 references for retrospective studies with very low certainty of evidence. We identified no prospective or ongoing studies and reported all results narratively. Conclusion: We recommend that decisions on kidney transplantation in patients with prostate cancer after local therapy with curative intent should be made on a case-by-case basis. It is indispensable to consult with health care professionals or specialists at transplant centers to obtain individualized information regarding the waiting time requirements for renal transplantation in prostate cancer patients after local therapy with curative intent. No recommendation can be made regarding the waiting times after prostate cancer therapy with curative intent.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Kidney transplantation; Prostatic neoplasms; Surgical techniques; Systematic review

Kindernierentransplantation bei komplexen urogenitalen Fehlbildungen – was gibt es zu beachten? - Marcou, Marios; Apel, Hendrik; Wullich, Bernd; Hirsch-Koch, Karin (Die Urologie, 2024)
Background: Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of end-stage renal disease (ESRD) in children. Approximately one third of children with CAKUT have lower urinary tract dysfunction (LUTD). Aim: This article highlights the important aspects that need to be considered in kidney transplantation of children with complex urogenital malformations. Materials and methods: The paper reviews the existing literature regarding the evaluation, preparation, perioperative management, and follow-up of children with complex urogenital malformations and ESRD undergoing renal transplantation. Results: Comprehensive diagnostics are required before any pediatric kidney transplantation. If LUTD is suspected, voiding cystourethrography and a urodynamic examination should be performed. Treatment of symptomatic vesicoureterorenal reflux and LUTD is mandatory prior to pediatric kidney transplantation. Following successful kidney transplantation of children with congenital urogenital malformations, lifelong follow-up is required. Regular reevaluations of the bladder by means of urodynamic examinations are necessary. In patients following bladder augmentation with intestinal segments or urinary diversions in childhood, regular endoscopic examinations of the urinary tract are recommended to rule out secondary malignancy. Conclusion: Treatment of children with complex urogenital malformations should be carried out in centers with appropriate expertise.
CRIS-Team Scopus Importer:2024-02-23
Keywords: CAKUT; Renal insufficiency; Urinary bladder diseases; Urinary tract; Voiding cystourethrography

Large nested variant of urothelial carcinoma: a prime example of a FGFR3-mutated, luminal tumour - Weyerer, Veronika; Eckstein, Markus; Comperat, E.; Juette, H.; Allory, Y.; Stoehr, R.; Wullich, Bernd; Roupret, M.; Hartmann, Arndt; Bertz, Simone (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Long-Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High-Risk Bladder Cancer (Ta, Tis, T1, T2) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al. (Oncologist, 2019)
Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high-risk bladder cancer after transurethral resection of bladder tumor (TUR-BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR-BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR-BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p =.037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p =.092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p =.045). Five-year OS from unadjusted Kaplan-Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5-year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p =.0001). RCT + RHT compared with RCT showed a significantly better bladder-preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p =.006). Median follow-up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR-BT followed by RT; concomitant platinum-based chemotherapy combined with RHT in patients with high-grade bladder cancer improves local control, bladder-preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle-invasive bladder cancer in medically fit patients, despite many centers reporting excellent long-term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder-preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum-based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder-preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Bladder cancer; Bladder preservation; Chemoradiotherapy; Hyperthermia; Radiotherapy

Loss of expression of the SWI/SNF complex is a frequent event in undifferentiated/dedifferentiated urothelial carcinoma of the urinary tract - Agaimy, Abbas; Bertz, Simone; Cheng, Liang; Hes, Ondrej; Junker, Kerstin; Keck, Bastian; Lopez-Beltran, Antonio; Stoeckle, Michael; Wullich, Bernd; Hartmann, Arndt (Virchows Archiv, 2016)
Loss of the SWI/SNF chromatin remodeling complex has been recently implicated in the pathogenesis of dedifferentiated carcinomas from different organs, but its possible role in undifferentiated urothelial carcinoma (UC) has not been studied to date. In this study, we analyzed by immunohistochemistry 14 undifferentiated UCs (11 from bladder and 3 from renal pelvis) with a nondescript anaplastic or rhabdoid morphology, using commercially available antibodies against the SWI/SNF components SMARCB1 (INI1), SMARCA2, SMARCA4, SMARCC1, SMARCC2, and ARID1A. Patients were eight females and six males aged 40 to 84 years (median, 65). All tumors were muscle-invasive (9 were T3-4). A conventional UC component was seen in eight cases and varied from in situ to papillary. The undifferentiated component comprised 60-100 % of the tumors. Histologically, most tumors showed diffuse dyscohesive or pseudoalveolar growth of variably sized cells with frequent rhabdoid features. Transition from conventional to undifferentiated UC was abrupt, except in one case. The undifferentiated component almost always expressed pan-cytokeratin AE1/AE3 (13/14) and variably vimentin (8/14) and GATA3 (9/14). Complete loss of at least one SWI/SNF subunit limited to the undifferentiated component was detected in 10/14 cases (71 %). SMARCA2 was most frequently lost (six) followed by ARID1A (four), SMARCB1/INI1 (two), SMARCA4 (one), and SMARCC1 (one). This is the first study exploring SWI/SNF expression in undifferentiated UC of the urinary tract. Our results are in line with recent studies reporting involvement of the SWI/SNF complex in the dedifferentiation process of a variety of epithelial neoplasms in different organs, including the urinary tract, and association with aggressive clinical course.
EVALuna2:6799

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study - Rogler, Anja; Hoja, Sabine; Giedl, Josef; Ekici, Arif Bülent; Wach, Sven; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; et al. (BMC Cancer, 2014)
Seventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder cancer.MTUS1 was identified to be the most promising deleted target gene at 8p in aCGH analysis with 19 papillary bladder tumours. A correlation with bladder cancer was further validated using immunohistochemistry of 85 papillary and 236 advanced bladder tumours and in functional experiments. Kaplan-Meier analysis and multivariate Cox-regression addressed overall survival (OS) and disease-specific survival (DSS) as a function of MTUS1/ATIP expression. Bivariate correlations investigated associations between MTUS1/ATIP expression, patient characteristics and histopathology. MTUS1 expression was analysed in cell lines and overexpressed in RT112, where impact on viability, proliferation and migration was measured.MTUS1 protein expression was lost in almost 50% of all papillary and advanced bladder cancers. Survival, however, was only influenced in advanced carcinomas, where loss of MTUS1 was associated with adverse OS and DSS. In this cohort, there was also a significant correlation of MTUS1 expression and histological subtype: positive expression was detected in all micropapillary tumours and aberrant nuclear staining was detected in a subset of plasmocytoid urothelial carcinomas. MTUS1 was expressed in all investigated bladder cell lines and overexpression in RT112 led to significantly decreased viability.MTUS1 is a tumour suppressor gene in cultured bladder cancer cells and in advanced bladder tumours. It might represent one new target gene at chromosome 8p and can be used as an independent prognostic factor for advanced bladder cancer patients. The limitation of the study is the retrospective data analysis. Thus, findings should be validated with a prospective advanced bladder tumour cohort.
EVALuna2:6624

Medication safety in patients treated with new oral antitumor agents: A prospective, randomized investigation on the impact of intensified clinical pharmaceutical/clinical pharmacological care on patient safety, patient knowledge and patient well-being (AMBORA). Supported by the German Cancer Aid within the Comprehensive Cancer Center Erlangen-EMN - Schlichtig, Katja; Lechner, P.; Grafe, Carolin; Ferstl, B.; Fuchs, F.; Hein, Alexander; Meidenbauer, N.; Sell, C.; Semrau, S.; Pavel, Marianne Ellen; Wullich, Bernd; Neurath, Markus; et al. (2018)
EVALuna2:33795

Megaprepuce: presentation of a modified surgical technique with excellent cosmetic and functional results - Hirsch, K.; Schwaiger, Brigitte; Kraske, S.; Wullich, Bernd (Journal of Pediatric Urology, 2019)
Objective: Congenital megaprepuce is a malformation consisting of a great redundancy of the inner preputial skin over a penis with normal shaft and glans and is combined with a severe phimosis. Patients suffer from difficulties in voiding because the urine is trapped in the large dome-shaped megaprepuce. We describe a modification of the surgical technique of reconstructing a megaprepuce initially presented by Leao et al. Patients and methods: We retrospectively reviewed 7 patients aged 6–53 months (mean age 17 months, 6 were younger than 18 months) who underwent congenital megaprepuce repair between 02/2014 and 05/2018 in our institution. All these otherwise healthy children suffering from difficulties in voiding and reporting genital ballooning during micturition and urinary retention were referred to our hospital. In all cases, parents needed to express the trapped urine. Four of these patients additionally showed a glanular hypospadias, another one a distal penile hypospadias. In addition to the repair of the megaprepuce, six patients needed correction of a penile curvature, five of whom needed correction of the chordee and one a corporoplasty (Schröder-Essed). The patient showing the distal penile hypospadias additionally underwent hypospadias repair. During the follow-up, we evaluated the cosmetic result and complications such as secondary concealed penis, difficulties in voiding, urinary retention, and urinary infections. Results: Mean follow-up was 18 months. All patients following surgery showed normal voiding without urinary retention or urinary infections and good cosmetic results resembling a circumcised penis in appearance without reconcealment. No intraoperative complications occurred. One patient had a scrotal hematoma postoperatively. Mild transient edema of the penis was seen in all patients, which disappeared spontaneously within one week after surgery. Conclusion: Our surgical approach is a safe and relatively simple procedure with a low rate of complications, good cosmetic results, and functional outcome. Whether the hypospadias associated with ventral curvature was a coincidence or part of the disease pattern remains unclear but will probably be the object of further investigations.[Figure presented]
CRIS-Team Scopus Importer:2019-07-16
Keywords: Hypospadias; Megaprepuce; Modified surgical technique

Micropapillary morphology is an indicator of poor prognosis in patients with urothelial carcinoma treated with transurethral resection and radiochemotherapy - Bertz, Simone; Wach, S.; Taubert, Helge; Merten, Ricarda; Krause, F. S.; Schick, S.; Ott, O. J.; Weigert, E.; Dworak, O.; Roedel, C.; Fietkau, Rainer; Wullich, Bernd; et al. (Virchows Archiv, 2016)
Purpose of this study was to evaluate prognostic impact of rare variants of urothelial bladder cancer (BC) after treatment with combined radiochemotherapy (RCT). To this end tumour tissue of 238 patients with urothelial carcinoma (UC) treated with transurethral resection of the bladder (TUR-B) and RCT with curative intent was collected. Histomorphological analysis included re-evaluation and semi-quantitative assessment of rare UC subtypes. Additionally, human epidermal growth factor receptor 2 (HER2) chromogenic in situ hybridisation (CISH) was performed in tumours with a micropapillary component exceeding 30 %. Long-term follow-up was available for 200 patients (range 3-282 months). Variant UC histology was found in 45 of 238 tumours, most frequently micropapillary UC (N = 17) including cases with a small fraction of tumour with micropapillary morphology. The mere presence of micropapillary morphology did not affect prognosis. In tumours with extensive (>=30 %) micropapillary morphology (N = 8) Kaplan-Meier analysis revealed significantly worse cancer specific survival (CSS) (P = 0.002) compared to conventional UC (mean survival times 97 months and 229 months, respectively). Univariate Cox regression analysis of cases with >=30 % micropapillary morphology revealed a hazard ratio of 4.726 (95 % CI 1.629-13.714) for CSS (P = 0.004). CISH revealed HER2 gene amplification in 3/10 tumours with >=30 % micropapillary component. In conclusion, for BC treated with TUR-B and RCT, the presence of micropapillary morphology in more than 30 % of the tumour is an adverse prognostic factor. Further studies are needed to evaluate a potential benefit of different, especially multimodal treatment strategies for micropapillary UC and also other subtypes of UC. Her2 represents a promising therapeutic target in a subset of micropapillary UC.
EVALuna2:6800

Micropapillary urothelial carcinoma: evaluation of HER2 status and immunohistochemical characterization of the molecular subtype - Zinnall, Ulrike; Weyerer, Veronika; Compérat, Eva; Camparo, Philippe; Gaisa, Nadine T.; Knuechel-Clarke, Ruth; Perren, Aurel; Lugli, Alessandro; Toma, Marieta; Baretton, Gustavo; Kristiansen, Glen; Wirtz, Ralph M.; et al. (Human Pathology, 2018)
Comprehensive molecular analyses of urothelial bladder cancer (UBC) have defined distinct subtypes with potential therapeutic implications. In this study, we focused on micropapillary urothelial carcinoma (MPUC), an aggressive, histomorphologically defined rare variant. Apart from genetic alterations shared with conventional UBC alterations of the HER2 gene have been reported in higher frequencies. However, only small cohorts of MPUCs have been analyzed and the real impact is still unclear. We collected a cohort of 94 MPUCs and immunohistochemically tested HER2, basal (CD44, CK5, EGFR, p63) and luminal (CD24, FOXA1, GATA3, CK20) markers to allocate MPUC to a molecular subtype. Additionally, HER2 amplification status was assigned by chromogenic in-situ-hybridization. Sanger sequencing of Exon 4 and 8 was used to test for HER2 mutations. Kruskal-Wallis test was calculated to compare marker distribution between proportions of the MPUC component. 2+/3+ HER2 staining scores were identified in 39.6% of 91 analyzed MPUCs and were not differentially distributed among the proportion of the MPUC component (P=.89). Additionally, CISH analysis revealed 30% of HER2 amplified tumors independently of the MPUC fraction. In 6/90 evaluable MPUCs a p.S310F HER2 mutation was detected. Overexpression of luminal markers was observed in the majority of MPUC. Our investigations of the largest cohort of analyzed MPUC demonstrate that HER2 overexpression and amplifications are common genetic alterations and identification of overexpressed luminal markers allows sub-classification to the luminal subtype. These findings highlight the need of histomorphological recognition of MPUC and analysis of HER2 status and the luminal molecular subtype for potential targeted therapeutic strategies.
EVALuna2:34304

Molecular Composition of Genomic TMPRSS2-ERG Rearrangements in Prostate Cancer - Krumbholz, Manuela; Agaimy, Abbas; Stöhr, Robert; Burger, Maximilian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt; Metzler, Markus (Disease Markers, 2019)
There is increasing interest in the use of cell-free circulating tumor DNA (ctDNA) as a serum marker for therapy assessment in prostate cancer patients. Prostate cancer is characterized by relatively low numbers of mutations, and, in contrast to many other common epithelial cancers, commercially available single nucleotide mutation assays for quantification of ctDNA are insufficient for therapy assessment in this disease. However, prostate cancer shares some similarity with translocation-affected mesenchymal tumors (e.g., leukemia and Ewing sarcoma), which are common in pediatric oncology, where chromosomal translocations are used as biomarkers for quantification of the tumor burden. Approximately 50% of prostate cancers carry a chromosomal translocation resulting in generation of the TMPRSS2-ERG fusion gene, which is unique to the tumor cells of each individual patient because of variability in the fusion breakpoint sites. In the present study, we examined the structural preconditions for TMPRSS2-ERG fusion sites in comparison with mesenchymal tumors in pediatric patients to determine whether the sequence composition is suitable for the establishment of tumor-specific quantification assays in prostate cancer patients. Genomic repeat elements represent potential obstacles to establishment of quantification assays, and we found similar proportions of repeat elements at fusion sites in prostate cancer to those reported for mesenchymal tumors, where genomic fusion sequences are established as biomarkers. Our data support the development of the TMPRSS2-ERG fusion gene as a noninvasive tumor marker for therapy assessment, risk stratification, and relapse detection to improve personalized therapy strategies for patients with prostate cancer.
CRIS-Team WoS Importer:2020-01-07

MRI-guided core biopsy of the prostate in the supine position - Introduction of a simplified technique using large-bore magnet systems - Schwab, Siegfried; Kuefner, Michael A.; Adamietz, Boris; Engelhard, Karl; Keck, Bastian; Kunath, Frank; Wach, Sven; Wullich, Bernd; Uder, Michael; Engehausen, Dirk (European Radiology, 2013)
Objectives: To introduce a simplified technique for MRI-guided core biopsies (MRGB) of the prostate in the supine position using large-bore magnet systems. Methods: Fifty men with a history of negative transrectal ultrasound-guided biopsies underwent MRGB in either a 1.5-T (13/50) or 3.0-T (37/50) wide-bore MRI unit. MRGBs were conducted with the patients in a supine position using a dedicated MR-compatible biopsy device. Results: We developed a dedicated positioning device for the supine position. Using this device, the biopsies were performed successfully in all patients. Apart from minor rectal bleeding, only one patient developed a major side effect (urosepsis). Histology revealed prostate cancer in 25/50 (50 %) patients. Conclusions: The new technique appears feasible. Its major advantage is the more comfortable and patient-friendly supine position during the biopsy without the need to modify the MRI system's patient table. Key Points: • A novel positioning device for MRI-guided prostate biopsies has been developed. • Biopsies can be performed in the patient-friendly supine position. • The positioning device can be utilised without modifying the MRI's patient table. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biopsy; Magnetic resonance imaging; Prostate cancer; Supine position

Multi-Center Assessment of Lymph-Node Density and Nodal-Stage to Predict Disease-Specific Survival in Patients with Bladder Cancer Treated by Radical Cystectomy. - van Gennep, Erik J.; Claps, Francesco; Bostrom, Peter J.; Shariat, Shahrokh F.; Neuzillet, Yann; Zlotta, Alexandre R.; Trombetta, Carlo; Eckstein, Markus; Mertens, Laura S.; Bussani, Rossana; Burger, Maximilian; Boormans, Joost L.; et al. (Bladder Cancer, 2024)
BACKGROUND: Prognostic tools in pathological-node (pN) patients after radical cystectomy (RC) are needed. OBJECTIVES: To evaluate the prognostic impact of lymph node (LN)-density on disease-specific survival (DSS) in patients with bladder cancer (BC) undergoing RC with pelvic lymph node dissection. METHODS: We analyzed a multi-institutional cohort of 1169 patients treated with upfront RC for cT1-4aN0M0 urothelial BCat nine centers. LN-densitywas calculated as the ratio of the number of positive LNs×100% to the number of LNs removed. The optimal LN-density cut-off value was defined by creating a time-dependent receiver operating characteristic (ROC) curve in pN patients. Univariable and multivariable Cox' regression analyses were used to assess the effect of conventional Tumor Nodes Metastasis (TNM) nodal staging system, LN-density and other LN-related variables on DSS in the pN-positive cohort. RESULTS: Of the 1169 patients, 463 (39.6%) patients had LN-involvement. The area under the ROC curve was 0.60 and the cut-off for LN-density was set at 20%, 223 of the pN-positive patients (48.2%) had a LN-density ≥ 20%. In multivariable models, the number of LN-metastases (HR 1.03, p = 0.005) and LN-density, either as continuous (HR 1.01, p = 0.013) or as categorical variable (HR 1.37, p = 0.014), were independently associated with worse DSS, whereas pN-stage was not. CONCLUSIONS: LN-density ≥ 20% was an independent predictor of worse DSS in BC patients with LN-involvement at RC. The integration of LN-density and other LN-parameters rather than only conventional pN-stage may contribute to a more refined risk-stratification in BC patients with nodal involvement.
EVALuna2:570127
Keywords: Bladder cancer; radical cystectomy; survival; lymph node density; urothelial neoplasm

Multicenter evaluation of complex urinary diversion for renal transplantation: outcomes of complex surgical solutions - Flegar, Luka; Huber, Johannes; Putz, Juliane; Thomas, Christian; Apel, Hendrik; Wullich, Bernd; Friedersdorff, Frank; Fechner, Guido; Ritter, Manuel; Kernig, Karoline; Weigand, Karl; Heynemann, Hans; et al. (World Journal of Urology, 2024)
Purpose: An abnormal lower urinary tract poses significant challenges for transplant surgeons. Besides the ureteral anastomosis to an ileal conduit, there are diverse complex reconstructive solutions. Due to its rarity, standardization and teaching of complex urinary diversion is extremely difficult. Methods: The indications and outcomes of complex urinary diversions after kidney transplantation (KT) were retrospectively investigated at eight urologic transplant centers including a current follow-up. Results: Of 37 patients with 21 (56%) males, vesicoureteral reflux (24%), spina bifida (22%), and glomerulonephritis (12%) were the most common causes of terminal renal failure. In 30 (81%) patients, urinary diversion was performed before KT, at a median of 107.5 (range, 10; 545) months before. Transplantations were held at a median patient age of 43 (10; 68) years, including six (16%) living donations. Urinary diversion was modified during 12 (32%) transplantations. After KT, the ileal conduit was the most common incontinent urinary diversion in 25 (67%) patients; a Mainz pouch I and bladder augmentation were the most frequent continent diversions (each n = 3). At a median follow-up of 120 months (range 0; 444), 12 (32%) patients had a graft failure with a 5-year graft survival of 79% (95%CI 61; 90). The median overall survival was 227 months (168; 286) and the 5-year overall survival 89% (69.3; 96.4). Conclusion: The mid-term kidney transplant function with complex urinary diversion appears to be comparable to transplants with regular urinary diversions. Hence, complex urinary diversion should always be considered as a surgical option, even during transplantation, if necessary.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Dialysis; Ileal conduit; Kidney transplantation; Renal insufficiency; Urinary diversion

Multicentric Analytical and Inter-observer Comparability of Four Clinically Developed Programmed Death-ligand 1 Immunohistochemistry Assays in Advanced Clear-cell Renal Cell Carcinoma - Sommer, Ulrich; Eckstein, Markus; Ammann, Johannes; Braunschweig, Till; Macher-Göppinger, Stephan; Schwamborn, Kristina; Hieke-Schulz, Stefanie; Harlow, Greg; Flores, Mike; Wullich, Bernd; Wirth, Manfred; Roth, Wilfried; et al. (Clinical Genitourinary Cancer, 2020)
Background: Previous studies have suggested increased clinical benefit with inhibition of programmed death-ligand 1 (PD-L1)/programmed death-1 in patients with PD-L1–positive locally advanced/metastatic renal cell carcinoma (RCC). We examined the analytical and inter-observer comparability of PD-L1–positivity across 4 clinically developed immunohistochemistry assays in clear-cell RCC (CCRCC). Materials and Methods: Randomly selected archived, formalin-fixed, paraffin-embedded nephrectomy specimens from 201 patients with locally advanced CCRCC were screened using VENTANA SP142. From these, 30 cases were selected based on their tumor-infiltrating immune cell (IC) PD-L1 status (PD-L1-IC–positivity of < 1%, 1%-5%, or > 5%; 10 cases each). These cases were stained for PD-L1 using VENTANA SP142 and SP263, and DAKO 22C3 and 28-8, and scored for PD-L1 expression on IC and tumor cells (TC) by trained readers at 5 sites. Results: Adjusted mean percentages of PD-L1-IC–positivity and PD-L1-TC–positivity varied from 4.0% to 4.9% and from 1.3% to 10.7%, respectively, between assays. Inter-assay differences in PD-L1-IC–positivity were small and non-significant (P = .1938 to .9963); for PD-L1-TC–positivity, significant differences were observed between VENTANA SP142 and the other assays (P ≤ .0001) and between VENTANA SP263 and DAKO 28-8 (P = .0248). Intra-class correlation values showed moderate-to-high inter-reader agreement for each assay for PD-L1-IC–positivity and for 3 assays for PD-L1-TC–positivity. Conclusions: In this first multicenter analytical comparison study of PD-L1 assays in CCRCC, PD-L1–positivity could be assessed reproducibly using all 4 assays for IC and for 3 of the 4 assays for TC.
CRIS-Team Scopus Importer:2020-03-27
Keywords: CCRC; Inter-observer variability; PD-L1; PD-L1 assay; Technical comparability; Uropathology

Multicentric validation of a comprehensive geriatric assessment to predict functional outcome and mortality following urooncological operations - Fiebig, Christian; Kahlmeyer, Andreas; Bannert, Hannes; Taubert, Helge; Wach, Sven; Koneval, Lukas; Graf, Sebastian; Folchini, Decio Maria; Alalem, Sameh; Gaßmann, Karl-Günter; Wullich, Bernd (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

NanoLuc Binary Technology as a methodological approach: an important new tool for studying the localization of androgen receptor and androgen receptor splice variant V7 homo and heterodimers - Guzman, Juan; Weigelt, Katrin; Neumann, Anna-Dorothea; Tripal, Philipp; Schmid, Benjamin; Winter, Zoltan; Palmisano, Ralf; Culig, Zoran; Cronauer, Marcus V.; Muschler, Paul; Wullich, Bernd; Taubert, Helge; et al. (BMC Cancer, 2024)
Background: The androgen/androgen receptor (AR)-signaling axis plays a central role in prostate cancer (PCa). Upon androgen-binding the AR dimerizes with another AR, and translocates into the nucleus where the AR-dimer activates/inactivates androgen-dependent genes. Consequently, treatments for PCa are commonly based on androgen deprivation therapy (ADT). The clinical benefits of ADT are only transitory and most tumors develop mechanisms allowing the AR to bypass its need for physiological levels of circulating androgens. Clinical failure of ADT is often characterized by the synthesis of a constitutively active AR splice variant, termed AR-V7. AR-V7 mRNA expression is considered as a resistance mechanism following ADT. AR-V7 no longer needs androgenic stimuli for nuclear entry and/or dimerization. Methods: Our goal was to mechanistically decipher the interaction between full-length AR (AR-FL) and AR-V7 in AR-null HEK-293 cells using the NanoLuc Binary Technology under androgen stimulation and deprivation conditions. Results: Our data point toward a hypothesis that AR-FL/AR-FL homodimers form in the cytoplasm, whereas AR-V7/AR-V7 homodimers localize in the nucleus. However, after androgen stimulation, all the AR-FL/AR-FL, AR-FL/AR-V7 and AR-V7/AR-V7 dimers were localized in the nucleus. Conclusions: We showed that AR-FL and AR-V7 form heterodimers that localize to the nucleus, whereas AR-V7/AR-V7 dimers were found to localize in the absence of androgens in the nucleus.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Androgen receptor; Androgen receptor variant 7; Heterodimer; Homodimer; NanoLuc Binary Technology; Prostate cancer

Neuropilin-2 and its ligand VEGF-C predict treatment response after transurethral resection and radiochemotherapy in bladder cancer patients - Keck, Bastian; Wach, S.; Taubert, Helge; Zeiler, S.; Ott, O. J.; Kunath, F.; Hartmann, Arndt; Bertz, Simone; Weiss, C.; Hoenscheid, P.; Schellenburg, S.; Roedel, C.; et al. (International Journal of Cancer, 2015)
The standard treatment for invasive bladder cancer is radical cystectomy. In selected patients, bladder-sparing therapy can be performed by transurethral resection (TURBT) and radio-chemotherapy (RCT) or radiotherapy (RT). Our published in vitro data suggest that the Neuropilin-2 (NRP2)/VEGF-C axis plays a role in therapy resistance. Therefore, we studied the prognostic impact of NRP2 and VEGF-C in 247 bladder cancer patients (cN0M0) treated with TURBT and RCT (n = 198) or RT (n = 49) and a follow-up time up to 15 years. A tissue microarray was analyzed by immunohistochemistry. NRP2 expression emerged as a prognostic factor in overall survival (OS; HR: 3.42; 95% CI: 1.48 - 7.86; p = 0.004) and was associated with a 3.85-fold increased risk of an early cancer specific death (95% CI: 0.91 - 16.24; p = 0.066) in multivariate analyses. Cancer specific survival (CSS) dropped from 166 months to 85 months when NRP2 was highly expressed (p = 0.037). Patients with high VEGF-C expression have a 2.29-fold increased risk of shorter CSS (95% CI: 1.03-5.35; p = 0.043) in univariate analysis. CSS dropped from 170 months to 88 months in the case of high VEGF-C expression (p = 0.041). Additionally, NRP2 and VEGF-C coexpression is a prognostic marker for OS in multivariate models (HR: 7.54; 95% CI: 1.57-36.23; p = 0.012). Stratification for muscle invasiveness (T1 vs. T2-T4) confirmed the prognostic role of NRP2 and NRP2/VEGF-C co-expression in patients with T2-T4 but also with high risk T1 disease. In conclusion, immunohistochemistry for NRP2 and VEGF-C has been determined to predict therapy outcome in bladder cancer patients prior to TURBT and RCT.
EVALuna2:6641

New Oral Antitumor Drugs and Medication Safety in Uro-Oncology: Implications for Clinical Practice Based on a Subgroup Analysis of the AMBORA Trial - Schlichtig, Katja; Cuba, Lisa; Dürr, Pauline; Bellut, Laura; Meidenbauer, Norbert; Kunath, Frank; Goebell, Peter; Mackensen, Andreas; Dörje, Frank; Fromm, Martin; Wullich, Bernd (Journal of Clinical Medicine, 2022)
Oral antitumor therapeutics (OAT) bear a high risk for medication errors, e.g., due to drug-drug or drug-food interactions or incorrect drug intake. Advanced age, organ insufficiencies, and polymedication are putting uro-oncological patients at an even larger risk. This analysis sets out to (1) investigate the frequency and relevance of medication errors in patients with prostate cancer or renal cell carcinoma treated with OAT and (2) compile recommendations for clinical practice. This post-hoc subgroup analysis used data collected in the randomized AMBORA trial (2017-2020; DRKS00013271). Clinical pharmacologists/pharmacists conducted advanced medication reviews over 12 weeks after initiation of a new oral regimen and assessed the complete medication process for drug-related problems. Medication errors related to either the OAT, prescribed or prescription-free concomitant medication, or food were classified regarding cause and severity. We identified 67 medication errors in 38 patients within the complete medication within 12 weeks. Thereof, 55% were detected at therapy initiation, 27% were caused by the patients, and 25% were drug-drug or drug-food interactions. Problem-prone issues are summarized in a 'medication safety table' to provide recommendations for clinical practice in uro-oncology. Tailored strategies including intensified care by clinical pharmacologists/pharmacists should be implemented in clinical practice to improve medication safety.
CRIS-Team WoS Importer:2022-08-26

No Evidence of Microsatellite Instability and Loss of Mismatch-Repair-Protein Expression in Squamous Cell Carcinoma of the Penis - Stoehr, Robert; Wendler, Olaf Dietrich; Giedl, Josef; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Wullich, Bernd; Bertz, Simone; Hartmann, Arndt (Pathobiology, 2019)
Objective: Microsatellite instability (MSI) and a defective mismatch repair (MMR) system were described as beneficial tumor features for response to immune checkpoint therapy (PD-1 blockade). Meanwhile, the FDA approved PD-1/PD-L1 inhibition treatment for any solid tumor showing MSI and/or defects in the MMR system. For squamous cell carcinoma (SCC) of the penis, no data on the frequency of MSI and altered MMR protein expression are available to date. Therefore, we investigated the MSI status and the expression of MMR proteins in a large cohort of penile SCCs. Methods: The MSI status of 105 archival formalin-fixed, paraffin-embedded penile SCCs was analyzed using the 5 markers of the NCI consensus panel for MIS testing (BAT25, 26, D2S123, D17S250, and D5S346), or, in cases without representative nontumorous tissue using a validated panel of 5 quasimonomorphic mononucleotide repeat markers (BAT 25, 26 and NR21, 24, 27). The expression of the MMR proteins MLH1, MSH2, MSH6, and PMS2 was analyzed using immunohistochemistry and a tissue microarray of a subset of penile SCCs from our cohort (n = 75). Results: Overall, in 96/105 cases, at least 4 microsatellite markers gave interpretable results. None of the cases showed MSI. Immunohistochemistry for MMR proteins was analyzable in 70/75 cases. All cases showed a regular expression of the MMR proteins. Conclusion: MSI and defects in MMR protein expression are not regular features of penile SCC and might not act as biomarkers for PD-1/PD-L1 blockade therapy in penile carcinoma.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Microsatellite instability; Mismatch-repair; Penile cancer; Squamous cell carcinoma; Tissue microarray

Non-steroidal antiandrogen monotherapy compared with luteinising hormone-releasing hormone agonists or surgical castration monotherapy for advanced prostate cancer - Kunath, Frank; Grobe, Henrik R.; Ruecker, Gerta; Motschall, Edith; Antes, Gerd; Dahm, Philipp; Wullich, Bernd; Meerpohl, Joerg J. (Cochrane Database of Systematic Reviews, 2014)
Non-steroidal antiandrogens and castration are the main therapy options for advanced stages of prostate cancer. However, debate regarding the value of these treatment options continues.To assess the effects of non-steroidal antiandrogen monotherapy compared with luteinising hormone-releasing hormone agonists or surgical castration monotherapy for treating advanced stages of prostate cancer.We searched the Cochrane Prostatic Diseases and Urologic Cancers Group Specialized Register (PROSTATE), the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Web of Science with Conference Proceedings, three trial registries and abstracts from three major conferences to 23 December 2013, together with reference lists, and contacted selected experts in the field and manufacturers.We included randomised controlled trials comparing non-steroidal antiandrogen monotherapy with medical or surgical castration monotherapy for men in advanced stages of prostate cancer.One review author screened all titles and abstracts; only citations that were clearly irrelevant were excluded at this stage. Then, two review authors independently examined full-text reports, identified relevant studies, assessed the eligibility of studies for inclusion, assessed trial quality and extracted data. We contacted the study authors to request additional information. We used Review Manager 5 for data synthesis and used the fixed-effect model for heterogeneity less than 50%; we used the random-effects model for substantial or considerable heterogeneity.Eleven studies involving 3060 randomly assigned participants were included in this review. The quality of evidence is hampered by risk of bias. Use of non-steroidal antiandrogens decreased overall survival (hazard ratio (HR) 1.24, 95% confidence interval (CI) 1.05 to 1.48, six studies, 2712 participants) and increased clinical progression (one year: risk ratio (RR) 1.25, 95% CI 1.08 to 1.45, five studies, 2067 participants; 70 weeks: RR 1.26, 95% CI 1.08 to 1.45, six studies, 2373 participants; two years: RR 1.14, 95% CI 1.04 to 1.25, three studies, 1336 participants), as well as treatment failure (one year: RR 1.19, 95% CI 1.02 to 1.38, four studies, 1539 participants; 70 weeks: RR 1.27, 95% CI 1.05 to 1.52, five studies, 1845 participants; two years: RR 1.14, 95% CI 1.05 to 1.24, two studies, 808 participants), compared with medical or surgical castration. The quality of evidence for overall survival, clinical progression and treatment failure was rated as moderate according to GRADE. Predefined subgroup analyses showed that use of non-steroidal antiandrogens, compared with castration, was less favourable for overall survival, clinical progression (at one year, 70 weeks, two years) and treatment failure (at one year, 70 weeks, two years) in men with metastatic disease. Use of non-steroidal antiandrogens also increased the risk for treatment discontinuation due to adverse events (RR 1.82, 95% CI 1.13 to 2.94, eight studies, 1559 participants), including events such as breast pain (RR 22.97, 95% CI 14.79 to 35.67, eight studies, 2670 participants), gynaecomastia (RR 8.43, 95% CI 3.19 to 22.28, nine studies, 2774 participants) and asthenia (RR 1.77, 95% CI 1.36 to 2.31, five studies, 2073 participants). The risk of other adverse events, such as hot flashes (RR 0.23, 95% CI 0.19 to 0.27, nine studies, 2774 participants), haemorrhage (RR 0.07, 95% CI 0.01 to 0.54, two studies, 546 participants), nocturia (RR 0.38, 95% CI 0.20 to 0.69, one study, 480 participants), fatigue (RR 0.52, 95% CI 0.31 to 0.88, one study, 51 participants), loss of sexual interest (RR 0.50, 95% CI 0.30 to 0.83, one study, 51 participants) and urinary frequency (RR 0.22, 95% CI 0.11 to 0.47, one study, 480 participants) was decreased when non-steroidal antiandrogens were used. The quality of evidence for breast pain, gynaecomastia and hot flashes was rated as moderate according to GRADE. The effects of non-steroidal antiandrogens on cancer-specific survival and biochemical progression remained unclear.Currently available evidence suggests that use of non-steroidal antiandrogen monotherapy compared with medical or surgical castration monotherapy for advanced prostate cancer is less effective in terms of overall survival, clinical progression, treatment failure and treatment discontinuation due to adverse events. Evidence quality was rated as moderate according to GRADE. Further research is likely to have an important impact on results for patients with advanced but non-metastatic prostate cancer treated with non-steroidal antiandrogen monotherapy. However, we believe that research is likely not necessary on non-steroidal antiandrogen monotherapy for men with metastatic prostate cancer. Only high-quality, randomised controlled trials with long-term follow-up should be conducted. If further research is planned to investigate biochemical progression, studies with standardised follow-up schedules using measurements of prostate-specific antigen based on current guidelines should be conducted.
EVALuna2:16299

Non-steroidal antiandrogen monotherapy compared with luteinizing hormone-releasing hormone agonists or surgical castration monotherapy for advanced prostate cancer: a Cochrane systematic review - Kunath, Frank; Grobe, Henrik R.; Ruecker, Gerta; Motschall, Edith; Antes, Gerd; Dahm, Philipp; Wullich, Bernd; Meerpohl, Joerg J. (Bju International, 2015)
To assess the effects of non-steroidal antiandrogen monotherapy compared with luteinizing hormone-releasing hormone agonists or surgical castration monotherapy for treating advanced hormone-sensitive stages of prostate cancer. We searched the Cochrane Prostatic Diseases and Urologic Cancers Group Specialized Register (PROSTATE), the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Web of Science with Conference Proceedings, three trial registries and abstracts from three major conferences to 23 December 2013, together with reference lists, and contacted selected experts in the field and manufacturers. We included randomized controlled trials comparing non-steroidal antiandrogen monotherapy with medical or surgical castration monotherapy for men in advanced hormone-sensitive stages of prostate cancer. Two review authors independently examined full-text reports, identified relevant studies, assessed the eligibility of studies for inclusion, extracted data and assessed risk of bias as well as quality of evidence according to the GRADE working group guidelines. We used Review Manager 5.2 for data synthesis and the fixed-effect model as primary analysis (when heterogeneity was low with I(2) < 50%); we used a random-effects model when confronted with substantial or considerable heterogeneity (when I(2) >=50%). A total of 11 studies involving 3060 randomly assigned participants were included in the present review. Use of non-steroidal antiandrogens resulted in lower overall survival times (hazard ratio [HR] 1.24, 95% confidence interval [CI] 1.05-1.48, six studies, 2712 participants) and greater clinical progression (1 year: risk ratio [RR] 1.25, 95% CI 1.08-1.45, five studies, 2067 participants; 70 weeks: RR 1.26, 95% CI 1.08-1.45, six studies, 2373 participants; 2 years: RR 1.14, 95% CI 1.04-1.25, three studies, 1336 participants), as well as treatment failure (1 year: RR 1.19, 95% CI 1.02-1.38, four studies, 1539 participants; 70 weeks: RR 1.27, 95% CI 1.05-1.52, five studies, 1845 participants; 2 years: RR 1.14, 95% CI 1.05-1.24, two studies, 808 participants), compared with medical or surgical castration. The quality of evidence for overall survival, clinical progression and treatment failure was rated as moderate according to GRADE. Use of non-steroidal antiandrogens increased the risk for treatment discontinuation as a result of adverse events (RR 1.82, 95% CI 1.13-2.94, eight studies, 1559 participants), including events such as breast pain (RR 22.97, 95% CI 14.79- 35.67, eight studies, 2670 participants) and gynaecomastia (RR 8.43, 95% CI 3.19-22.28, nine studies, 2774 participants) The risk of other adverse events, such as hot flushes (RR 0.23, 95% CI 0.19-0.27, nine studies, 2774 participants) was decreased when non-steroidal antiandrogens were used. The quality of evidence for breast pain, gynaecomastia and hot flushes was rated as moderate according to GRADE. The effects of non-steroidal antiandrogens on cancer-specific survival and biochemical progression remained unclear. Non-steroidal antiandrogen monotherapy compared with medical or surgical castration monotherapy for advanced prostate cancer is less effective in terms of overall survival, clinical progression, treatment failure and treatment discontinuation resulting from adverse events. Evidence quality was rated as moderate according to GRADE; therefore, further research is likely to have an important impact on results for patients with advanced but non-metastatic prostate cancer treated with non-steroidal antiandrogen monotherapy.
EVALuna2:16293

Operative therapy of spinal metastases from urological tumors - Richter, R. H.; Hammon, Matthias; Uder, Michael; Huber, J.; Goebell, Peter; Kunath, F.; Wullich, Bernd; Keck, Bastian (Urologe, 2016)
The treatment of bone metastases from urological tumors represents a palliative form of therapy, apart from the resection of solitary metastases from renal cell carcinomas. Due to the high incidence of spinal metastases this can result in clinically significant symptoms and possible complications for patients, such as pain, spinal instability and compression of the spinal canal with corresponding neurological deficits. By the use of targeted diagnostics and induction of radiotherapeutic and/or surgical treatment, for the majority of patients an immediate reduction in pain as well as early mobilization and sometimes even regression of existing neurological deficits and therefore an improved quality of life can be achieved.
EVALuna2:14490

Optimizing outcome reporting after radical cystectomy for organ-confined urothelial carcinoma of the bladder using oncological trifecta and pentafecta - Aziz, Atiqullah; Gierth, Michael; Rink, Michael; Schmid, Marianne; Chun, Felix K.; Dahlem, Roland; Roghmann, Florian; Palisaar, Rein-Jueri; Noldus, Joachim; Ellinger, Jörg; Mueller, Stefan C.; Pycha, Armin; et al. (World Journal of Urology, 2015)
Radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB) is associated with heterogeneous functional and oncological outcomes. The aim of this study was to generate trifecta and pentafecta criteria to optimize outcome reporting after RC.We interviewed 50 experts to consider a virtual group of patients (age <= 75 years, ASA score <= 3) undergoing RC for a cT2 UCB and a final histology of <=pT3pN0M0. A ranking was generated for the three and five criteria with the highest sum score. The criteria were applied to the Prospective Multicenter Radical Cystectomy Series 2011. Multivariable binary logistic regression analyses were used to evaluate the impact of clinical and histopathological parameters on meeting the top selected criteria.The criteria with the highest sum score were negative soft tissue surgical margin, lymph node (LN) dissection of at least 16 LNs, no complications according to Clavien-Dindo grade 3-5 within 90 days after RC, treatment-free time between TUR-BT with detection of muscle-invasive UCB and RC <3 months and the absence of local UCB-recurrence in the pelvis <=12 months. The first three criteria formed trifecta, and all five criteria pentafecta. A total of 334 patients qualified for final analysis, whereas 35.3 and 29 % met trifecta and pentafecta criteria, respectively. Multivariable analyses showed that the relative probability of meeting trifecta and pentafecta decreases with higher age (3.2 %, p = 0.043 and 3.3 %, p = 0.042) per year, respectively.Trifecta and pentafecta incorporate essential criteria in terms of outcome reporting and might be considered for the improvement of standardized quality assessment after RC for UCB.
EVALuna2:16328

Overcoming the language barrier: UroEvidence translates Cochrane abstracts - Schmidt, S.; Kunath, F.; Kranz, J.; Zengerling, F.; Draeger, D. L.; Kroeger, N.; Krabbe, L. -M.; Miernik, A.; Borgmann, H.; Spek, A.; Meerpohl, J.; Dahm, P.; et al. (Urologe, 2015)
EVALuna2:16332

P53 Codon 72 Polymorphism and Risk for Squamous Cell Carcinoma of the Penis: A Caucasian Case-Control Study - Stoehr, Robert; Weisser, Rebecca; Wendler, Olaf Dietrich; Giedl, Josef; Daifalla, Khalid; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Wullich, Bernd; Hartmann, Arndt (Journal of Cancer, 2018)
Squamous cell carcinoma of the penis is a rare but often aggressive disease. A large proportion of penile cancers are associated with HPV infection, mainly with HPV high-risk subtypes 16 and 18. From other HPV-related malignancies a link between a functional SNP in the p53 gene (rs1042522, p.Arg72Pro) and a higher disease risk in the presence of HPV is documented. The p53 p.Arg72 variant was described as a risk factor for developing a malignancy in combination with the presence of HPV as the p.72Arg variant is more prone to HPV E6 protein-mediated degradation than the p.72Pro variant. For penile carcinoma there are only sparse data available on this topic. We therefore analyzed the distribution of this p53 codon 72 SNP in a cohort of 107 penile cancer patients and a healthy control group (n=194) using Restriction Fragment Length Polymorphism (RFLP) analysis. After DNA isolation a PCR amplicon including the variant nucleotide was generated. Based on the variant nucleotide this amplicon can be cleaved into two parts or remain unaffected by a restriction enzyme. Subsequent electrophoresis allowed the discrimination of SNP alleles in the investigated sample. Comparison of the allelic variants revealed no significant differences in the distribution of this SNP between cases and controls (p=0,622). There was also no difference in SNP distribution between cases with/without HPV infection (p=0,558) or histologic variants (p=0.339). In order to strengthen the impact of our data we performed a combined analysis of all published data on this topic with our results. This ended up in SNP distribution data from 177 cases and 1149 controls. Overall, there were also no significant differences in the allelic distribution of the p53 codon 72 SNP between either cases and controls (p=0,914) or HPV-positive and HPV-negative cases (p=0,486). From this most comprehensive data available to date we conclude that there is no influence of the p53 codon 72 SNP on the risk of development of penile carcinoma in Caucasians even in the presence of HPV.
EVALuna2:34861

Patient Benefits of Radical Prostatectomy in Certified Prostate Cancer Centers: Comparative Results from the Multicenter IMPROVE Study - Sikic, Danijel; Fiebig, Christian; Wullich, Bernd; Wolff, Ingmar; Hoschke, Bernd; Manseck, Andreas; Gillitzer, Rolf; Burger, Maximilian; Steinestel, Julie; Harke, Nina; Löbig, Niklas; Distler, Florian A.; et al. (Urologia Internationalis, 2023)
Introduction: We investigated differences in treatment outcomes following radical prostatectomy (RP) between certified centers (CCs) and noncertified centers (nCCs) within the IMPROVE study group. Methods: A validated survey assessing various factors, including stress urinary incontinence (SUI) and decision regret (DR), was administered to 950 patients who underwent RP across 19 hospitals (12 CCs and 7 nCCs) at a median follow-up of 15 months after RP (interquartile range: 11-20). The response rate was 74%, with 703 patients participating, including 480 (68%) from CCs. Multivariate binary regression models were used to analyze differences between CCs and nCCs regarding the following binary endpoints: nerve-sparing (NS), positive surgical margins (PSM), SUI (defined as >1 safety pad), complications based on the Clavien-Dindo classification (grade ≥1, grade ≥3) and DR (>15 points indicating critical DR). Results: Considering the multivariate analysis, the rate of NS surgery was lower in CCs than in nCCs (OR = 0.52; p = 0.004). No significant differences were observed in the PSM rate (OR = 1.67; p = 0.051), SUI (OR = 1.03; p = 0.919), and DR (OR = 1.00; p = 0.990). SUI (OR 0.39; p < 0.001) and DR (OR 0.62; p = 0.026) were reported significantly less frequently by patients treated with robotic-assisted RP, which was significantly more often performed in CCs than in nCCs (68.3% vs. 18%; p < 0.001). The total complication rate was 45% lower in CCs (OR = 0.55; p = 0.004), although the number of complications requiring intervention (Clavien-Dindo classification ≥3) did not differ significantly between CCs and nCCs (OR = 2.52; p = 0.051). Conclusion: Within the IMPROVE study group, similarly favorable outcomes after RP were found in both CCs and nCCs, which, however, cannot be transferred to the general treatment landscape of PCA in Germany. Of note, robotic-assisted RP was more often performed in CCs and associated with less SUI and DR, while open prostatectomy was the treatment of choice in low-volume nCCs. Future prospective and region wide studies should also investigate the surgeon caseload and experience as well as a spillover effect of the certification process on nCCs.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Certification; German cancer society; Patient-reported outcome; Prostate cancer; Radical prostatectomy

Penile reconstruction with dermal template and vacuum therapy in severe skin and soft tissue defects caused by Fournier's gangrene and hidradenitis suppurativa - Ludolph, Ingo; Titel, Torsten; Beier, Justus; Dragu, Adrian; Schmitz, Marweh; Wullich, Bernd; Horch, Raymund E. (International Wound Journal, 2016)
The aim of this article is to improve the treatment of patients with complete skin loss of the penile shaft after Fournier's gangrene or hidradenitis suppurativa using modern biomatrices and topical negative pressure therapy. From January 2010 to December 2011, three patients with Fournier's gangrene or hidradenitis suppurativa were treated. After initial radical debridements, topical negative pressure therapy was applied for wound stabilisation. After that dermal templates (acellular dermal matrix) were used to achieve early healing and topical negative pressure-dressing in a special setting or a special foam compression bandage was used together with a urinary catheter. After integration of the dermal template, a split-thickness skin graft is used for coverage and again secured with a circular total negative pressure-dressing. In all cases, the split-thickness skin grafts healed very well applying this therapy concept. The patients were very satisfied with the functional as well as with the aesthetic outcome. We suggest a new method of staged reconstruction to successfully preserve the functionality of the penis after complete loss of the skin and soft tissue of the penile shaft using modern biomatrices and topical negative pressure therapy.
EVALuna2:15559

Performance of the Food and Drug Administration/EMA-approved programmed cell death ligand-1 assays in urothelial carcinoma with emphasis on therapy stratification for first-line use of atezolizumab and pembrolizumab - Eckstein, Markus; Erben, Philipp; Kriegmair, Maximilian C.; Worst, Thomas S.; Weiss, Cleo-Aron; Wirtz, Ralph M.; Wach, Sven; Stoehr, Robert; Sikic, Danijel; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; et al. (European Journal of Cancer, 2019)
BACKGROUND: Recently, the Food and Drug Administration (FDA)/European Medicines Agency (EMA) restricted first-line use of atezolizumab and pembrolizumab in patients with metastasised urothelial carcinoma by defining distinct programmed cell death ligand-1 cut-offs. We analysed the diagnostic performance of all FDA/EMA-approved programmed cell death ligand-1 assays with emphasis on new restrictions for first-line treatment with atezolizumab and pembrolizumab. PATIENTS AND METHODS: Two hundred fifty-one urothelial carcinomas were analysed on tissue microarrays with four cores of each tumour. Stains were performed in certified laboratories on Ventana Benchmark Ultra and Dako Link 48 autostainers. Stains were read on an assay-by-assay basis by two trained pathologists. Overall percentage agreement (OPA) was calculated across the preset cut-offs. Positive percentage agreement (PPA) and negative percentage agreement (NPA) were calculated across different scoring algorithms. Venn diagrams were constructed to illustrate discordance according to the recent FDA/EMA guidelines. RESULTS: The Dako 28-8, 22c3 and the Ventana SP263 assays showed high interassay correlation (r-range 0.83-0.91). Interassay correlation between the Ventana SP142 and the three other assays was moderate (r-range 0.66-0.75). OPA of 93.3% was achieved between the Dako 28-8, 22c3 and Ventana SP263 assays. OPA including the SP142 was 84.1%. Pooled PPA and NPA of different scoring algorithms was 89.4% and 95.3% for the Dako 28-8, 22c3 and the SP263 assays, respectively. With the SP142 assay, pooled PPA was 59.1%. The SP142 assay identifies fewer eligible patients for first-line treatment with atezolizumab/pembrolizumab. CONCLUSION: Dako 28-8, 22c3 and SP263 assays show interchangeable performance. The SP142 assay shows divergent staining results. Interassay variability leads to different detection rates of eligible patients for first-line treatment with atezolizumab and pembrolizumab.
EVALuna2:52994

Piwil 2 expression is correlated with disease-specific and progression-free survival of chemotherapy-treated bladder cancer patients - Taubert, Helge; Wach, Sven; Jung, Rudolf; Pugia, Michael; Keck, Bastian; Bertz, Simone; Nolte, Elke; Stoehr, Robert; Lehmann, Jan; Ohlmann, Carsten-H; Stöckle, Michael; Wullich, Bernd; et al. (Molecular Medicine, 2015)
Piwi-like 2 (Piwil 2) belongs to the family of Argonaute genes/proteins. The expression of Piwil 2 is associated with stem cells. A role in tumorigenesis and/or tumor progression is proposed for different cancers but not yet for bladder cancer (BCa). We investigated the Piwil 2 expression by immunohistochemistry in a cohort of 202 BCa patients treated by cystectomy and adjuvant chemotherapy. The association between Piwil 2 expression and disease-specific (DSS) or progression-free survival (PFS) was calculated using Kaplan Meier analyses and univariate/multivariate Cox's regression hazard models.In a multivariate Cox's regression, Piwil 2 expression, either in the cytoplasm or the nucleus, was significantly associated with DSS and PFS. A weak cytoplasmic staining pattern was associated with poor DSS and tumor progression (RR=2.7; P=0.004 and RR=2.4; P=0.027). Likewise,, absent nuclear Piwil 2 immunoreactivity was associated with poor DSS and tumor progression (RR=2.3; P=0.023 and RR=2.2; P=0.022). BCa patients whose tumors exhibited a combination of weak cytoplasmic and absent nuclear immunoreactivity had a 6-fold increased risk of tumor-related death (P=0.005) compared to patients with strong expression. Considering only patients with high grade G3 tumors, a 7.8-fold risk of tumor-associated death and a 3.6-fold risk of tumor progression were detected independently of the histologic tumor subtype or the chemotherapy regimen. In summary, a combination of weak cytoplasmic and absent nuclear expression of Piwil 2 is significantly associated with an increased risk of DSS and tumor progression. This implicates that Piwil 2 could be a valuable prognostic marker for high-risk BCa patients.
EVALuna2:6705

Piwi-like 1 and-2 protein expression levels are prognostic factors for muscle invasive urothelial bladder cancer patients - Eckstein, Markus; Jung, Rudolf; Weigelt, Katrin; Sikic, Danijel; Stoehr, Robert; Geppert, Carol-Immanuel; Agaimy, Abbas; Lieb, Verena; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (Scientific Reports, 2018)
Piwi-like proteins are essential for stem-cell maintenance and self-renewal in multicellular organisms. We analyzed the expression of Piwi-like 1 and Piwi-like 2 by immunohistochemistry (IHC) in 95 muscle invasive bladder cancer (MIBC) samples using tissue microarray. Application of an immunoreactive score (IRS) revealed 37 and 45 patients who were Piwi-like 1 and -2 positive (IRS > 2). IHC results were correlated with clinico-pathological and survival data. The expression of both proteins was positively correlated with each other, lymph node metastasis and expression of CK20 and GATA 3. A negative correlation for both proteins was detected for disease-specific survival (DSS), recurrence, Ki67/MIB1 proliferation index, and CK5 expression. Detection of Piwi-like 1 protein positivity was associated with poor DSS (P = 0.019; log rank test, Kaplan-Meier analysis), and in multivariate Cox's analysis (adjusted to tumor stage and tumor grade), it was an independent prognostic factor for DSS (RR = 2.16; P = 0.011). Piwi-like 2 positivity was associated with DSS (P = 0.008) and recurrence-free survival (RFS; P = 0.040), and in multivariate Cox's analysis, Piwi-like 2 positivity was an independent prognostic factor for DSS (RR = 2.46; P = 0.004) and RFS (RR = 3.0; P = 0.003). Most interestingly, in the basal type patient subgroup (CK5+/GATA3-), Piwi-like 2 positivity was associated with poorer DSS, OS and RFS (P < 0.001, P = 0.004 and P = 0.05; log rank test). In multivariate analysis, Piwi-like 2 positivity was an independent prognostic factor for DSS (RR = 12.70; P = 0.001), OS (RR = 6.62; = 0.008) and RFS (RR=13.0; P = 0.040). In summary, Piwi-like 1 and -2 positivity are associated with clinico-pathological factors and survival. Both Piwi-like proteins are suggested as biomarkers for MIBC patients.
EVALuna2:35874

Piwi-like 1 and 4 gene transcript levels are associated with clinicopathological parameters in renal cell carcinomas - Al-Janabi, Omar; Wach, Sven; Nolte, Elke; Weigelt, Katrin; Rau, Tilman; Stoehr, Christine; Legal, Wolfgang; Schick, Stefan; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2014)
Piwi-like gene family members (Piwil 1-4) are considered stem cell-associated genes/proteins. These are expressed predominantly in germline cells, but are re-expressed in different tumors. Piwil 1-4 gene expression has not previously been studied and correlated with clinicopathological parameters in renal cell carcinomas (RCC). The Piwil 1-4 transcript levels were analyzed by quantitative real-time PCR in 73 clear cell RCC (ccRCC) tissues and corresponding normal tissues. The transcript levels of Piwil 1, 2 and 4 were strongly and significantly correlated with each other, in both the tumor tissues and the normal tissues (P<0.001; Spearman's rank test). Piwil 4 gene expression was significantly higher in the ccRCC tissues than that in the corresponding normal renal tissues (P<0.001; Wilcoxon signed-rank test). When the ccRCC patient cohort was divided according to the median Piwil 1-4 expression into low- and high-expression groups and according to age into younger (<=64years) and older patient groups (>64years), the younger patients displayed significantly higher levels of Piwil 1 mRNA in comparison to the older patients (P=0.010; Fisher's exact test). Interestingly, Piwil 1 expression was left-right polarized in the normal tissues but not in the tumor tissues (P=0.004; Fisher's exact test). Altogether, associations were determined between the Piwi-like family member expression levels and clinicopathological parameters of ccRCC, suggesting a potential role for these genes/proteins in ccRCC diagnostics and tumorigenesis as well as in renal tissue embryology.
EVALuna2:6563

Piwi-like 1 protein expression is a prognostic factor for renal cell carcinoma patients - Stoehr, Christine; Steffens, Sandra; Polifka, Iris; Jung, Rudolf; Kahlmeyer, Andreas; Ivanyi, Philipp; Weber, Florian; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (Scientific Reports, 2019)
The Piwi-like genes belong to the Argonaute gene family and are conserved in plants, animals and humans. In addition to their essential role in the germ line and as stem cell-associated genes, Piwi-like proteins play a role in different cancer types but have yet to be studied in renal cell carcinoma (RCC). We investigated tissue micro arrays (TMAs) with tumor samples of two independent cohorts of RCC patients (N = 265 and N = 345); we used immunohistochemistry to assess the protein expression of Piwi-like 1. Applying an immunoreactive score (IRS), we found Piwi-like 1 positivity (IRS > 0) in 28.3% and 14.8% of the tumors in cohorts 1 and 2, respectively. Piwi-like 1 positivity was correlated with Fuhrman grade, tumor stage and the presence of distant metastasis (P < 0.005). Moreover, in univariate and multivariate analyses (adjusted to Fuhrman grade and tumor stage), Piwi-like 1 positivity was associated with a shorter cancer-specific survival in the patients in the second cohort. In addition, Piwi-like 1 expression allowed to further distinguish the RCC patients with high Fuhrman grade, high tumor stage, distant metastasis or high pre-operative levels of C-reactive protein, as Piwi-like 1 positivity was associated with a shorter cancer-specific survival in both cohorts. Our data encourage further investigations to enlighten the role of Piwi-like 1 and its function as a marker of poor prognosis in RCC patients.
CRIS-Team WoS Importer:2019-02-22

Preoperative anemia is associated with adverse outcome in patients with urothelial carcinoma of the bladder following radical cystectomy - Gierth, M.; Mayr, R.; Aziz, A.; Krieger, Stefan; Wullich, Bernd; Pycha, A.; Lodde, Michele; Salvadori, U.; Bruendl, J.; Fritsche, H. M.; Hofstaedter, F.; Pawlik, M. T.; et al. (Journal of Cancer Research and Clinical Oncology, 2015)
Radical cystectomy (RC) can be associated with significant blood loss, whereas many patients are presenting with anemia preoperatively. To date, there is a lack of data addressing the impact of preoperative anemia (PA) on survival of patients undergoing RC for urothelial carcinoma of the bladder (UCB).This retrospective multicenter study includes 684 patients with UCB undergoing RC with pelvic lymph node dissection. The median follow-up was 50 (IQR 29,78) months. Anemia was defined in line with the WHO classification (hemoglobin (Hb): male <=13 g/dL, female <=12 g/dL) and based on contemporary gender- and age-adjusted classification (Hb: white male aged <60 years: <=13.7 g/dL; >=60 years: <=13.2 g/dL; white female of all ages <=12.2 g/dL). Univariable and multivariable Cox regression analyses were used to assess the effects of PA on oncological outcomes.A total of 269 (39.3 %) and 302 (44.2 %) patients were anemic according to the WHO classification versus contemporary classification. Age, increased ECOG performance status, advanced tumor stages, lymph node metastasis, positive surgical margin and anemia were associated with disease recurrence (DR), cancer-specific mortality (CSM) and all-cause mortality (ACM). In multivariable analysis, anemia was an independent predictor of DR, CSM and ACM (WHO and/or contemporary classification). Blood transfusion was significantly associated with ACM in both classifications of anemia.PA is significantly associated with worse oncological outcome in patients undergoing RC. Based on the additional unfavorable influence of blood transfusion, this emphasizes the importance of early diagnosis and correction of anemia and implementation of alternative methods of blood volume management.
EVALuna2:16330

Preoperative geriatric assessment to predict functional outcome after major urologic operations: Results from a multicenter study - Graf, Sebastian; Lutz, Jakob; Koneval, Lukas; Kalogirou, Charis; Weiß, Sarah Christiane; Bannert, Hannes; Taubert, Helge; Wach, Sven; Gaßmann, Karl-Günter; Wullich, Bernd; Fiebig, Christian (Ejso, 2024)
Introduction: Major urological tumor surgery entails a severe risk of unexpected adverse events, persistent functional deterioration, and death in older patients. The Erlangen Index (EI) geriatric assessment tool has previously been shown to predict incomplete functional recovery following major urological tumor surgery in an elderly patient collective. We prospectively evaluated assessment tools including EI in a multicenter setting. Materials and methods: A total of 340 patients over the age of 65 were assessed prospectively before and after cystectomy, prostatectomy, or renal tumor surgery at three academic centers in Germany and Austria. Endpoints were long-term functional deterioration (Activities of daily living (ADL) measured by Barthel-Index) at day 30 and day 180, and mortality at day 180. Results: In this study 58 (17.0 %) patients underwent cystectomy, 140 (41.2 %) prostatectomy and 142 (41.8 %) a kidney tumor operation. Mean age was 74.8 years. ADL impairment as a measure of incomplete recovery at day 30 and 180 after surgery were recorded in 47.6 % and 37.4 % of cases, respectively. The EI showed good sensitivity for mortality at day 180 (reference cohort: 85 %, validation center 1: 100 %, validation center 2: 50 %) and for ADL impairment at day 180 (reference cohort 75.4 %, validation center 1 72.3 %, validation center 2 83.3 %). Conclusion: Elderly patients with a poor performance status have a high risk of persistent functional deterioration. Data from this multicenter external validation trial confirms the EI as an accurate and reliable tool to identify patients with high risk of mortality or persistent postoperative functional impairment.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Erlangen index; Frailty; Functional impairment; Geriatric assessment; Oncological surgery; Urological surgery

Preoperative hormone stimulation; does it increase hypospadias postoperative complications? - Fawzy, Mohamed; Marcou, Marios; Sennert, Michael; Wirmer, Johannes; Wullich, Bernd; T Hadidi, Ahmed (Journal of Pediatric Urology, 2023)
Aim of the study: To assess the effect of Preoperative Hormone Stimulation (PHS) on glans size in proximal hypospadias with chordee and small glans, and to determine if PHS is associated with increased postoperative complications. Patients & Methods: Between 2014 and 2021, 101 cases of proximal hypospadias with small glans (12 mm or less) were operated upon in our hospital and are the basis of this cohort. All patients underwent a standard two-stage surgical repair, undergoing a correction of the chordee in the first operation and urethroplasty in the second operation. All patients included were operated by the same surgeon. They were classified into two groups; Group A: 50 children were operated upon between 2014 and 2017 and did not receive PHS and Group B: 51 children operated between 2018 and 2021 and received PHS. Glans dimensions including Dorsal Longitudinal Length (DLL) and Glans Width (GW) were measured during the first operation. PHS was given 1–2 months before the second operation in Group B. The glans dimensions were measured again during the second operation after PHS. Follow up period ranged from 2 to 9 years (mean 5 years). Results: Following PHS a statistically significant increase in glans length (p = 0.042) and glans width (p = 0.011) was observed at the second operation, with 36 patients (70%) showing a mean glans width increase of 2.78 mm (range 2–8 mm) after receiving PHS. There was no statistically significant difference in the complication rates between the two groups (p = 0.556) with a fragility index of zero (FI = 0). Discussion: The present study separates itself from most other studies in the literature, in the fact that it has included only a specific group of proximal and perineal hypospadias with severe chordee and glans width of 12 mm or less and that glans dimensions were always objectively and accurately measured under general anesthesia. The other major difference is that PHS in our study was given after and not before the first operation. Furthermore, the fact that all patients prior to 2018 did not receive PHS and all patients after 2018 received PHS, indicates that there was no selection bias. Conclusion: This study shows that PHS results in an increase the size of the glans in 70% of patients with hypospadias and a small glans without an increase in postoperative complications.[Formula presented]
CRIS-Team Scopus Importer:2023-10-06
Keywords: Complications; Glans size; Hormone therapy; Hypospadias; Preoperative hormone stimulation; Preoperative hormone therapy

Prerequisites, skills and productivity of young academic urologists in Germany - Borgmann, H.; Bruendl, J.; Huber, J.; Ruf, C.; Schagdarsurgengin, U.; Wullich, Bernd; Salem, J. (Urologe, 2017)
To safeguard scientific and clinical progress, German urology requires properly trained junior scientists. Before initiating or continuing actions aiming at quality improvement an analysis of the status quo is necessary. To assess the conditions to pursue research, research skills and research output of junior scientists in urology in Germany. A 16-item online questionnaire was sent to 95 junior scientists in urology within the research network GeSRU Academics. Primary outcomes were the conditions to pursue research in terms of research time, research skills and sources of learning and research output as measured by peer-reviewed publications. Subpopulations were compared with respect to the number of peer-reviewed publications. Out of 78 junior scientists (82% response rate) 45% pursued research exclusively in their leisure time. Self-assessment of research skills varied from good (systematic literature search) to sufficient (grant acquisition). The main source of learning for research skills was self-study, followed by mentor, own department, courses and networks. Of the junior scientists 81% had peer-reviewed publications (median 4). The groups of junior scientists who pursued research (partially) during working hours, who had good skills and whose research skills were supported by a mentor/network had significantly more peer-reviewed publications than their counterparts. Junior scientists in urology in Germany lack protected time to pursue research and have varying research skills, which are predominantly acquired by self-study and demonstrate their first research output as peer-reviewed publications.
EVALuna2:35910

Presurgical assessments (Assessments vor Operationen) - Kahlmeyer, A.; Goebell, Peter; Wullich, Bernd (Urologe, 2019)
For the estimation of perioperative risks and mortality in the context of radical urological tumor surgery in elderly patients, the guidelines meanwhile require the use of geriatric assessments. The aim of this work is therefore to explain frequently used geriatric assessments and to give an overview of their predictive significance in radical urological tumor surgery. Comprehensive geriatric assessments provide a good description of the patient’s state of health, but are hardly feasible in clinical routine due to their complexity. It is more reasonable to use screening tools with subsequent targeted examination of high-risk patients. Special tools allow the standardized assessment of functional status, mobility, cognition, mood, nutrition, frailty, comorbidities and polypharmacy and have different prognostic significance. Evidence on the predictive value of assessments prior to radical urological tumor surgery is mainly described for the systematic classification of comorbidities. In cystectomy, the Charlson Comorbidity Index (CCI) and the American Society of Anesthesiologists (ASA) score allow an estimation of the risk of complications and mortality. The focus of assessments prior to prostatectomy is to identify patients with sufficient life expectancy to benefit from radical surgery. CCI and ASA scores as well as the Eastern Co-operative Oncology Group (ECOG) score can help to assess the risk of perioperative complications in kidney tumor surgery.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cognition; Cystectomy; Geriatric Assessments; Nephrectomy; Prostatectomy

Presurgical assessments - Kahlmeyer, A.; Goebell, Peter; Wullich, Bernd (Urologe, 2019)
For the estimation of perioperative risks and mortality in the context of radical urological tumor surgery in elderly patients, the guidelines meanwhile require the use of geriatric assessments. The aim of this work is therefore to explain frequently used geriatric assessments and to give an overview of their predictive significance in radical urological tumor surgery. Comprehensive geriatric assessments provide agood description of the patient's state of health, but are hardly feasible in clinical routine due to their complexity. It is more reasonable to use screening tools with subsequent targeted examination of high-risk patients. Special tools allow the standardized assessment of functional status, mobility, cognition, mood, nutrition, frailty, comorbidities and polypharmacy and have different prognostic significance. Evidence on the predictive value of assessments prior to radical urological tumor surgery is mainly described for the systematic classification of comorbidities. In cystectomy, the Charlson Comorbidity Index (CCI) and the American Society of Anesthesiologists (ASA) score allow an estimation of the risk of complications and mortality. The focus of assessments prior to prostatectomy is to identify patients with sufficient life expectancy to benefit from radical surgery. CCI and ASA scores as well as the Eastern Co-operative Oncology Group (ECOG) score can help to assess the risk of perioperative complications in kidney tumor surgery.
CRIS-Team WoS Importer:2019-04-23

Prognostic and Predictive Potential of CCL5 Expression in Muscle-Invasive Bladder Cancer Patients - Smolka, Cedric; Eckstein, Markus; Jung, Rudolf; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Bahlinger, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (International Journal of Molecular Sciences, 2024)
Bladder cancer (BC) is the 12th most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, prognostic and predictive markers for tumor cells and immune cells are still needed. Using a tissue microarray, we analyzed the expression of the chemokine CC motif ligand 5 (CCL5) by immunohistochemistry (IHC) in 175 muscle-invasive BC samples. The application of a single cutoff for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; positive vs. negative) revealed 75 patients (42.9%) and 123 patients (70.3%) with CCL5-positive TCs or ICs, respectively. IHC results were associated with prognostic and predictive data. Multivariate Cox regression analysis revealed that positive CCL5 staining in TCs was associated with significantly shorter disease-specific survival (DSS; RR = 1.51; p = 0.047), but CCL5-negative ICs were associated with significantly shorter overall survival (OS; RR = 1.66; p = 0.005), DSS (RR = 2.02; p = 0.001) and recurrence-free survival (RFS; RR = 1.94; p = 0.002). Adjuvant chemotherapy was favorable for patients with CCL5-negative ICs for OS (RR = 0.30; p = 0.006), DSS (RR = 0.36; p = 0.022) and RFS (RR = 0.41; p = 0.046) but not for patients with CCL5-positive ICs, except in the subgroup of N1 + N2 patients, where it was associated with better OS. We suggest that CCL5 expression can be a prognostic and predictive marker for muscle-invasive bladder cancer patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: CCL5; chemokine; chemotherapy; immune cells; muscle-invasive bladder cancer; prognosis; tumor cells

Prognostic impact of molecular muscle-invasive bladder cancer subtyping approaches and correlations with variant histology in a population-based mono-institutional cystectomy cohort - Weyerer, Veronika; Stöhr, Robert; Bertz, Simone; Lange, Fabienne; Geppert, Carol-Immanuel; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (World Journal of Urology, 2021)
Purpose Recently discovered molecular classifications for urothelial bladder cancer appeared to be promising prognostic and predictive biomarkers. The present study was conducted to evaluate the prognostic impact of molecular subtypes assessed by two different methodologies (gene and protein expression), to compare these two approaches and to correlate molecular with histological subtypes in a consecutively collected, mono-institutional muscle-invasive bladder cancer (MIBC) cohort. Methods 193 MIBC were pathologically re-evaluated and molecular subtypes were assessed on mRNA (NanoString technology, modified 21-gene-containing MDACC approach) and protein levels (immuno-histochemical [IHC] analysis of CK5, CK14, CD44, CK20, GATA3 and FOXA1). Descriptive statistical methods and uni-/multi-variable survival models were employed to analyze derived data. Results Neither gene expression nor protein-based subtyping showed significant associations with disease-specific (DSS) or recurrence-free survival (RFS). Agreement between mRNA (reference) and protein-based subtyping amounted 68.6% for basal, 76.1% for luminal and 50.0% for double-negative tumors. Histological subtypes associated with RFS in uni-variable (P = 0.03), but not in multivariable survival analyses. Tumors with variant histology predominantly showed luminal subtypes (gene expression subtyping: 36/55 cases, 65.5%; protein subtyping: 44/55 cases, 80.0%). Squamous differentiation significantly associated with basal subtypes (gene expression subtyping: 44/45 squamous cases, 97.8%; protein subtyping: 36/45 cases, 80.0%). Conclusion In our consecutive cystectomy cohort, neither gene, protein expression-based subtyping, nor histological subtypes associated with DSS or RFS in multi-variably adjusted survival analyses. Application of a limited IHC subtyping marker panel showed high concordance of 83.9% with gene expression-based subtyping, thus underlining the utility for subtyping in pathological routine diagnostics. In addition, histological MIBC subtypes are strong indicators for intrinsic subtypes.
CRIS-Team WoS Importer:2021-07-23

Prognostic impact of urokinase-type plasminogen activator system components in clear cell renal cell carcinoma patients without distant metastasis - Fuessel, Susanne; Erdmann, Kati; Taubert, Helge; Lohse-Fischer, Andrea; Zastrow, Stefan; Meinhardt, Matthias; Bluemke, Karen; Hofbauer, Lorenz; Fornara, Paolo; Wullich, Bernd; Baretton, Gustavo; Magdolen, Viktor; et al. (BMC Cancer, 2014)
Members of the urokinase-type plasminogen activator (uPA) system including uPA, its receptor uPAR and the plasminogen activator inhibitor 1 (PAI-1) play an important role in tumour invasion and progression in a variety of tumour types. Since the majority of clear cell renal cell carcinoma (ccRCC) shows distant metastasis at time of diagnosis or later, the interplay of uPA, uPAR and PAI-1 might be of importance in this process determining the patients' outcome.Corresponding pairs of malignant and non-malignant renal tissue specimens were obtained from 112 ccRCC patients without distant metastasis who underwent tumour nephrectomy. Tissue extracts prepared from fresh-frozen tissue samples by detergent extraction were used for the determination of antigen levels of uPA, uPAR and PAI-1 by ELISA. Antigen levels were normalised to protein concentrations and expressed as ng per mg of total protein.Antigen levels of uPA, uPAR, and PAI-1 correlated with each other in the malignant tissue specimens (rs=0.51-0.65; all P<0.001). Antigen levels of uPA system components were significantly higher in tissue extracts of non-organ confined tumours (pT3+4) compared to organ-confined tumours (pT1+2; all P<0.05). Significantly elevated levels of uPAR and PAI-1 were also observed in high grade ccRCC. When using median antigen levels as cut-off points, all three uPA system factors were significant predictors for disease-specific survival (DSS) in univariate Cox's regression analyses. High levels of uPA and uPAR remained independent predictors for DSS with HR=2.86 (95% CI 1.07-7.67, P=0.037) and HR=4.70 (95% CI 1.51-14.6, P=0.008), respectively, in multivariate Cox's regression analyses. A combination of high antigen levels of uPA and/or uPAR further improved the prediction of DSS in multivariate analysis (HR=14.5, 95% CI 1.88-111.1, P=0.010). Moreover, high uPA and/or uPAR levels defined a patient subgroup of high risk for tumour-related death in ccRCC patients with organ-confined disease (pT1+2) (HR=9.83, 95% CI 1.21-79.6, P=0.032).High levels of uPA and uPAR in tumour tissue extracts are associated with a significantly shorter DSS of ccRCC patients without distant metastases.
EVALuna2:16312

Prognostic impact of variant histologies in urothelial bladder cancer treated with radical cystectomy - Claps, Francesco; van de Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Hippe, Katrin; Bertz, Simone; Neuzillet, Yann; Sanders, Joyce; Otto, Wolfgang; van der Heijden, Michiel S.; Jewett, Michael A.S.; et al. (Bju International, 2023)
Objectives: To evaluate variant histologies (VHs) for disease-specific survival (DSS) in patients with invasive urothelial bladder cancer (BCa) undergoing radical cystectomy (RC). Materials and Methods: We analysed a multi-institutional cohort of 1082 patients treated with upfront RC for cT1-4aN0M0 urothelial BCa at eight centres. Univariable and multivariable Cox’ regression analyses were used to assess the effect of different VHs on DSS in overall cohort and three stage-based analyses. The stages were defined as ‘organ-confined’ (≤pT2N0), ‘locally advanced’ (pT3-4N0) and ‘node-positive’ (pTanyN1-3). Results: Overall, 784 patients (72.5%) had pure urothelial carcinoma (UC), while the remaining 298 (27.5%) harboured a VH. Squamous differentiation was the most common VH, observed in 166 patients (15.3%), followed by micropapillary (40 patients [3.7%]), sarcomatoid (29 patients [2.7%]), glandular (18 patients [1.7%]), lymphoepithelioma-like (14 patients [1.3%]), small-cell (13 patients [1.2%]), clear-cell (eight patients [0.7%]), nested (seven patients [0.6%]) and plasmacytoid VH (three patients [0.3%]). The median follow-up was 2.3 years. Overall, 534 (49.4%) disease-related deaths occurred. In uni- and multivariable analyses, plasmacytoid and small-cell VHs were associated with worse DSS in the overall cohort (both P = 0.04). In univariable analyses, sarcomatoid VH was significantly associated with worse DSS, while lymphoepithelioma-like VH had favourable DSS compared to pure UC. Clear-cell (P = 0.015) and small-cell (P = 0.011) VH were associated with worse DSS in the organ-confined and node-positive cohorts, respectively. Conclusions: More than 25% of patients harboured a VH at time of RC. Compared to pure UC, clear-cell, plasmacytoid, small-cell and sarcomatoid VHs were associated with worse DSS, while lymphoepithelioma-like VH was characterized by a DSS benefit. Accurate pathological diagnosis of VHs may ensure tailored counselling to identify patients who require more intensive management.
CRIS-Team Scopus Importer:2023-03-03
Keywords: #BladderCancer; #blcsm; #uroonc; #utuc; bladder urothelial carcinoma; prognosis; radical cystectomy; survival; variant histology

Prognostic markers in invasive bladder cancer: FGFR3 mutation status versus P53 and KI-67 expression: a multi-center, multi-laboratory analysis in 1058 radical cystectomy patients - Mertens, Laura S.; Claps, Francesco; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (Urologic Oncology-Seminars and Original Investigations, 2022)
Objectives: To determine the association between the FGFR3 mutation status and immuno-histochemistry (IHC) markers (p53 and Ki-67) in invasive bladder cancer (BC), and to analyze their prognostic value in a multicenter, multi-laboratory radical cystectomy (RC) cohort. Patients and methods: We included 1058 cN0M0, chemotherapy-naive BC patients who underwent RC with pelvic lymph-node dissection at 8 hospitals. The specimens were reviewed by uro-pathologists. Mutations in the FGFR3 gene were examined using PCR-SNaPshot; p53 and Ki-67 expression were determined by standard IHC. FGFR3 mutation status as well as p53 (cut-off>10%) and Ki-67 (cut-off>20%) expression were correlated to clinicopathological parameters and disease specific survival (DSS). Results: pT-stage was
CRIS-Team Scopus Importer:2022-03-04
Keywords: Bladder; Cancer; Cystectomy; FGFR3; Immunohistochemistry; Ki-67; Mutation; p53; Urothelial carcinoma

Prognostic models for predicting overall survival in metastatic castration-resistant prostate cancer: a systematic review - Pinart, M.; Kunath, F.; Lieb, V.; Tsaur, I.; Wullich, Bernd; Schmidt, Stefanie (World Journal of Urology, 2018)
PURPOSE: Prognostic models are developed to estimate the probability of the occurrence of future outcomes incorporating multiple variables. We aimed to identify and summarize existing multivariable prognostic models developed for predicting overall survival in patients with metastatic castration-resistant prostate cancer (mCRPC). METHODS: The protocol was prospectively registered (CRD42017064448). We systematically searched Medline and reference lists up to May 2018 and included experimental and observational studies, which developed and/or internally validated prognostic models for mCRPC patients and were further externally validated or updated. The outcome of interest was overall survival. Two authors independently performed literature screening and quality assessment. RESULTS: We included 12 studies that developed models including 8750 patients aged 42-95 years. Models included 4-11 predictor variables, mostly hemoglobin, baseline PSA, alkaline phosphatase, performance status, and lactate dehydrogenase. Very few incorporated Gleason score. Two models included predictors related to docetaxel and mitoxantrone treatments. Model performance after internal validation showed similar discrimination power ranging from 0.62 to 0.73. Overall survival models were mainly constructed as nomograms or risk groups/score. Two models obtained an overall judgment of low risk of bias. CONCLUSIONS: Most models were not suitable for clinical use due to methodological shortcomings and lack of external validation. Further external validation and/or model updating is required to increase prognostic accuracy and clinical applicability prior to their incorporation in clinical practice as a useful tool in patient management.
EVALuna2:35929

Prognostic Role of FGFR Alterations and FGFR mRNA Expression in Metastatic Urothelial Cancer Undergoing Checkpoint Inhibitor Therapy - Tully, Karl H.; Jütte, Hendrik; Wirtz, Ralph M.; Jarczyk, Jonas; Santiago-Walker, Ademi; Zengerling, Friedemann; Breyer, Johannes; Sikic, Danijel; Kriegmair, Maximilian C.; von Hardenberg, Jost; Wullich, Bernd; Taubert, Helge; et al. (Urology, 2021)
Objective: To examine the disease-specific survival(DSS) after checkpoint inhibitor(CPI) therapy based on FGFR alterations and FGFR mRNA expression levels in patients with metastatic urothelial cancer(mUCa) within a multi-center cohort. Methods: Within a cohort of 72 patients with mUCa from five academic centers in Germany FGFR alterations, as well as FGFR1-4 mRNA expression levels in tumor samples from the primary tumor or metastatic sites. Spearman rank correlations, logistic regression, as well as Kaplan-Meier survival analyses and univariate Cox proportional hazards regression models were employed to examine the impact of different FGFR patterns on the DSS after CPI treatment. Results: FGFR3 mutations or gene fusions (gene alterations) were detected in 16.9% of all samples. Patients with or without FGFR3 gene alterations did not show different oncological outcomes undergoing CPI treatment. Low expression of FGFR2 mRNA alone, as well as the combination of either low FGFR2mRNA expression and FGFR3 gene alteration or high FGFR3mRNA expression (P = 0.027), identified a subgroup of patients with unfavorable outcomes, comprising 40% of the total cohort. This trend was also observed in univariate Cox proportional hazards regression analysis(FGFR3 gene alteration: Hazard ratio(HR) 5.33, 95%Confidence interval(CI)1.76-15.0, P = 0.004; FGFR3mRNA expression:HR 3.04, 95%CI 1.40-7.13, P = 0.005). Conclusion: Assessment of FGFR mRNA expression identified a high-risk subgroup of patients with mUCa. These patients showing overexpression of FGFR3 mRNA were found to have unfavorable DSS after CPI treatment. Using this approach may be suitable for identifying a patient population with poor response to CPI treatment, which may benefit from early FGFR inhibition.
CRIS-Team Scopus Importer:2021-07-30

Prognostic role of FGFR Mutations and FGFR mRNA expression in metastatic urothelial cancer treated with anti-PD(L1) inhibitors in first and second-line setting - Roghmann, F.; Wirtz, R.; Jarczyk, J.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; Zengerling, F.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Progranulin (GP88) is an independent prognostic factor for prostate cancer patients - Taubert, Helge; Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2024)
BACKGROUND: Grading of muscle-invasive bladder cancer (MIBC) according to the current World Health Organization (WHO) criteria is controversial due to its limited prognostic value. All MIBC cases except a tiny minority are of high grade. OBJECTIVE: To develop a prognostic histological scoring system for MIBC integrating histomorphological phenotype, stromal tumor-infiltrating lymphocytes (sTILs), tumor budding, and growth and spreading patterns. DESIGN, SETTING, AND PARTICIPANTS: Tissue specimens and clinical data of 484 patients receiving cystectomy and lymphadenectomy with curative intent with or without adjuvant chemotherapy. Histomorphological phenotypes, sTILs, tumor budding, and growth and spreading patterns were evaluated and categorized into four grade groups (GGs). GGs were correlated with molecular subtypes, immune infiltration, immune checkpoint expression, extracellular matrix (ECM) remodeling, and epithelial-mesenchymal transition (EMT) activity. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: GGs were associated with overall (OS), disease-specific (DSS), and progression-free (PFS) survival in univariable and multivariable analyses. Association with biological features was analyzed with descriptive statistics. RESULTS AND LIMITATIONS: Integration of two histomorphological tumor groups, three sTILs groups, three tumor budding groups, and four growth/spread patterns yielded four novel GGs that had high significance in the univariable survival analysis (OS, DSS, and PFS). GGs were confirmed as independent prognostic predictors with the greatest effect in the multivariable Cox regression analysis. Correlation with molecular data showed a gradual transition from basal to luminal subtypes from GG1 to GG4; a gradual decrease in survival, immune infiltration, and immune checkpoint activity; and a gradual increase in ECM remodeling and EMT activity. CONCLUSIONS: We propose a novel, prognostically relevant, and biologically based scoring system for MIBC in cystectomies applicable to routine pathological sections. PATIENT SUMMARY: We developed a novel approach to assess the aggressiveness of advanced bladder cancer, which allows improved risk stratification compared with the method currently proposed by the World Health Organization.
EVALuna2:539845

Prospective evaluation of geriatric assessment tools as predictors of functional outcome in old patients undergoing major urologic tumor surgery - Kahlmeyer, A.; Losensky, Wencke; Sikic, D.; Wach, S.; Ritt, M.; Goebell, Peter; Keck, Bastian; Wullich, Bernd (2018)
EVALuna2:35900

Protein levels of Piwi-like 1 and-2 protein are prognostic factors for muscle invasive urothelial bladder cancer patients - Eckstein, Markus; Jung, Rudolf; Weigelt, Katrin; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Agaimy, Abbas; Lieb, Verena; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Pure large nested variant of urothelial carcinoma (Lnuc) is the prototype of an fgfr3 mutated aggressive urothelial carcinoma with luminal-papillary phenotype - Weyerer, Veronika; Eckstein, Markus; Compérat, Eva; Juette, Hendrik; Gaisa, Nadine T.; Allory, Yves; Stöhr, Robert; Wullich, Bernd; Rouprêt, Morgan; Hartmann, Arndt; Bertz, Simone (Cancers, 2020)
Since 2016, large nested urothelial carcinoma (LNUC) has been included within the WHO classification of urothelial tumors. Limited reports with mainly small case series have confirmed the malignant behavior of LNUC despite its bland morphological appearance. We evaluated, for the first time, markers for new immunooncological or targeted therapies including FGFR3 mutational status and PD-L1 status, the frequency of TERT-promoter mutations and the molecular subtype in a cohort of 25 LNUC using SNaPshot analysis and immunohistochemistry. Of the 25 cases, 17 were pure LNUC, with 13 showing an additional exophytic papillary/papillary-like component. Seven mixed LNUCs presented areas of classical nested variant urothelial carcinoma (NVUC) and one showed a component of conventional urothelial carcinoma. Of the 17 evaluable pure LNUCs, 16 were FGFR3-mutated with identical mutations in their concomitant papillary/papillary-like components. An FGFR3 mutation was found in 1/7 evaluable mixed LNUCs combined with NVUC. TERT-promoter mutations were detected in 86.7% pure and 83.3% mixed tumors. Immunohistochemistry revealed a luminal phenotype; PD-L1 was negative in the majority of tumor cells and tumor-associated immune cells. Pure LNUC is a prime example of a luminal, FGFR3-mutated, mostly PD-L1-negative tumor. In contrast, FGFR3 mutations seem to be rare in mixed LNUC, which may indicate a different pathway of tumor development.
CRIS-Team Scopus Importer:2020-04-14
Keywords: FGFR3 mutation; Large nested variant; LNUC; Luminal subtype; Urothelial carcinoma

Quantification of Nighttime Micturition with an Ambulatory Sensor-Based System - Huppert, Verena; Paulus, Jan; Paulsen, Ute; Burkart, Martin; Wullich, Bernd; Eskofier, Björn (IEEE Journal of Biomedical and Health Informatics, 2015)
Among elderly males, benign prostate syndrome (BPS) is the most common urinary disorder. Nocturia is one of the major symptoms of BPS and has a considerable influence on quality of life (QoL). For assessment of BPS (including nocturia), the International Prostate Symptom Score (IPSS) is widely used, but questionnaires are prone to bias. To date, there is no objective measurement system available for nocturia. In this study, we present an unobtrusive and non-stigmatizing device for objective measurement of nighttime micturition. In a preliminary study of 6 males diagnosed with BPS and nighttime micturition >= 2 times, we showed that the device is accurate, with an average misdetection rate of 0.32 events and a mean absolute deviation of 3.8% when comparing the average number of nighttime micturition occurrences. In this extended study, an additional 9 males were recorded and data from an occupancy sensor were also included. The results of the preliminary study were confirmed with an average misdetection rate of 0.33 events and a mean absolute deviation of 9.1%. The system can therefore be used to objectively measure nighttime micturition, and thereby provide the basis for treatment, e.g., medication efficacy assessment.
EVALuna2:16321

Reduced Recurrence Rates Are Associated with Photodynamic Diagnostics Compared to White Light after Extended Transurethral Resection of Bladder Tumors - Marquardt, Alexander; Richterstetter, Mario; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Lieb, Verena; Bellut, Laura; Wach, Sven; Apel, Hendrik (Life, 2022)
One pillar in treating non-muscle-invasive bladder cancer (NMIBC) is the complete and high-quality transurethral resection of the primary tumor (TURBT). However, even after a high-quality primary resection, the residual tumor risk is considerable, thus requiring a re-TURBT. Resections performed with the aid of a photodynamic diagnostics report improved recurrence-free survival rates and increased detection rates of carcinoma in situ (CIS). This monocentric retrospective study reports on patients treated with an extended TURBT procedure using conventional white-light cystoscopy or photodynamic diagnostics (PDD). Only patients undergoing a TURBT resection for their primary tumor were included in the statistical analysis. Recurrence-free survival and overall survival were the clinical endpoints. Mann-Whitney U tests and chi-squared tests were used for descriptive intergroup comparisons. The associations with overall survival and recurrence-free survival were determined by univariate and multivariate analyses. The test results were considered significant when p was < 0.05. In comparison to conventional white-light cystoscopy, PDD increased the detection rates of CIS (p = 0.004) and tumor multifocality (p = 0.005) and led to reduced residual tumor incidence at the primary resection site (p < 0.001). Likewise, tumor recurrence rates were reduced in the PDD cohort (p < 0.001). Patient age and the presence of residual tumor at the primary resection site were identified as independent predictors of overall survival. For recurrence-free survival, only the PDD resection method was an independent predictor (HR = 0.43; p < 0.001). In summary, we demonstrated that the utilization of PDD techniques was associated with improved detection rates of CIS and multifocal tumors and with reduced recurrence rates. The extended resection protocol allowed us to determine that PDD resections lead to a reduced residual tumor rate at the initial resection site. This residual tumor state at the resection site, determined by extended TURBT, became an independent predictor of long-term survival. On the other hand, the PDD technique was confirmed as the only independent predictor of recurrence-free survival.
CRIS-Team WoS Importer:2022-06-10

Renal transplantation in urinary diversions Nierentransplantation in Harnableitungen - Sikic, D.; Richterstetter, M.; Wullich, Bernd; Apel, Hendrik (Urologe, 2019)
Renal transplantations in augmented bladders or urinary diversions are rare, accounting for only 1–2% of all renal transplantations. In most cases a dysfunctional lower urinary tract is the cause of end-stage renal disease in these patients; therefore recovery of the lower urinary tract is mandatory for long-term graft survival. Usually, urinary diversion is timed several months prior to renal transplantation. Beside renal transplantations into an ileum conduit, renal transplantations in continent urinary diversions have become increasingly popular. The most frequent complications are bacteriuria and urinary tract infections, which usually do not lead to graft loss when treated correctly with antibiotics. Long-term outcome of renal transplantations in urinary diversions is comparable to transplantations in healthy native bladders.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Conduit; Cystectomy; Immunosuppression; Neobladder; Renal insufficiency

Renal transplantation: Opportunities and risks for medical refugees - Mammadova, Dilbar; Hirsch, K.; Schwaiger, Brigitte; Wullich, Bernd; Rascher, Wolfgang (Urologe, 2018)
BACKGROUND: Families with children and adolescents with end-stage renal disease came to Germany from the former Eastern Bloc countries before the wave of refugees in 2015, in order to enable their children to survive with adequate kidney replacement therapy and in the best case a kidney transplant. METHODS: In a case study, medical records of 4 childen and adolescents were retrospectively analyzed. These patients who fled to Germany for the treatment of terminal renal failure applied for asylum and were successfully transplanted after the usual waiting period. RESULTS: Four of the eight children and adolescents who came to Erlangen for treatment of terminal renal failure between 2003 and 2013 received a functioning kidney transplant (deceased donor kidney) after dialysis therapy was difficult due to lack of compliance to drug and dietary recommendations such as fluid restriction. Since children and adolescents are treated with chronic dialysis only with the aim of kidney transplantation, a living donation was discussed but was not possible for medical reasons. 3 recipients are symptom-free with a functional graft. DISCUSSION: The case study demonstrates that children and adolescents fleeing to Germany due to their end stage renal disease are better integrated after kidney transplantation, have better chances of obtaining a good education and can be expected to live independently with their own income in the future.
EVALuna2:35726

Report of the 24th annual conference of the Working Group Kidney Transplantation of the German Society of Urology in Erlangen - Apel, Hendrik; Putz, J.; Fornara, P.; Friedersdorff, F.; Dreikorn, K.; Stoeckle, M.; Wullich, Bernd (Urologe, 2017)
EVALuna2:16355

Results of Renal Transplantation on Alloplastic Arterial Grafts - Sagban, Tolga Atilla; Regus, Susanne; Heller, Katharina; Jacobi, Johannes; Apel, Hendrik; Keck, Bastian; Richterstetter, Mario; Eckardt, Kai-Uwe; Wullich, Bernd; Lang, Werner (Urologia Internationalis, 2016)
The aim of this retrospective study was to report results of a consecutive series of kidney transplant patients in whom the renal artery was implanted on a prosthetic vascular graft (PVG).Between January 2011 and December 2014, 208 deceased donor renal transplantations (68 female, 140 male, mean age 52, SD 16 years) were performed. Medical charts and outpatient clinical records of patients who had undergone renal artery implantation on a PVG were reviewed. Extensive literature research added to our 4 patients further 170 published cases during 1989 and 2015 and was compared with regular transplanted patients. Data on patient characteristics, prior vascular procedures, postoperative and long-term outcome were collected.Patients with transplant renal artery anastomosis on a PVG were 4 years older than the control group. Function of the graft was similar in these patients compared to regular renal transplant patients. Resistance indices assessed in our clinic over the entire follow-up period showed also no significant difference between the 2 groups. Thirty-day mortality was 6% (none in our group), which occurred mostly in combination when renal transplantation and PVG replacement was performed simultaneously.Grafting of the renal artery to a PVG is feasible and yields good results, despite the technical difficulties involved.
EVALuna2:3839

Retrospective histological evaluation of orchiectomy specimens following testicular torsion reveals a 10% incidence of reversible injury. Is it time for a change of strategy? - Marcou, Marios; Hartmann, Arndt; Wullich, Bernd; Apel, Hendrik; Hirsch-Koch, Karin (Andrology, 2022)
BackgroundAccording to standard medical practice, immediate orchiectomy is advised in the case of a non-viable testis following testicular torsion. Because of the lack of objective criteria in the evaluation of testicular viability, the fate of the testis solely depends on the discretion and experience of the surgeon. ObjectiveIn this study, we retrospectively reassess the management of patients with testicular torsion in our center, and we ask the question, from a retrospective point of view, of whether the decision to perform orchiectomy has always been correct. Materials and methodsWe retrospectively reviewed all cases of patients with testicular torsion who underwent surgery in our center between 2001 and 2021. All orchiectomy specimens were reevaluated and graded by an experienced pathologist using the Mikuz grading system. ResultsImmediate orchiectomy was performed in 48 of the 136 patients (35%). Five (10.4%) of the 48 orchiectomy specimens were categorized as "grade 1," and 17 (35.4%) were categorized as "grade 2." The time between the onset of symptoms and surgical exploration exceeded 12 h in three of the five patients with a "grade 1" testicular injury, and in one case, it even exceeded 24 h. Discussion"Grade 1" testicular injury is potentially reversible, whereas the fate of a testis with a "grade 2" testicular injury remains unknown. Whether and to what extent partial testicular tissue salvage in a "grade 2" injury is still possible remain unclear. ConclusionsOur results indicate that at least 10% of the testicles removed in our center could, from a retrospective point of view, have been salvaged. Our study further demonstrated that the duration of symptoms is not an absolute indicator of testicular damage and that the decision of whether orchiectomy should be performed, based simply on the subjective macroscopic image of the affected testis, is not always correct.
CRIS-Team WoS Importer:2023-01-20

Rhabdoid and Undifferentiated Phenotype in Renal Cell Carcinoma: Analysis of 32 Cases Indicating a Distinctive Common Pathway of Dedifferentiation Frequently Associated With SWI/SNF Complex Deficiency - Agaimy, Abbas; Cheng, Liang; Egevad, Lars; Feyerabend, Bernd; Hes, Ondrej; Keck, Bastian; Pizzolitto, Stefano; Sioletic, Stefano; Wullich, Bernd; Hartmann, Arndt (American Journal of Surgical Pathology, 2017)
Undifferentiated (anaplastic) and rhabdoid cell features are increasingly recognized as adverse prognostic findings in renal cell carcinoma (RCC), but their molecular pathogenesis has not been studied sufficiently. Recent studies identified alterations in the Switch Sucrose nonfermentable (SWI/SNF) chromatin remodeling complex as molecular mechanisms underlying dedifferentiation and rhabdoid features in carcinomas of different organs. We herein have analyzed 32 undifferentiated RCCs having in common an undifferentiated (anaplastic) phenotype, prominent rhabdoid features, or both, irrespective of the presence or absence of conventional RCC component. Cases were stained with 6 SWI/SNF pathway members (SMARCB1, SMARCA2, SMARCA4, ARID1A, SMARCC1, and SMARCC2) in addition to conventional RCC markers. Patients were 20 males and 12 females aged 32 to 85 years (mean, 59). A total of 22/27 patients with known stage presented with >=pT3. A differentiated component varying from microscopic to major component was detected in 20/32 cases (16 clear cell and 2 cases each chromophobe and papillary RCC). The undifferentiated component varied from rhabdoid dyscohesive cells to large epithelioid to small monotonous anaplastic cells. Variable loss of at least 1 SWI/SNF complex subunit was noted in the undifferentiated/rhabdoid component of 21/32 cases (65%) compared with intact or reduced expression in the differentiated component. A total of 15/17 patients (88%) with follow-up died of metastatic disease (mostly within 1 y). Only 2 patients were disease free at last follow-up (1 and 6 y). No difference in survival, age distribution, or sex was observed between the SWI/SNF-deficient and the SWI/SNF-intact group. This is the first study exploring the role of SWI/SNF deficiency as a potential mechanism underlying undifferentiated and rhabdoid phenotype in RCC. Our results highlight the association between the aggressive rhabdoid phenotype and the SWI/SNF complex deficiency, consistent with studies on similar neoplasms in other organs. Thorough sampling of such tumors that are usually huge and locally advanced is necessary for recognizing the clone of origin and hence for proper subtyping and also for differentiating them from undifferentiated urothelial carcinoma.
EVALuna2:6840

Risk and timing of biochemical recurrence in pT3aN0/Nx prostate cancer with positive surgical margin - A multicenter study - Karl, Alexander; Buchner, Alexander; Tympner, Christiane; Kirchner, Thomas; Ganswindt, Ute; Belka, Claus; Ganzer, Roman; Wieland, Wolf; Eder, Fabian; Hofstaedter, Ferdinand; Schilling, David; Sievert, Karl-Dietrich; et al. (Radiotherapy and Oncology, 2015)
Positive surgical margins (PSM) after radical prostatectomy have been shown to be associated with impaired outcome. In pT3pN0 patients with PSM either immediate radiotherapy or clinical and biological monitoring followed by salvage radiotherapy is recommended by the latest guidelines of the European Association of Urology.A retrospective, multicenter study of eight urological centers was conducted on 536 prostatectomy patients with pT3aN0/NxR1 tumors and no neoadjuvant/adjuvant therapy. A pathological re-review of all prostate specimens was performed. Association of clinical and pathological features with biochemical recurrence (BCR) was analyzed using univariate and multivariate analysis.With 48months median follow-up, BCR occurred in 39.7%. Preoperative PSA value, performance of pelvic lymph node dissection and Gleason score were significantly associated with BCR. In multivariate analysis, Gleason score was the only independent prognostic factor (p<0.001) for BCR. Five-year BCR-free survival rates were 74%, 70%, 38%, and 51% with Gleason score 6, 3+4=7a, 4+3=7b, and 8-10, respectively.In pT3aN0/NxR1 patients with no adjuvant/neoadjuvant treatment, Gleason Score permits independent prediction of the risk for BCR. These findings could help to estimate and discuss the individual risk for BCR with our patients on an individual basis.
EVALuna2:6761

Risk Factor Analysis for Long-Term Graft Survival Following Pediatric Kidney Transplantation: The Importance of Pretransplantation Time on Dialysis and Donor/Recipient Age Difference - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2023)
Recognizing risk factors that may negatively affect long-term graft survival following pediatric kidney transplantation is a key element in the decision-making process during organ allocation. We retrospectively reassessed all cases of pediatric kidney transplantation performed in our center in the last 20 years with the aim of determining baseline characteristics that could be identified as prognostic risk factors for long-term graft survival. Between 2001 and 2020, a total of 91 kidney transplantations in children under the age of 18 years were undertaken in our center. Early graft failure was observed in six of the 91 patients (7%). The median follow-up of the remaining 85 children was 100 months, and the overall kidney graft survival rates at 5, 10, 15 and 20 years were 85.2%, 71.4%, 46.0% and 30.6%, respectively. Small children with a body surface area of <1 m2 were significantly associated with better long-term graft survival outcomes, while adolescents aged more than twelve years showed poorer graft survival rates than younger children. Body surface area of the recipient of ≥1 m2, pretransplantation duration of the recipient on dialysis ≥18 months, hemodialysis prior to transplantation and donor/recipient age difference of ≥25 years were significantly associated with poorer long-term graft survival.
CRIS-Team Scopus Importer:2023-12-08
Keywords: age difference; children; graft survival; kidney transplantation; renal dialysis

Risk factors associated with positive surgical margins’ location at radical cystectomy and their impact on bladder cancer survival - Claps, Francesco; Van De Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Boormans, Joost L.; Eckstein, Markus; Mertens, Laura S.; Boeve, Egbert R.; Neuzillet, Yann; Burger, Maximilian; Pouessel, Damien; Trombetta, Carlo; et al. (World Journal of Urology, 2021)
Purpose: To evaluate the risk factors associated with positive surgical margins' (PSMs) location and their impact on disease-specific survival (DSS) in patients with bladder cancer (BCa) undergoing radical cystectomy (RC). Methods: We analyzed a large multi-institutional cohort of patients treated with upfront RC for non-metastatic (cT1-4aN0M0) BCa. Multivariable binomial logistic regression analyses were used to assess the risk of PSMs at RC for each location after adjusting for clinicopathological covariates. The Kaplan–Meier method was used to estimate DSS stratified by margins’ status and location. Log-rank statistics and Cox’ regression models were used to determine significance. Results: A total of 1058 patients were included and 108 (10.2%) patients had PSMs. PSMs were located at soft-tissue, ureter(s), and urethra in 57 (5.4%), 30 (2.8%) and 21 (2.0%) patients, respectively. At multivariable analysis, soft-tissue PSMs were independently associated with pathological stage T4 (pT4) (Odds ratio (OR) 6.20, p < 0.001) and lymph-node metastases (OR 1.86, p = 0.04). Concomitant carcinoma-in-situ (CIS) was an independent risk factor for ureteric PSMs (OR 6.31, p = 0.003). Finally, urethral PSMs were independently correlated with pT4-stage (OR 5.10, p = 0.01). The estimated 3-years DSS rates were 58.2%, 32.4%, 50.1%, and 40.3% for negative SMs, soft-tissue-, ureteric- and urethral PSMs, respectively (log-rank; p < 0.001). Conclusions: PSMs’ location represents distinct risk factors’ patterns. Concomitant CIS was associated with ureteric PSMs. Urethral and soft-tissue PSM showed worse DSS rates. Our results suggest that clinical decision-making paradigms on adjuvant treatment and surveillance might be adapted based on PSM and their location.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Bladder; Cancer; Cystectomy; Margin; Soft tissue; Ureter; Urethra; Urothelial carcinoma

Risk of penile tumor development in Caucasian individuals is independent of the coding variant rs7208422 in the TMC8 (EVER2) gene - Stöhr, Robert; Wendler, Olaf Dietrich; Giedl, Josef; Richter, Georg; Campean, Valentina; Burger, Maximilian; Bertz, Simone; Hartmann, Arndt; Gaisa, Nadine T.; Wullich, Bernd (Molecular and Clinical Oncology, 2021)
Genetic variation in the transmembrane channel-like (TMC)6/TMC8 region has been linked to beta-type human papillomavirus (HPV) infection and squamous cell carcinoma (SCC) of the skin and the head and neck, alpha-type HPV persistence and progression to cervical cancer. The functional variant rs7208422 of the TMC8 gene was suggested to have a high impact on susceptibility to beta-papillomaviruses and their oncogenic potential and to also have an influence on alpha-type HPV-related disease. The aim of the present study was to evaluate a possible influence of rs7208422 on penile cancer risk, a known alpha-type HPV-related malignancy. Therefore, the distribution of rs7208422 was determined by direct Sanger sequencing of 104 Caucasian penile SCC cases and compared to data of 3,810 controls taken from the literature. HPV detection was performed by usage of GP5+/6+ primers and subtype-specific PCR. It was observed that the distribution of rs7208422 followed the Hardy Weinberg equilibrium in both cases and controls. HPV DNA was detected in 39% of the penile SCC cases. Overall, there was no significant difference in the distribution of rs7208422 neither between cases and controls (P=0.726) nor between HPV-positive and-negative penile SCC cases (P=0.747). There was also no association between rs7208422 genotypes and age of disease onset (P=0.740). In conclusion, the present data argue against a significant impact of rs7208422 on the risk for the development of penile SCC in Caucasians. Even in combination with the HPV status, the SNP appears not to influence the risk of penile SCC in HPV-positive cases.
CRIS-Team WoS Importer:2021-11-26

Risk stratification for locoregional recurrence after radical cystectomy for urothelial carcinoma of the bladder - Novotny, Vladimir; Froehner, Michael; May, Matthias; Protzel, Chris; Hergenroether, Katrin; Rink, Michael; Chun, Felix K.; Fisch, Margit; Roghmann, Florian; Palisaar, Rein-Juri; Noldus, Joachim; Gierth, Michael; et al. (World Journal of Urology, 2015)
To externally validate the Christodouleas risk model incorporating pathological tumor stage, lymph node (LN) count and soft tissue surgical margin (STSM) and stratifying patients who develop locoregional recurrence (LR) after radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB). In addition, we aimed to generate a new model including established clinicopathological features that were absent in the Christodouleas risk model.Prospectively assessed multicenter data from 565 patients undergoing RC for UCB in 2011 qualified for final analysis. For the purpose of external validation, risk group stratification according to Christodouleas was performed. Competing-risk models were calculated to compare the cumulative incidences of LR after RC.After a median follow-up of 25 months (interquartile range 19-29), the LR-rate was 11.5 %. The Christodouleas model showed a predictive accuracy of 83.2 % in our cohort. In multivariable competing-risk analysis, tumor stage >=pT3 (HR 4.32, p < 0.001), positive STSM (HR 2.93, p = 0.005), lymphovascular invasion (HR 3.41, p < 0.001), the number of removed LNs <10 (HR 2.62, p < 0.001) and the administration of adjuvant chemotherapy (HR 0.40, p = 0.008) independently predicted the LR-rate. The resulting risk groups revealed significant differences in LR-rates after 24 months with 4.8 % for low-risk patients, 14.7 % for intermediate-risk patients and 38.9 % for high-risk patients (p < 0.001 for all), with a predictive accuracy of 85.6 %, respectively.The Christodouleas risk model has been successfully externally validated in the present prospective series. However, this analysis finds that overall model performance may be improved by incorporating lymphovascular invasion. After external validation of the newly proposed risk model, it may be used to identify patients who benefit from an adjuvant therapy and suit for inclusion in clinical trials.
EVALuna2:16294

RNA sequencing of collecting duct renal cell carcinoma suggests an interaction between miRNA and target genes and a predominance of deregulated solute carrier genes - Wach, Sven; Taubert, Helge; Weigelt, Katrin; Hase, Nora; Köhn, Marcel; Misiak, Danny; Hüttelmaier, Stefan; Stöhr, Christine G.; Kahlmeyer, Andreas; Haller, Florian; Vera, Julio; Hartmann, Arndt; et al. (Cancers, 2020)
Collecting duct carcinoma (CDC) is a rare renal cell carcinoma subtype with a very poor prognosis. There have been only a few studies on gene expression analysis in CDCs. We compared the gene expression profiles of two CDC cases with those of eight normal tissues of renal cell carcinoma patients. At a threshold of |log2fold-change| ≥ 1, 3349 genes were upregulated and 1947 genes were downregulated in CDCs compared to the normal samples. Pathway analysis of the deregulated genes revealed that cancer pathways and cell cycle pathways were most prominent in CDCs. The most upregulated gene was keratin 17, and the most downregulated gene was cubilin. Among the most downregulated genes were four solute carrier genes (SLC3A1, SLC9A3, SLC26A7, and SLC47A1). The strongest negative correlations between miRNAs and mRNAs were found between the downregulated miR-374b-5p and its upregulated target genes HIST1H3B, HK2, and SLC7A11 and between upregulated miR-26b-5p and its downregulated target genes PPARGC1A, ALDH6A1, and MARC2. An upregulation of HK2 and a downregulation of PPARGC1A, ALDH6A1, and MARC2 were observed at the protein level. Survival analysis of the cancer genome atlas (TCGA) dataset showed for the first time that low gene expression of MARC2, cubilin, and SLC47A1 and high gene expression of KRT17 are associated with poor overall survival in clear cell renal cell carcinoma patients. Altogether, we identified dysregulated protein-coding genes, potential miRNA-target interactions, and prognostic markers that could be associated with CDC.
CRIS-Team Scopus Importer:2020-01-10
Keywords: Collecting duct carcinoma; RNA sequencing; Solute carrier proteins

Role of two single nucleotide polymorphisms in secreted frizzled related protein 1 and bladder cancer risk - Rogler, Anja; Hoja, Sabine; Socher, Eileen; Nolte, Elke; Wach, Sven; Wieland, Wolf; Hofstädter, Ferdinand; Goebell, Peter; Wullich, Bernd; Hartmann, Arndt; Stoehr, Robert (International Journal of Clinical and Experimental Pathology, 2013)
In this study, we determined the genotype distribution of two single nucleotide polymorphisms (SNPs) in secreted frizzled related protein 1 (SFRP1), rs3242 and rs921142, in a Caucasian bladder cancer case-control study. Allelic variants of the SNPs were determined using restriction fragment length polymorphism (RFLP) analysis and partly verified by sequencing analysis. Overall, DNA from 188 consecutive and 215 early-onset bladder cancer patients (≤45 years) as well as from 332 controls was investigated. Potential microRNA binding sites were determined for rs3242, and microRNA expression was analysed in cell lines and tumour specimens. We observed a remarkable distribution difference in rs3242 between bladder cancer patients and healthy controls (p=0.05). Additionally, we found a significant difference in genotype distribution (p=0.032), resulting from the difference of early-onset patients and the control group (p=0.007). The risk allele T showed increased frequency in the early-onset patient group (p=0.002). Genotype-dependent differences of microRNA binding capacity were predicted in SFRP1 mRNA for two microRNAs. Hsa-miR-3646 showed strong expression in cell lines and tumour tissue, whereas hsa-miR-603 exhibited weak expression. The rs921142 SNP showed no significant association with bladder cancer risk. This is the first study to describe an association of the SFRP1 SNP rs3242 and bladder cancer risk as well as the influence of rs3242 on genotype-dependent microRNA capacity on SFRP1 mRNA. The onset of bladder seems to be associated with the increased occurrence of the T-allele in rs3242.
Keywords: Bladder cancer; Microrna; Sfrp1; Snp; Wnt signalling pathway

Salvage external beam radiation therapy of biochemical relapse after radical prostatectomy: Results and potential role of PET/CT - Rutzner, Sandra; Lubgan, Dorota; Wullich, Bernd; Kuehn, R.; Kuwert, Torsten; Fietkau, Rainer (2018)
EVALuna2:35905

Serum levels of miR-320 family members are associated with clinical parameters and diagnosis in prostate cancer patients - Lieb, Verena; Weigelt, Katrin; Scheinost, Lena; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Klocker, Helmut; Holzhausen, Hans Juergen; Lai, Xin; Vera, Julio; Ekici, Arif Bülent; et al. (Oncotarget, 2018)
We studied the association of the serum levels of the microRNA family members miR-320a/-b/-c with clinico-pathological data to assess their applicability as diagnostic biomarker in prostate cancer (PCa) patients. The levels of miR-320a/-b/-c in 3 groups were evaluated by qRT-PCR (145 patients with PCa, 31 patients with benign prostatic hyperplasia (BPH) and 19 healthy controls). The levels of the three family members of miR-320 were directly correlated within each group (P < 0.001), but they differed significantly among the three groups (P < 0.001). The serum levels of the miR-320 family members were significantly increased in older patients compared to younger patients (≤ 66 years vs. > 66 years, P ≤ 0.001). In addition, the levels of all three miR-320 family members were significantly different in patients with low tumor stage compared with those with high tumor stage (miR-320a: P = 0.034; miR-320b: P = 0.006; miR-320c: P = 0.007) and in patients with low serum PSA compared with those with high serum PSA (≤ 4 ng vs. > 4 ng; miR-320a: P = 0.003; miR-320b: P = 0.003; miR-320c: P = 0.006). The levels of these miRNAs were inversely correlated with serum PSA levels. Detection in the serum samples of PCa patients with or without PSA relapse revealed higher levels of miR-320a/-b/-c in the group without PSA relapse before/after radical prostatectomy than in that with PCa relapse. In summary, the differences among the PCa/BPH/healthy control groups with respect to miR-320a/-b/-c levels in conjunction with higher levels in patients without a PSA relapse than in those with a relapse suggest the diagnostic potential of these miRNA-320 family members in PCa patients.
EVALuna2:35121

Serum miRNAs Support the Indication for MRI-Ultrasound Fusion-Guided Biopsy of the Prostate in Patients with Low-PI-RADS Lesions - Keck, Bastian; Borkowetz, Angelika; Pöllmann, Julia; Jansen, Thilo; Fischer, Moritz; Fuessel, Susanne; Kahlmeyer, Andreas; Wirth, Manfred; Huber, Johannes; Cavallaro, Alexander Josef; Hammon, Matthias; Platzek, Ivan; et al. (Cells, 2021)
Multiparametric MRI (mpMRI) and targeted biopsy of the prostate enhance the tumor detection rate. However, the prediction of clinically significant prostate cancer (PCa) is still limited. Our study tested the additional value of serum levels of selected miRNAs in combination with clinical and mpMRI information for PCa prediction and classification. A total of 289 patients underwent targeted mpMRI-ultrasound fusion-guided prostate biopsy complemented by systematic biopsy. Serum miRNA levels of miRNAs (miR-141, miR-375, miR-21-5p, miR-320b, miR-210-3p, let-7c, and miR-486) were determined by quantitative PCR. Detection of any PCa and of significant PCa were the outcome variables. The patient age, pre-biopsy PSA level, previous biopsy procedure, PI-RADS score, and serum miRNA levels were covariates for regularized binary logistic regression models. The addition of miRNA expression of miR-486 and let-7c to the baseline model, containing only clinical parameters, increased the predictive accuracy. Particularly in patients with PI-RADS ≤3, we determined a sensitivity for detecting significant PCa (Gleason score ≥ 7a corresponding to Grade group ≥2) of 95.2%, and an NPV for absence of significant PCa of 97.1%. This accuracy could be useful to support patient counseling in selected cases.
CRIS-Team Scopus Importer:2021-06-18
Keywords: diagnosis; microRNA; miRNA; mpMRI; PI-RADS; prostate biopsy; prostate cancer

SPECT/CT With the PSMA Ligand 99mTc-MIP-1404 for Whole-Body Primary Staging of Patients With Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp (Clinical Nuclear Medicine, 2018)
BACKGROUND: Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) is a novel ligand binding to prostate-specific membrane antigen suitable for SPECT. There are, as yet, no data concerning its use in whole-body primary staging and its interobserver variability in patients with prostate cancer (PC) prior to therapy. METHODS: A search of our clinical database from April 2013 to May 2017 yielded 93 patients with histologically confirmed cancer in whom Tc-MIP-1404 SPECT/CT had been performed for primary whole-body staging before therapy. Whole-body planar and SPECT/CT images of the lower abdomen and thorax had been obtained 3 to 4 hours postinjection of 706 ± 72 MBq Tc-MIP-1404. Images were visually analyzed for extent and location of abnormal uptake by 2 experienced nuclear physicians. Interobserver agreement for detection of primary tumor and metastatic lesions was assessed. In addition, SUVs of prostate-specific membrane antigen-positive regions of the prostate were determined in all patients, and from these, a variable reflecting total tumor load in the prostate gland was calculated (TUprostate). Follow-up reports of subsequent therapeutic interventions were available in 52 (56%) of all patients with a median follow-up of 18 months. RESULTS: In 90 (97%) of 93 patients, prostate uptake above background was detected as correlate of the histologically diagnosed PC. Forty-eight lymph node and 29 bone metastases were detected in 16 and 9 patients, respectively. In addition, 3 patients had disseminated bone metastases. No distant organ metastases were found. Interobserver agreement was high for the overall scan result (97%), as well as for the detection of the primary tumor (97%), of lymph node metastases (97%), and of bone metastases (99%). Recurrence of PC occurred in 5 patients in whom follow-up was available (10%). TUprostate was significantly higher in patients with Gleason scores of 8 or greater compared with patients with Gleason scores of 7 or less and at prostate-specific antigen (PSA) serum levels of 10 ng/mL or greater compared with PSA serum levels of 10 ng/mL or less. TUprostate of greater than 26 in the primary tumor predicted the occurrence of lymph node or bone metastases with a sensitivity of 82% and specificity of 76%. CONCLUSIONS: MIP-1404 SPECT/CT has a high accuracy and low interobserver variability in the diagnosis of PC and allows detection of lymph node and bone metastases in a significant proportion of as yet untreated PC patients. TUprostate is correlated with Gleason score and PSA serum concentration and allows prediction of the occurrence of lymph node and bone metastases with moderate accuracy at primary staging.
EVALuna2:32786

Taguchi versus Lich-Gregoir Extravesical Ureteroneocystostomy in Kidney Transplantation: A Systematic Review - Wehner, Hannah; Wullich, Bernd; Kunath, Frank; Apel, Hendrik (Urologia Internationalis, 2021)
Introduction: Ureteric implantation of the transplanted ureter into native urinary bladder tissue in kidney transplantation recipients is essential for post-operative kidney function. We aimed to determine the effects of Taguchi versus Lich-Gregoir extravesical ureteroneocystostomy in kidney transplantation. Methods: We searched multiple databases (MEDLINE, Cochrane Library, and Web of Science), trial registries, and conference proceedings until March 2021. We included prospective studies comparing Taguchi and Lich-Gregoir ureteroneocystostomy in kidney transplantation. Two review authors independently screened the identified records, extracted data, evaluated the risk of bias using ROBINS-I, and assessed the certainty of evidence according to GRADE. Results: We identified 3 prospective studies with serious or critical risk of bias, leading to low-certainty evidence. We downgraded the risk of bias due to study limitations. Assessment and/or reporting of baseline imbalances, co-interventions, and confounding factors was insufficient in all included studies. The effect of Taguchi ureteroneocystostomy remains unclear. Conclusion: Currently available evidence is not useful to determine the effect of Taguchi versus Lich-Gregoir ureteroneocystostomy in kidney transplantation. There is a need for methodologically better designed and executed studies, such as randomized controlled trials with long-term follow-up reporting baseline imbalances, co-interventions, and confounding factors.
CRIS-Team WoS Importer:2021-10-15

TERT promoter mutation analysis as a surrogate to morphology and immunohistochemistry in problematic spindle cell lesions of the urinary bladder - Bertz, Simone; Stöhr, Robert; Gaisa, Nadine T.; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Histopathology, 2020)
Aims: Pseudosarcomatous myofibroblastic proliferations (PSMPs) of the urinary bladder are diagnostically challenging. Diagnostic difficulties are mainly due to frequent cytokeratin expression, variable ALK expression and worrisome morphological features suggestive of malignancy. Conversely, sarcomatoid urothelial carcinoma (UC) may show bland inflammatory myofibroblastic tumour (IMT)-like morphology. TERT promoter mutations are characteristic events in urothelial cancers, but have not been studied in PSMPs. Methods and results: We compared histomorphological and immunohistochemical features and TERT promoter status in 16 PSMPs and 18 sarcomatoid UC. In a subset of PSMPs, RNA sequencing was performed. At least focal IMT-like morphology was seen in nine of 17 sarcomatoid UC. Atypical mitoses, differentiated urothelial component and heterologous elements were the most reliable distinguishing histomorphological features of sarcomatoid UC, if present. A panel of immunohistochemistry (IHC) including ALK (clone D5F3), p53 pattern, p63 and GATA3 reliably distinguished PSMP from sarcomatoid UC. GATA3 (P = 0.001) and p53 patterns (mutant versus wild-type; P < 0.001) were differentially expressed between PSMPs and sarcomatoid UC. Diffuse pancytokeratin staining was significantly associated with PSMPs (10 of 13) compared to four of 14 sarcomatoid UCs (P = 0.012). TERT promoter mutations were found in 17 of 18 sarcomatoid UC versus none of 16 PSMPs (P < 0.001). RNA sequencing revealed ALK genetic rearrangements in one of two ALK-positive and one of 10 ALK-negative PSMPs, which revealed a novel FN1/RET gene fusion. Conclusion: Careful histomorphological analysis and differential IHC reliably distinguish the majority of PSMPs and sarcomatoid UC. In equivocal cases, TERT promoter mutation analysis and/or detection of ALK expression/rearrangements are valuable additional diagnostic adjuncts, strongly supporting sarcomatoid UC and PSMP, respectively.
CRIS-Team Scopus Importer:2020-10-02
Keywords: ALK gene rearrangement; inflammatory myofibroblastic tumour; pseudosarcomatous myofibroblastic proliferation; sarcomatoid urothelial carcinoma; TERT promoter mutation

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

Testosterone Replacement Therapy in Hypogonadal Men Following Prostate Cancer Treatment: A Questionnaire-Based Retrospective Study among Urologists in Bavaria, Germany - Kühn, Charlotte; Strasser, Hans; Romming, Alexander; Wullich, Bernd; Goebell, Peter (Urologia Internationalis, 2015)
Several reports suggest testosterone replacement therapy (TRT) may be an option in selected hypogonadal patients with a history of prostate cancer (PCa) and no evidence of disease after curative treatment. Our aim was to assess TRT experience and patient management among urologists in Bavaria.Questionnaires were developed and mailed to all registered urologists in Bavaria (n = 420) regarding their experience with TRT in patients with treated PCa.One hundred and ninety-three (46%) urologists returned the questionnaire and reported their experience with TRT in hypogonadal patients after curative treatment for PCa. Complete data was available for 32 men. Twenty-six patients (81%) received TRT after prostatectomy, 1 patient after external beam radiation, 3 patients after high-dose brachytherapy and 2 patients after high-intensity focused ultrasound. Of the PCa cases, 88.5% (23/26) were organ confined (pT2a-c), and 3 were pT3 tumors. All patients were pN0/cN0, and only 1 patient (pT3a) had a positive surgical margin status postoperatively. After a mean follow-up of 39.8 months, no biochemical relapse was observed.To date, there is no clear evidence to withhold TRT from hypogonadal men after curative PCa treatment. Our findings, although with limitations, fit in with the available data showing that TRT does not put patients at an increased risk after curative treatment of PCa.
EVALuna2:16276

The 14th annual DPKK meeting on "Importance of molecular analysis for diagnosis and therapy" - Taubert, Helge; Becker, C.; Fuessel, S.; Seitz, G.; Thelen, P.; Wullich, Bernd (Urologe, 2017)
EVALuna2:35925

The 16th DPKK Annual Conference "Urology meets Pathology" - Taubert, Helge; Becker, C.; Fuessel, S.; Seitz, G.; Kristiansen, G.; Wach, S.; Wullich, Bernd (Urologe, 2019)
CRIS-Team WoS Importer:2019-07-02

The combined serum levels of miR-375 and urokinase plasminogen activator receptor are suggested as diagnostic and prognostic biomarkers in prostate cancer - Wach, Sven; Al-Janabi, Omar; Weigelt, Katrin; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Nolte, Elke; Holzhausen, Hans-Juergen; Stoehr, Robert; Huppert, Verena; Hartmann, Arndt; et al. (International Journal of Cancer, 2015)
This study aimed to assess the applicability of miR-375 in combination with the soluble urokinase plasminogen activator receptor (suPAR) protein as a diagnostic and/or prognostic biomarker for prostate cancer (PCa) patients. miR-375 levels by qRT-PCR and suPAR levels by ELISA were evaluated in serum samples from 146 PCa patients, 35 benign prostate hyperplasia (BPH) patients and 18 healthy controls. Antigen levels of suPAR differed between healthy controls and PCa or BPH patients, whereas miR-375 levels differed between PCa and BPH patients or healthy controls (p < 0.001). Additionally, suPAR levels differed between the Gleason sum groups GS = 7 versus GS > 7, with higher levels in the latter group (p = 0.011), and miR-375 levels were higher in the tumor stage group T3-T4 compared with the T1-T2 group (p = 0.039). A high concentration of suPAR was associated with a poor disease-specific survival (DSS; p = 0.039). The combination of suPAR and miR-375 levels identified a patient group possessing high levels for both parameters. This was associated with a poorer 10-year overall survival (OS) and DSS, with a 6.38-fold increased risk of death and a 7.68-fold increased risk of tumor-related death (p = 0.00026 and p = 0.014; univariate Cox's regression analysis). In a multivariate Cox's regression analysis PCa patients with high levels of suPAR and miR-375 showed a 5.72-fold increased risk of death in OS (p = 0.006). In summary, the differences between the PCa/BPH/healthy control cohorts for either suPAR and miR-375 levels in conjunction with the association of combined high suPAR/miR-375 levels with a poor prognosis suggest a diagnostic and prognostic impact for PCa patients.
EVALuna2:6726

The natural course of pT2 prostate cancer with positive surgical margin: predicting biochemical recurrence - Karl, A.; Buchner, A.; Tympner, C.; Kirchner, T.; Ganswindt, U.; Belka, C.; Ganzer, R.; Burger, M.; Eder, F.; Hofstädter, F.; Schilling, D.; Sievert, K.; et al. (World Journal of Urology, 2015)
To predict biochemical recurrence respecting the natural course of pT2 prostate cancer with positive surgical margin (R1) and no adjuvant/neoadjuvant therapy.A multicenter data analysis of 956 patients with pT2R1N0/Nx tumors was performed. Patients underwent radical prostatectomy between 1994 and 2009. No patients received neoadjuvant or adjuvant therapy. All prostate specimens were re-evaluated according to a well-defined protocol. The association of pathological and clinical features, in regard to BCR, was calculated using various statistical tests.With a mean follow-up of 48 months, BCR was found in 25.4 %. In univariate analysis, multiple parameters such as tumor volume, PSA, Gleason at positive margin were significantly associated with BCR. However, in multivariate analysis, Gleason score (GS) of the prostatectomy specimen was the only significant parameter for BCR. Median time to recurrence for GS <= 6 was not reached; 5-year BCR-free survival was 82 %; and they were 127 months and 72 % for GS 3+4, 56 months and 54 % for GS 4 + 3, and 27 months and 32 % for GS 8-10. The retrospective approach is a limitation of our study.Our study provides data on the BCR in pT2R1-PCa without adjuvant/neoadjuvant therapy and thus a rationale for an individual's risk stratification. The data support patients and physicians in estimating the individual risk and timing of BCR and thus serve to personalize the management in pT2R1-PCa.
EVALuna2:6640

The new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) efficiently suppresses cell growth in human leukemia and urologic tumor cell lines - Nolte, Elke; Sobel, Anna; Wach, Sven; Hertlein, Heidi; Ebert, Nadja; Müller-Uri, Frieder; Slany, Robert; Taubert, Helge; Wullich, Bernd; Kreis, Wolfgang (Anticancer Research, 2015)
Background/Aim: The use of cardenolides in the treatment of cardiac insufficiency is well-established. However, the potential of cardenolides in tumor therapy has not been comprehensively studied. The aim of the present study was to characterize the cytotoxic effects of the new semisynthetic cardenolide analog AMANTADIG (3β-[2-(1-amantadine)-1- on-ethylamine]-digitoxigenin), and the cardenolide digitoxin on leukemia and urological tumor cell lines. Materials and Methods: The anti-proliferative effects of AMANTADIG and digitoxin on leukemia and urological cancer cell lines were analyzed using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction viability assay. Results: AMANTADIG and digitoxin exhibited antiproliferative activities against the leukemia cell lines in the low nanomolar range. The prostate cancer and renal cell carcinoma cell lines were equally sensitive to AMANTADIG and digitoxin, however, the leukemia cell lines were more sensitive to both cardenolides. Conclusion: The new cardenolide analog AMANTADIG appears effective in cell growth inhibition of leukemia and urological tumor cell lines.
Keywords: 3β-[2-(1-Amantadine)-1-on-ethylamine]-digitoxigenin; AMANTADIG; Cardenolide analog; Human leukemia cells; Human urological cancer cells; Porcine cerebral cortex Na+/K+-ATPase

The prognostic impact of Claudin 6 in papillary renal cell carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Pathology Research and Practice, 2022)
Background: Claudins are promising biomarkers for diagnosis and prognosis or targets for treatment. They play a major role in signal transduction and are important in nearly all aspects of tumorigenesis. Claudin 6 is a member of the claudin family and is part of the tight junction molecule. It is reactivated in several cancer types and serves as prognostic marker in, for example, gastric, breast or non small cell lung cancer. The prognostic role of Claudin 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), is still unclear. Patients and Methods: The patients’ sample collection was a joint collaboration of the PANZAR consortium. Patients’ medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Claudin 6 was determined by immunohistochemistry. Results: In total, Claudin 6 staining was positive in 55 of 240 type 1 and 30 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed an overall survival of 84% for Claudin 6- compared to 78% for Claudin 6 + in pRCC type 1 tumors (p = 0.449, log-rank) and 68% for Claudin 6- compared to 65.4% for Claudin 6 + in pRCC type 2 tumors (p = 0.364, log-rank). Conclusion: In this study, claudin 6 expression showed no significant association regarding overall survival (OS) and therefore did not qualify as a prognostic marker in pRCC. Future studies will have to determine, whether Claudin 6 plays a prognostic role in other RCC entities. In addition, the function of Claudin 6 as a predictive marker for therapeutic approaches has to be evaluated in future studies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Claudin 6; Papillary renal cell carcinoma; Prognosis; Survival

The Prognostic Impact of PD-L2 in Papillary Renal-Cell Carcinoma. - Mondorf, Yvonne; Mikuteit, Marie; Ivanyi, Philipp; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; et al. (Urologia Internationalis, 2022)
INTRODUCTION: Programmed death-1 ligand (PD-L1) has been often studied in different types of renal-cell carcinoma (RCC). For example, in clear-cell renal carcinoma it is well established that programmed death-1 receptor and PD-L1 are important prognostic markers. In contrast, the role of programmed death-2 ligand (PD-L2) as prognostic marker remains unclear. The aim of this study was to evaluate if PD-L2 expression could play a role as a prognostic marker for papillary RCC (pRCC). METHODS: The patients' sample collection was a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of PD-L2 was determined by immunohistochemistry. In total, PD-L2 staining was evaluable in 185 of 240 type 1 and 99 of 128 type 2 pRCC cases. RESULTS: PD-L2 staining was positive in 67 (36.2%) of type 1 and in 31 (31.3%) of type 2 pRCC specimens. The prevalence of PD-L2+ cells was significantly higher in high-grade type 1 tumors (p = 0.019) and in type 2 patients with metastasis (p = 0.002). Kaplan-Meier analysis disclosed significant differences in 5-year overall survival (OS) for patients with PD-L2- compared to PD-L2+ in pRCC type 1 of 88.4% compared to 73.6% (p = 0.039) and type 2 of 78.8% compared to 39.1% % (p < 0.001). However, multivariate analysis did not identify the presence of PD-L2+ cells neither in type 1 nor type 2 pRCC as an independent predictor of poor OS. DISCUSSION/CONCLUSION: PD-L2 expression did not qualify as an independent prognostic marker in pRCC. Future studies will have to determine whether anti-PD-L2-targeted treatment may play a role in pRCC and expression can potentially serve as a predictive marker for these therapeutic approaches.
EVALuna2:505682

The Prognostic Value of FGFR3 Expression in Patients with T1 Non-Muscle Invasive Bladder Cancer - Sikic, Danijel; Taubert, Helge; Breyer, Johannes; Eckstein, Markus; Weyerer, Veronika; Keck, Bastian; Kubon, Jennifer; Otto, Wolfgang; Worst, Thomas S.; Kriegnnair, Maximilian C.; Erben, Philipp; Hartmann, Arndt; et al. (Cancer Management and Research, 2021)
Purpose: Fibroblast growth factor receptor 3 (FGFR3) alterations are frequent in non-muscle-invasive bladder cancer (NMIBC), although current data regarding the prognostic and therapeutic relevance are inconsistent. We analyzed the prognostic role of FGFR3 mRNA expression in stage T1 NMIBC. Patients and Methods: The mRNA expression of FGFR3 and cyclin-dependent kinase inhibitor 2A (CDKN2A) was measured by RT-qPCR in 80 patients with stage T1 NMIBC treated with transurethral resection of the bladder and correlated with clinical data and KRT5 and KRT20 expression, used as surrogate markers for basal and luminal subtypes, respectively. Results: FGFR3 and CDKN2A transcript levels were not correlated. FGFR3 expression was associated with the expression of KRT5 (p=0.002) and KRT20 (p < 0.001). CDKN2A expression was negatively correlated with KRT5 (p=0.030). In Kaplan-Meier analysis and univariable Cox regression analysis, high FGFR3 expression was associated with signifi-cantly reduced recurrence-free survival (RFS) (HR=3.78; p < 0.001) and improved overall survival (OS) (HR=0.50; p=0.043), while high CDKN2A expression was associated with reduced OS (HR=2.34; p=0.034). Patient age was the only clinicopathological parameter associated with reduced OS (HR=2.29; p=0.022). No parameter was an independent prog-nostic factor in multivariable analysis. Next, we stratified the patients depending on their lineage differentiation. In univariable analysis, the prognostic effect of FGFR3 and CDKN2A was observed primarily in patients demonstrating high expression of KRT5 or KRT20, whereas high FGFR3 expression was associated with significantly reduced RFS, irrespective of instillation therapy. Conclusion: Stage T1 NMIBC patients with high FGFR3 expression show shorter RFS but better OS than patients with low FGFR3 expression.
CRIS-Team WoS Importer:2021-09-03

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

The Role of PSMA PET Imaging in Prostate Cancer Theranostics: A Nationwide Survey - Borkowetz, Angelika; Linxweiler, Johannes; Fussek, Sebastian; Wullich, Bernd; Saar, Matthias (Urologia Internationalis, 2022)
Introduction: Prostate-specific membrane antigen (PSMA)-based imaging and theranostics have played an important role in the diagnosis, staging, and treatment of prostate cancer (PCa). We aimed to evaluate the acceptance and use of PSMA theranostics among German urologists. Methods: An anonymous online questionnaire was sent via survio.com to the members of the German Society of Urology (DGU). Results: Seventy-two percent of participants performed PSMA positron emission tomography (PET) imaging regularly in biochemically recurrent PCa. Overall, 61% of participants considered PSMA-radioligand therapy to be very useful or extremely useful. PSMA PET imaging in high-risk PCa is more often considered by urologists working in a university setting than in nonuniversity settings or medical practices (51% vs. 25%, p < 0.001). Most perform PSMA-radioligand therapy as an option after all approved systemic treatments for metastatic castration-resistant PCa (56%) or after cabazitaxel (14%). A total of 93.9% and 70.3% of respondents consider the lack of reimbursement by health insurance to be the main obstacle to using PSMA PET imaging or radioligand therapy, respectively. Discussion/Conclusion: PSMA-based imaging/theranostics are already widely applied but would find even more widespread use if reimbursement is clearly regulated by health insurance in Germany.
CRIS-Team WoS Importer:2022-10-28

The Treatment Reality of Octogenarians with Bladder Cancer in a Maximum Care Hospital - Sikic, D.; Wach, S.; Taubert, Helge; Richterstetter, M.; Kunath, F.; Lieb, V.; Krause, S.; Merten, Ricarda; Ott, O.; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (2016)
EVALuna2:18333

Timing of androgen deprivation monotherapy and combined treatments in castration-sensitive and castration-resistant prostate cancer: a narrative review - Kunath, F.; Goebell, Peter; Wullich, Bernd; Sikic, D.; Kahlmeyer, A. (World Journal of Urology, 2019)
Purpose: Standard androgen deprivation therapy (ADT) can be initiated early at the time of diagnosis in asymptomatic castration-sensitive advanced prostate cancer. This definition has recently been expanded to also include an early combined treatment with standard ADT and new antihormonal drugs. We aimed to present the best available evidence for the timing of initiation of ADT monotherapy and combined treatments in castration-sensitive/-resistant prostate cancer. Methods: For this narrative review, we searched Cochrane reviews in the Cochrane Library, systematic reviews and randomized controlled trials in MEDLINE, phase III and ongoing trials in ClinicalTrials.gov and screened the reference lists to extract articles of interest. One author screened the references which were finally included after assessing their relevance through discussion with other experts in the field. Results: The identified references were grouped by medication (standard ADT, androgen biosynthesis inhibitor, androgen receptor antagonists or combined therapies) and tumor stage (castration sensitive or resistant). The evidence was narratively summarized and discussed in the context of the current therapeutic landscape. Conclusions: Early standard ADT can reduce symptoms of disease progression and may extend progression-free and overall survival. The patient should be well informed about the higher rates of treatment-related side effects. Deferring standard ADT might be indicated only for well-informed or unfit patients. Early standard ADT is increasingly combined with new antihormonal drugs in castration-sensitive metastatic prostate cancer to gain additional survival and quality of life benefits. Combined treatment at the time of development of castration-resistant disease is well established.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Androgen antagonists; Androgen receptor antagonists; Castration resistant; Nonsteroidal antiandrogens; Prostatic neoplasms

Transplant Ureteral Stenosis after Renal Transplantation: Risk Factor Analysis - Apel, Hendrik; Rother, Ulrich; Wach, Sven; Schiffer, Mario; Kunath, Frank; Wullich, Bernd; Heller, Katharina M. (Urologia Internationalis, 2021)
Introduction: The results of kidney transplants have improved dramatically in recent years, leading to reduced morbidity and mortality. Despite continuous improvements, urological complications occur at a rate of 2.6%-15%. Ureteral stenosis of graft ureters is the most common complication, with a probability of 0.5%-6.3%. This study aimed to determine the incidence of ureteral stenosis after kidney transplantation and identify risk factors that distinguish transplant patients with and without ureteral stenosis. Methods: This study retrospectively analyzed patients who had undergone kidney transplantation at the Department of Urology of the Friedrich-Alexander University Erlangen-Nuremberg between 2001 and 2015. Forty-seven patients developed ureteral stenosis during the operation. Most of the ureteral stenosis cases occurred in the first 4 months after transplantation. Kaplan-Meier analysis and the log-rank test were used to calculate the cumulative risk, and the Mann-Whitney U test was used nonparametrically. The significance level was set at p < 0.05. Results: Statistical analysis showed that residual diuresis (p = 0.008), cold ischemia time (CIT) (p = 0.040), the body mass index (p = 0.027), and donor serum creatinine value (p = 0.039) showed a significantly different distribution between recipients with or without ureteral stenosis after kidney transplantation. In multivariate Cox's regression modeling, residual diuresis and the donor serum creatinine level were identified as the only independent predictors of patients' stenosis-free survival. Conclusion: Urological complications not diagnosed and treated in time endanger the success of kidney transplantation. After evaluating the kidney transplantation data of the patients at the Transplant Center Erlangen-Nuremberg from 2001 to 2015, residual diuresis, CIT, the body mass index, and donor serum creatinine value were found to influence the development of ureteral stenosis.
CRIS-Team WoS Importer:2021-12-03

Transurethral en bloc submucosal hydrodissection vs conventional resection for resection of non-muscle-invasive bladder cancer (HYBRIDBLUE): a randomised, multicentre trial - Gakis, Georgios; Karl, Alexander; Bertz, Simone; Burger, Maximillian; Fritsche, Hans Martin; Hartmann, Arndt; Jokisch, Friedrich; Kempkensteffen, Carsten; Miller, Kurt; Mundhenk, Jens; Schneevoigt, Birte Swantje; Schubert, Tina; et al. (Bju International, 2020)
Objective: To determine whether transurethral en bloc submucosal hydrodissection of bladder tumours (TUEB) improves the quality of the resection compared to conventional transurethral resection of bladder tumour (TURBT) in patients with non-muscle-invasive bladder cancer (NMIBC). Patients and Methods: A randomised, multicentre trial (HYBRIDBLUE) was conducted with a superiority design. Six German academic centres participated between September 2012 and August 2015. Based on literature analysis, a sample size for accurate histopathological assessment concerning muscle invasion was assumed to be feasible in 50% (P0 = 0.5) of TURBT and 80% of TUEB cases. After pre-screening of a total of 305 patients, participants were allocated to two study arms: Group I: hexaminolevulinate (HAL)-guided TUEB; Group II: conventional HAL-guided TURBT. The primary endpoint was the proportion of specimens that could be reliably evaluated pathologically concerning muscle invasiveness. Secondary endpoints included rates of histopathological completeness of the resection, muscularis propria content, recurrence, and complication rates. Results: A total of 115 patients (TUEB 56; TURBT 59) were eligible for final analysis. Adequate histopathological assessment, which included muscularis propria content and tumour margins (R0 vs R1), was present in 48/56 (86%) TUEB patients compared to 37/59 (63%; P = 0.006) in the TURBT group. R0 was confirmed in 30/56 TUEB patients (57%) and five of 59 TURBT patients (9%; P < 0.001). No complications of Grade ≥III were observed in both arms. At 3 and 12 months, three and 19 patients recurred in the TUEB group vs seven and 11 patients in the TURBT group, respectively (P = 0.33 and P = 0.08). Conclusions: In this randomised study, TUEB was shown to be clinically safe regarding perioperative endpoints. An adequate histopathological assessment concerning muscle invasion was significantly better assessable in the TUEB arm compared to standard TURBT. This finding indicates the clinical potential for reducing the rate of early re-resections. Yet, a larger study with recurrence-free survival as the primary endpoint is needed to assess the oncological efficacy between both techniques.
CRIS-Team Scopus Importer:2020-08-14
Keywords: #BladderCancer; #blcsm; bladder cancer; en bloc; hexaminolevulinate; hydrodissection; photodynamic diagnosis; transurethral; trial

Treatment of benign prostatic hyperplasia in geriatric patients-use and limitations of existing guidelines - Schoeb, D. S.; Wullich, Bernd; Duerschmied, D.; Heimbach, B.; Heupel-Reuter, M.; Gross, A. J.; Wilhelm, K.; Gratzke, C.; Miernik, A. (Urologe, 2019)
The demographic developments of western society and the resulting increase in the number of very old patients in urology represents a challenge for the design of clinical studies and, consequently, recommendations of guidelines. While in internal medicine there is already a subspecialization with a focus on the treatment of elderly and multimorbid patients, in urology there is hardly any subspecialization into the problems of geriatric patients. Thus, using a case study as an example, the treatment decisions for benign prostatic hyperplasia (BPH) in geriatric patients are discussed. In addition the available evidence from the literature and guidelines are presented in order to assiste in daily management of geriatric patients with lower urinary tract symptoms and to critically discuss potential fields of application and limitations of the existing guidelines. In this context, we also examine the challenges when choosing a drug therapy and in deciding which of the many surgical options should be used.
CRIS-Team WoS Importer:2019-09-13

Tumor grade-titude: XGBoost radiomics paves the way for RCC classification - Ellmann, Stephan; von Rohr, Felicitas; Komina, Selim; Bayerl, Nadine; Amann, Kerstin Ute; Polifka, Iris; Hartmann, Arndt; Sikic, Danijel; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (European Journal of Radiology, 2025)
This study aimed to develop and evaluate a non-invasive XGBoost-based machine learning model using radiomic features extracted from pre-treatment CT images to differentiate grade 4 renal cell carcinoma (RCC) from lower-grade tumours. A total of 102 RCC patients who underwent contrast-enhanced CT scans were included in the analysis. Radiomic features were extracted, and a two-step feature selection methodology was applied to identify the most relevant features for classification. The XGBoost model demonstrated high performance in both training (AUC = 0.87) and testing (AUC = 0.92) sets, with no significant difference between the two (p = 0.521). The model also exhibited high sensitivity, specificity, positive predictive value, and negative predictive value. The selected radiomic features captured both the distribution of intensity values and spatial relationships, which may provide valuable insights for personalized treatment decision-making. Our findings suggest that the XGBoost model has the potential to be integrated into clinical workflows to facilitate personalized adjuvant immunotherapy decision-making, ultimately improving patient outcomes. Further research is needed to validate the model in larger, multicentre cohorts and explore the potential of combining radiomic features with other clinical and molecular data.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Computed tomography (CT); Diagnostic performance; Feature extraction; Machine learning; Personalized immunotherapy; Radiomics; Renal cell carcinoma (RCC); Treatment decision-making; Tumor grading

Tumour immune microenvironment drives prognostic relevance correlating with bladder cancer subtypes - Eckstein, Markus; Strissel, Pamela; Pfannstiel, C.; Chiappinelli, K.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Keck, Bastian; Wirtz, R.; Breyer, J.; Burger, M.; et al. (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Urethral Plate Characteristics in Cases of Non-proximal Hypospadias May Not Be Associated With a Higher Risk of Complications When a Two-Stage Repair Is Applied - Marcou, Marios; Bobbe, Sarah-Magdalena; Wullich, Bernd; Hirsch-Koch, Karin (Frontiers in Pediatrics, 2022)
Purpose: To investigate whether a two-stage repair of distal- and mid-shaft hypospadias (non-proximal hypospadias) could eliminate the risk factors resulting from adverse urethral plate characteristics and eventually reduce complication rates. Methods: We retrospectively reviewed all cases of primary surgical repair of non-proximal hypospadias performed in our center between 2009 and 2018. In all cases where adverse urethral plate characteristics were found, such as meatal stenosis, a shallow urethral groove, a thick web of tissue between the native meatus and the urethral groove or in the presence of a very “thin,” skin-like distal urethra, a two-stage repair was routinely undertaken. In cases of native meatal stenosis, a meatotomy, and meatoplasty were performed. In cases of a very “thin” distal urethra we incised the skin proximally up to the point of a normal urethral fold and a meatoplasty was performed at that point. Hypospadias repair was then performed in a second operation, 3–6 months following the first procedure. Urethroplasty, both in cases of a single-stage repair and in cases of a two-stage repair, was always performed using the Thiersch-Duplay technique. Patients with a follow-up of less than 12 months were excluded from this study. Results: Over a period of 10 years, 208 boys underwent primary surgical repair of non-proximal hypospadias. Eighty-nine of the 208 patients (42.8%) underwent single-stage hypospadias repair. Two-stage repair of the hypospadias was required in 119 (57.2%) of the patients. The overall complication rate was 3.4% in the group operated in a single stage and 7.6% in the group that required a two-stage repair (p = 0.09). The most frequent complication reported was urethrocutaneous fistula (p = 0.31), followed by meatal stenosis (p = 0.37), urethral stricture (p = 0.08) and wound dehiscence (p = 0.16). There was no significant difference between the complication rates of the two groups. Conclusion: Patients with distal hypospadias and poor urethral plate characteristics repaired in a two-stage approach have comparable low-complications to those with favorable urethral plate characteristics repaired in a single-stage.
CRIS-Team Scopus Importer:2022-08-05
Keywords: children; distal hypospadias; hypospadias repair; mid-shaft hypospadias; non-proximal hypospadias; Thiersch-Duplay; two-stage repair; urethral plate

"UroEvidence" - Centre for knowledge translation of the DGU (German Society of Urology) : Summarizing, analysing and making current knowledge available - Kranz, J.; Kunath, F.; Borgmann, H.; Dräger, D. L.; Krabbe, L. M.; Kröger, N.; Otto, W.; Spek, A.; Zengerling, F.; Wullich, Bernd; Miernik, A. (Urologe, 2014)
EVALuna2:6557

UroEvidence opens new Call for Applications - Schmidt, S.; Kunath, F.; Wullich, Bernd (Urologe, 2018)
EVALuna2:35877

Urological Challenges in Refugees and Migrants - Wullich, Bernd; Alloussi, S. (Urologe, 2018)
EVALuna2:35881

Urology and the environment - Wullich, Bernd; Golka, K. (Die Urologie, 2022)
CRIS-Team WoS Importer:2022-12-16

Urology vision 2025 Urologie Vision 2025 - Klotz, T.; Zumbe, Juergen; Wullich, Bernd (Urologe, 2019)
CRIS-Team Scopus Importer:2019-07-30

Urotechnology: a new interdisciplinary platform for promoting and managing of technical innovations in urology - Miernik, A.; Becker, C.; Wullich, Bernd; Schoenthaler, M.; Arnolds, B. J.; Wetterauer, U. (Urologe, 2015)
The innovative power in medical engineering and technology development requires a close cooperation between universities and non-university research institutions and a collaboration with industrial partners. German knowledge in the fields of video and micro-optics, microsystem technology and of informational technology and software applications seem to be highly competitive at international level. Germany's previous leadership in the development of technical equipment will be challenged by today's requirements and difficulties in medical engineering. Research and expenses demands for the development of novel medical instruments, products and applications will increase continuously. Transparency and coordinated collaboration between universities and industrial partners will contribute to a substantial improvement in surgical therapy. Medical technology of the future, including urotechnology, requires professional structures and coordination and will have to be based on evidence.
EVALuna2:16333

Utility of stromal tumor infiltrating lymphocyte scoring (sTILs) for risk stratification of patients with muscle-invasive urothelial bladder cancer after radical cystectomy - Sikic, Danijel; Weyerer, Veronika; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Schmitz-Draeger, Bernd J.; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Urologic Oncology-Seminars and Original Investigations, 2021)
Background: Multi-omics analyses of muscle-invasive bladder cancer (MIBC) demonstrated that specific patterns of tumor infiltrating lymphocytes (TILs) associates with improved outcomes in patients treated with radical cystectomy. However, methodologies for simple and robust quantification of TILs, especially for daily practice purposes, are lacking. Thus, we investigated the feasibility of stromal TIL scoring on hematoxylin/eosin stained (HE) slides in MIBC. Materials and methods: sTILs were scored on HE whole slides of 241 MIBC patients treated with radical cystectomy and adjuvant chemotherapy. Median infiltration of 10% was used as objective cut-off. Additionally, immunohistochemistry was performed on spatially organized tissue microarrays to quantify key immune cell populations objectively for correlational analyses with sTIL scoring results (CD3+/Pan-T-cells, CD8+/cytotoxic T-Cells, CD56+/NK-cells, CD68+/macrophages). sTILs amounts were correlated with clinicopathological features, recurrence-free (RFS), disease-specific (DSS), and overall survival (OS). Results: sTIL amounts correlated moderately to strongly with quantitatively estimated amounts of pan-T-cells (r = 0.73, P <0.0001), cytotoxic T-cells (r = 0.73, P <0.0001), NK-cells (r = 0.68, P <0.0001), macrophages (r = 0.55, P <0.0001) and with pan-cytotoxic immune infiltration (r = 0.78, P <0.0001), thus reflecting overall infiltration with key immune cell populations. sTIL infiltration ≥10% was associated with significantly higher 5-year OS (45.5% vs. 19.8%), DSS (56.6% vs. 25.6%) and RFS (56.2% vs. 18.9%; P <0.0001 for all three comparisons) rates, and lower pT-stage (P = 0.015), lower pN-stage (P = 0.028), lower rates of lymphovascular invasion (P = 0.0003) and blood vessel invasion (P = 0.01) when compared to sTIL infiltration of <10%. Multivariable regressions models confirmed sTILs as strongest independent predictor for improved outcomes following radical cystectomy. Conclusions: HE based sTIL scoring is a reliable tool to assess MIBC inflammation status and to stratify the survival of MIBC patients undergoing radical cystectomy. sTIL amount is an independent predictor for improved survival, and might be an useful, routinely applicable tool to identify patients benefiting from perioperative platinum-based chemotherapy and checkpoint inhibitor therapy. However, external validation of our data is required.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bladder cancer; Cystectomy; Prognosis; sTILs; TILs; Urothelial cancer

Variant morphology and random chromosomal integration of BK polyomavirus in posttransplant urothelial carcinomas - Bertz, Simone; Enßer, Armin; Stöhr, Robert; Eckstein, Markus; Apel, Hendrik; Mayr, Doris; Büttner-Herold, Maike; Gaisa, Nadine Therese; Comperat, Eva; Wullich, Bernd; Hartmann, Arndt; Knöll, Antje (Modern Pathology, 2020)
BK polyomavirus (BKPyV) causes major complications in solid organ transplant recipients but little is known about its role in the development of urothelial carcinoma (UC) during immunosuppression. Immunohistochemistry (IHC) screening for polyomavirus large T antigen (LTag) was performed in 94 micropapillary UC (MPUC), 480 unselected UC, 199 muscle invasive UC (including 83 UC with variant differentiation), 76 cases of plasmocytoid, nested and large nested UC and 15 posttransplant UC. LTag expressing UC were reevaluated regarding their histomorphological features and characterized by IHC for p53 and HER2, chromogenic in situ hybridization for HER2 and SNaPshot analysis of the TERT promoter and HRAS. Real-time PCR and next generation sequencing (NGS) were performed to search for BKPyV-DNA and for variants in the tumor and viral genomes. We detected five LTag expressing UC which were diagnosed between 2 and 18 years after kidney (n = 4) or heart (n = 1) transplantation. 89 MPUC without history of organ transplantation and overall 755 UC (including cases with variant histology) were LTag negative. Of the five LTag expressing UC, three were MPUC, one showed extensive divergent differentiation with Mullerian type clear cell carcinoma, and one displayed focal villoglandular differentiation. All five tumors had aberrant nuclear p53 expression, 2/5 were HER2-amplified, and 3/5 had TERT promoter mutations. Within the 50 most common cancer related genes altered in UC we detected very few alterations and no TP53 mutations. BKPyV-DNA was present in 5/5 UC, chromosomal integration of the BKPyV genome was detectable in 4/5 UC. Two UC with BKPyV integration showed small deletions in the BKPyV noncoding control region (NCCR). The only UC without detectable BKPyV integration had a high viral load of human herpesvirus 6 (HHV-6). Our results suggest that LTag expression of integrated BKPyV genomes and resulting p53 inactivation lead to aggressive high-grade UC with unusual, often micropapillary morphology.
CRIS-Team WoS Importer:2020-02-28

Vertebral metastases of urogenital carcinomas : Diagnosis and conservative therapy - Keck, Bastian; Hammon, Matthias; Uder, Michael; Huber, J.; Goebell, Peter; Kunath, F.; Wullich, Bernd; Richter, R. H. (Urologe, 2016)
The high incidence of bone metastases of urologic neoplasms and their morbidity, especially of vertebral metastases, requires exact diagnosis and consequent therapy. Conventional radiography plays an important role in the diagnosis of symptomatic bone lesions. Computed tomography can evaluate the stability of metastatic lesions and is indispensable for therapy planning. MRI and PET-CT have the highest diagnostic accuracy for the detection of bone metastases and MRI can evaluate their intra- and extraosseus components. PET-CT, PET-MRI, or SPECT-CT in combination with specific tracers - due to their high specificity and sensitivity - have the potential to replace conventional methods in the future. Conservative treatment basically consists of analgesic therapy, the administration of calcium and vitamin D3 and bisphosphonates or inhibitors of RANKL (denosumab). Moreover radium-223-dichloride can improve overall survival and the time to the first symptomatic skeletal event in castration-resistant prostate cancer patients with bone metastases.
EVALuna2:14491

Whole-Body Electromyostimulation combined with personalized Nutritional Support improves the Body Composition of Patients with advanced Cancer - Schink, Kristin; Herrmann, Hans Joachim; Schwappacher, Raphaela; Orlemann, Till; Meyer, Julia; Waldmann, Elisabeth; Wullich, Bernd; Kahlmeyer, Andreas; Fietkau, Rainer; Lubgan, Dorota; Beckmann, Matthias; Hack, Carolin; et al. (2018)
EVALuna2:35187